Investigation into pore structure regulation and CO2 adsorption mechanisms during PVC synergistic activation of gasification fine slag - Yue Lu; Ying Zhou; Xudong Song; Peng Lv; Jie Xu; Lei Li; Linmin Zhang; Yuchen Shi; Yonghui Bai; Guangsuo Yu; Min Yao (Fuel, 2027)

Xanthan gum-calcium chloride coating preserves postharvest strawberry quality via regulating antioxidant system - Hongyan Lu; Mengyan Li; Yang Yi; Hongxun Wang; Ting Min (Postharvest Biology and Technology, 2027)

Linking branch hierarchy to wave attenuation: from perspective of vortex dynamics - Peng Yao; Lu Li; Min Su; Hongnan Tang; Qian Zhang; Qinghua Ye (Coastal Engineering, 2027)

Performance and mechanism investigation of CO2 adsorption materials prepared from rich carbon gasification fine slag and PVC synergy - Ying Zhou; Yue Lu; Mingxuan Yin; Xudong Song; Peng Lv; Qinghua Guo; Lei Li; Linmin Zhang; Yonghui Bai; Guangsuo Yu; Min Yao (Fuel, 2026)

Indole alkaloids from the roots of Nauclea officinalis and their chemotaxonomic significance - Shan-Ze Yin; Bao-Chan Liu; Guo-Lan Ma; Jiu-Wei Ma; Xi-Yang Lei; Bin-Bao Wang; Rui Li; Shao-Jie Lu; Wei-Min Gao; Pei-Gang Ouyang; Cai-Feng Ding (Biochemical Systematics and Ecology, 2026)

Mitogenomes of three Sinoxylon species and phylogenetic analysis of Bostrichoidea (Coleoptera) - Hua-Min Fan; Xiao-Yun Wang; Kai Lin; Qian Lu; Qiu-Hong Tao; Jun Li; Xia-Lin Zheng (Molecular Genetics and Genomics, 2026)

Combined use of methyl gallate and N-acyl homoserine lactonase YtnP to inhibit biofilm formation in Burkholderia thailandensis - Kai-Zhong Xu; Di Meng; Lu-Jun Yin; Min Wang; Zhi-Wen Ding; Jing Li (Brazilian Journal of Microbiology, 2026)

Bushen Yijing formula exerts chondroprotective effects in knee osteoarthritis via the ERα/PI3K/AKT signaling pathway: Insights from network pharmacology and experimental validation - Yu-Qing Zhai; Jian-Wei Lu; Qiang Yan; Jia-Wei Du; Yang-Shuo Ge; Min-Jun Zhao; Jian-Li Yin; Chun-Meng Huang; Ting-Ting Meng; Xin-Hui Huang; Liao-Lin Chen; Jia-Hui Luo; et al. (Tissue and Cell, 2026)

Global, regional, and national burden of schizophrenia and its environmental drivers, 1990-2021: Retrospective analysis and projections to 2040 - Yixin Liu; Xiangyu Fan; Jiayue Yu; Shaonan Tong; Ying Sun; Pu Lei; Liangjia Wang; Min Jia; Xiancang Ma; Lichun Qiao; Peiqi Lu; Hong Li; et al. (Journal of Environmental Sciences, 2026)

Bioinspired peptidomimetics combat bacterial resistance via “trap-and-kill” strategy by self-assembly into bacteria-responsive nanonets - Yuhang He; Jie Su; Panpan Wang; Muhammad Subaan Fareed; Yaqi Lu; Zhaopeng Wang; Min Li; Daicao Wan; Feiyun Gao; Han Liu; Kairong Wang; Xianxing Jiang (Chemical Engineering Journal, 2026)

Dual-induced Ni/CoOOH generation on lignin-derived carbon decorating MoNi3-Co3Mo heterostructure for enhanced urea electro-oxidation - Ruyu Zhang; Yihao Xu; Jiacheng Huang; Qiuyi Huang; Jiawei Li; Guorong Wang; Yuan Yao; Jiaxing Lu; Douyong Min; Changzhou Chen; Minsheng Lu; Guangfu Qian (Chemical Engineering Journal, 2026)

Customizable self-supporting upconversion aerogels from assembly of nanowires - Xiumei Chen; Xingyu Li; Jiahui Wu; Ruikai Shi; Weiqiu Kang; Min Lu; Juan Wang; Ze Yuan; Wei Huang; Xiaoji Xie (Chemical Engineering Journal, 2026)

Biosensor-driven adaptive laboratory evolution and modular pathway engineering for high-level production of nicotinamide mononucleotide in yeast - Ruirui Shi; Qiancheng Han; Yingxue Xu; Lei Li; Fuping Lu; Yixun Jiang; Zhengqiang Jiang; Hui-Min Qin (Bioresource Technology, 2026)

Small molecules dually targeting SARS-CoV-2 and host G-quadruplexes: binding mechanism explored by integrated experiments and computations - Long-yu Zhu; Min Zhu; Lu-yan An; Jun-qin Qiao; Wei-juan Zheng; Ju-wen Shen; Li Mao; Hong-zhen Lian (Analytica Chimica Acta, 2026)

Fe(II)-driven abiotic-biotic relay alleviates denitrification bottleneck via chemical nitrite reduction and intracellular carbon - Na Hu; Qi Feng; Chenxi Li; Yuanyuan Liu; Baoli Zhu; Tianci Guo; Lei Tong; Jianbo Shi; Robert A. Sanford; Shuyi Li; Yu He; Yidan Hu; et al. (Water Research, 2026)

Pinellia ternata lectin induces mitochondrial damage and inflammation in RAW264.7 cells via mannose receptor-mediated endocytosis - Yangyi Huang; Jinfei Li; Yue Lu; Jie Cao; Xinzhi Wang; Hao Wu; Min Shen; Hongli Yu (Toxicology and Applied Pharmacology, 2026)

Risk propagation analysis and mitigation strategy for Arctic maritime accidents: An integrated approach of LLM-based event logic graph and Bayesian inference - Lu Wang; Le Zhang; Feng Li; Min Wu; Jun Wu (Ocean Engineering, 2026)

Analytical modeling for uplift resistance of subsea pipelines in loose sand: Local flow-around failure mechanism and smooth-pipe validation - Xiao-Mi Li; Yu-Min Shi; Ning Wang; Xiao-Bing Lu; Fu-Ping Gao (Ocean Engineering, 2026)

Biosorbent based on Ganoderma lucidum mycelium for highly efficient synergistic adsorption of tetracycline-microplastic-Cu2+ composite pollutants - Min Zhang; Qian Chen; Lu Gao; Xiao Li; Xueping Liu; Lihui Chen; Hui Wu; Yonghao Ni; Cuicui Ding (Journal of Environmental Chemical Engineering, 2026)

Magnetic and glycolysis-compatible immobilized Kubu-PM12 for chemoenzymatic cascade depolymerization of PET - Yiman Li; Jincheng Zheng; Jianqi Lu; Liyuan Tang; Jie Zhou; Xiaoli Zhou; Weiliang Dong; Min Jiang (Journal of Environmental Chemical Engineering, 2026)

Molecular hydrogen mitigates hydroxyl radical–driven oxidative deterioration of tilapia myofibrillar proteins: through the lens of redox microenvironment modulation - Zhuo-Feng Gan; Jia-Ying Li; Ying-Zhi Yao; Hui-Min Lu; Xi-Yang Chen; Ming-Shen Zhu; Duried Alwazeer; Xin-An Zeng; Lan Liao (Food Chemistry, 2026)

Influence of erosion process on the resistance of Debris flow induced by rock-ice avalanche (DFRIA): Insights from the flume experiments - Xiangning Li; Jiangang Chen; Lu Zeng; Huayong Chen; Jinshui Wang; Hechun Ruan; Min Huang (Engineering Geology, 2026)

Injectable enzyme-triggered conductive hydrogel for restoring electrical homogeneity and functional recovery in myocardial infarction - Shun Xie; Fengjiao Deng; Ying Lu; Min Li; Shen Shen; Qin Wang; Weidong Li; Linwei Chen (Chemical Engineering Journal, 2026)

Recyclable cellulose-based paper from bleached eucalyptus pulp with high electromagnetic shielding and excellent processability - Gaofeng Cheng; Junjie Liu; Daquan Li; Wei Liu; Weiyu Li; Shaochao Sun; Guangfu Qain; Minsheng Lu; Douyong Min; Changzhou Chen (Carbohydrate Polymers, 2026)

High-resolution urban air temperature mapping and interpretable multi-scale built-environment analysis for climate adaptation in a severe cold-region city - Qi Jia; Jingsi Xie; Fanyu Zeng; Dongliang Han; Shuling Li; Min Zhang; Tiantian Zhang; Lin Lu (Building and Environment, 2026)

Plant and microbial-derived carbon responses to contrasting tillage practices in a 53-year field experiment - Guixin Zhang; Feifei Yao; Yingxin Lu; Leanne Peixoto; Kazem Zamanian; Lingling Shi; Michaela Dippold; Wentao Zhang; Haishui Yang; Antonio Rafael Sánchez-Rodríguez; Jie Zhou; Feng-Min Li (Soil and Tillage Research, 2026)

Retraction notice to “Biochar's dual role in greenhouse gas emissions: Nitrogen fertilization dependency and mitigation potential” [Sci. Total Environ. 917 (2024) 170293] - Hongzhao Li; Liwen Lin; Yutao Peng; Yongzhou Hao; Zhen Li; Jing Li; Min Yu; Xuewen Li; Yusheng Lu; Wenjie Gu; Baige Zhang (Science of The Total Environment, 2026)

Establishment of a new germ-free Spodoptera frugiperda model to explore the gut microbiota on larval, pupal development and adult reproduction - Bin Li; Hai-Dong Sun; Mei Liu; Xin He; Xiao-Long Liu; Min Lu (Journal of Insect Physiology, 2026)

Landfill aging enhances chlorinated organophosphate adsorption on microplastics: Mechanistic insights and elevated risks for biodegradable polymers - Dongsheng Shen; Yujie Xuan; Beixiao Ge; Yaqing Liu; Yuyang Long; Jiali Shentu; Li Lu; Min Zhu (Journal of Hazardous Materials, 2026)

Effect of different structures of β-glucan on extruded starch: physicochemical properties, multiscale structure, and in vitro digestibility - Manman Lu; Yijia Li; Haoyuan Wang; Zhilong Zeng; Ahmed H. Abdullah; Min Zhou; Xiong Liu (Food Chemistry, 2026)

Attenuation of aging by probiotic strains BLa80, LRa05 and their postbiotics through gut microbiota modulation and NF-κB signaling inhibition - Feiran Xu; Qian Li; Lu Zhang; Xiao Shi; Yunjiao Zhao; Shuguang Fang; Lalita Siriwattananon; Min Zhang (Food Bioscience, 2026)

The TLR9/NF-κB and cGAS/STING pathways mediate​ the assembly of the NLRP3 inflammasome induced by Singapore grouper iridovirus DNA - Lifang Cao; Lu Yang; Runjian Huang; Dekun Tang; Zihan Li; Yunxiang Jiang; Min Yang; Qiwei Qin; Shina Wei (Fish & Shellfish Immunology, 2026)

Residential greenness and incident type 2 diabetes: A large prospective cohort study in China integrating evidence from 17 global cohorts - Jian-Cheng Jiang; Chuan-Jiang He; Ai-Min Xu; Lu Wang; Xiao-Qi Zhu; Bei-Bei Li; Wen Liu; Ya Qiu; Jing-Ran Xu; Min-Hui Li; Zhuo-Hao Wang; Xiao-Guang Zou; et al. (Environmental Research, 2026)

Cold exposure induced cognitive impairment: A systematic review - Bing-Yao Liu; Xin-Mei Ma; Si-Wei Wang; Qi-Feng Li; Jun-Hua Chen; Sen Li; Hai-Yan Wang; Xiu-Min Lu; Yong-Tang Wang (Cryobiology, 2026)

Sulfur-driven hidden carbon flux enables reductive dechlorinating in sulfur-metabolism biofilm - Zhou-Yang Li; Han-Bing Xiao; Min Li; Xue-Ning Zhang; Kun Zheng; Ai-Jie Wang; Yi-Lu Sun (Chemical Engineering Journal, 2026)

The characteristics and mechanism of phosphorus adsorption and release of extracellular polymeric substances in biofilms based on phosphorus recovery - Min Ni; Zhiwen Dong; Ruijing Wu; Yu Wang; Wenle Yang; Can Zhang; Dapeng Li; Yong Huang; Lu Li; Yanyan Ding; Chuanming Yang; Yang Pan (Bioresource Technology, 2026)

Deep soil water acquisition at low water potentials sustains photosynthesis but compromises water-use efficiency in apple trees on the Loess Plateau - Haoyan Wei; Yanwei Lu; Ran Yu; Guangyuan Wei; Xia Wang; Mingyi Wen; Brent Clothier; Wei Hu; Chamindu Deepagoda; Min Li (Agricultural and Forest Meteorology, 2026)

Biofabrication and artificial intelligence strategies for investigating solid- and fluid-pressure mechanobiology in pancreatic ductal adenocarcinoma - Yahui Ding; Peiyuan Zhao; Yan Jin; Yan Li; Zifei Wang; Ye Lu; Yichen Zhang; Hongzhuan Chen; Weidong Zhang; Xin Luan; Min Tang (Cancer and Metastasis Reviews, 2026)

Galectin-3 in systemic lupus erythematosus: a meta-analysis - Yang Wu; Li-Na Jiang; Jing-Ru Wu; Yi-Ran Lu; Ting-ting Lu; Ji-Min Zhu; Jing Li; Shanshan Xu; Bai-Kun Li; Cheng-Gui Miao; Yan-Mei Mao (Immunologic Research, 2026)

Corrigendum to “A phospho-switch centered on OsAHL23 orchestrates immune homeostasis in rice” [Sci. Bull. 71(11) (2026), 2701-2705] - Zhaotang Ma; Qi He; Haicheng Liao; Junjie Yin; Xiaobo Zhu; Xiang Lu; Li Song; Long Wang; Hai Qing; Yu Fang; Kangjian Niu; Langqing Chen; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Evaluation of a full-scale two-stage anoxic/oxic–ultrafiltration–reverse osmosis process for landfill leachate treatment: Performance and microbial community succession - Erming Luo; Jia Ouyang; Xiaoqin Li; Honggang Chen; Zhongjie Lei; Min Shen; Xinxin Zhang; Qian Lu; Dong Wei; Chunying Li; Li Wei (Journal of Water Process Engineering, 2026)

Waste cotton textiles-derived cellulose superhydrophobic aerogel for efficient oil-water separation - Ya-hui Li; Hui-Jiang; Xiao-quan Zhu; Ru-ru Ma; Er-min Zhou; Jun-li Luo; De-qiang Li; Hong-tao Jia; Jun Li; Lu-xiang Wang (Journal of Water Process Engineering, 2026)

From solvent-tailored carbon dots to a practical sensor array: fingerprint discrimination and quantification of azo dyes in beverages - Zhi-Min Zhi; Zong-Mei Huang; Cong-Ting Wu; Jing Li; Yanting Song; Lu-Shuang Li (Food Chemistry, 2026)

Effects of yeast β-glucan on the digestibility of extruded corn starch with varying amylose contents - Manman Lu; Haoyuan Wang; Zhilong Zeng; Ahmed H. Abdullah; Yijia Li; Muhammad Wasim; Min Zhou; Xiong Liu (Food Bioscience, 2026)

Orbital symmetry matching-mediated synergistic N2/CO2 activation on Cu-Co3O4 for photocatalytic urea synthesis - Meng Qiao; Yan-Fei Mu; Ji-Li Zhou; Su-Xian Yuan; Meng-Ran Zhang; Min Zhang; Tong-Bu Lu (Chemical Engineering Journal, 2026)

Millennium-scale dynamics of microbial carbon metabolism genes in coastal soils along a reclamation chronosequence - Min Wang; Yiling Wang; Hanzhu Li; Yuchen Lu; Xinyi Xu; Hang-Wei Hu; Jizheng He; Bin Ma; Xiaofei Lv (CATENA, 2026)

IGF-1 Inhibits the Hemodynamics‑Induced Progression of Intracranial Aneurysms by Modulating the Proliferation and Apoptosis of Vascular Smooth Muscle Cells - Si-si Li; Zhi-wen Lu; Yin Luo; Hai-shuang Tang; Bo Hong; Yu Zhou; Jian-min Liu (Translational Stroke Research, 2026)

Tumor cell-intrinsic TET3 restrains type I interferon signaling and anti-tumor immunity - Lu Liu; Wenxuan Zhao; Tianbao Shang; Bo Xu; Mengyuan Wang; Xinze Li; Jie Min; Wenqi Xu; Hongjie Shen; Li Tan; Yujiang Geno Shi (Science China Life Sciences, 2026)

Crop diversification drives microbial-mediated nitrogen accumulation via fungal necromass stabilization - Chunyan Liu; Guixin Zhang; Wentao Zhang; Yingxin Lu; Haishui Yang; Feng-Min Li; Jie Zhou; Lingling Shi (Agriculture, Ecosystems & Environment, 2026)

Temporin-GHaR6R Peptide Ameliorates Experimental Autoimmune Encephalomyelitis by Suppressing Microglial M1 Polarization and Mitochondrial Dynamics Dysfunction - Da-Qi Zhang; Hui-Min Xu; Jing Lu; Yu-Sheng Huang; Xiao-Li Feng; Li-Jun Chen; Wen-Jie Zhao; Rong Wang; Yingxia Zhang; Qifu Li (Probiotics and Antimicrobial Proteins, 2026)

Linking the dietary inflammation index to sarcopenia in diabetes: mediation by body roundness index and evidence from complementary analyses - Yang Yang; Ren-hua Lv; Peng-min Liu; Yan-qiu Sun; Lu-ping Wang; Yu Yu; Li-mei Zhang; Xin-yang Zhang (European Journal of Applied Physiology, 2026)

Single-cell sequencing reveals the co-option of epithelial structural programs by macrophages in teleost granulomas - Zhengyang Zhou; Jinlai Gu; Zhengran Jian; Jie He; Zhendong Zhong; Quanxin Xiong; Min Qi; Yuanchang Gao; Sheng Lian; Shangjie Bai; Chenwang Lu; Linfeng Kuang; et al. (Aquaculture, 2026)

Tumor-confined nano-activators for antigen-independent broad activation of tumor-infiltrating T cells - Yue Wang; Min Yang; Bao-Yue Zhang; Mei-Tang Peng; Yi-Qun Sun; Shi-Kun Zhou; Wei Li; Xian-Zhu Yang; Shi-Dang Xu; Zi-Dong Lu; Cong-Fei Xu; Jun Wang (Science Bulletin, 2026)

Benzene-induced myelosuppression confers a survival advantage to hematopoietic progenitors: Single-cell analysis of malignant transformation dynamics in a murine model - Jin Zhou; Pinpin Sui; Ying Li; Jinxu He; Yedan Lu; Min Zheng; Xiangrong Song; Tao Yu; Xiurong Cheng; Caihong Xing (Journal of Hazardous Materials, 2026)

Acidification reshapes plastisphere communities to sustain potassium-stimulated N2O emissions under warming - Muhammad Ayaz; Yoong-Sin Oon; Yoong-Ling Oon; Min Deng; Lu Li; Kang Song (Journal of Hazardous Materials, 2026)

Flavor-guided superior variety selection for round bell Paojiao: An integrated GC–MS metabolomics and chemometrics study - Ju Chen; Min Lu; Nan Lu; Wenxin Li; Dan Su; Xueya Wang; Xiaojing Sun; Yubing Huang (Food Research International, 2026)

Ankyrin-repeat transmembrane protein WAI-1 confers multiple disease resistance in wheat by activating autoimmunity - Qiuhong Wu; Wenling Li; Yongxing Chen; Huaizhi Zhang; Delin Li; Zhan Li; Fei Xiong; Guanghao Guo; Lei Dong; Xuejia Cui; Jingzhong Xie; Ping Lu; et al. (Science China Life Sciences, 2026)

A new perspective on real-time monitoring and function interpretation of nitrification based on machine learning and mass-to-charge fingerprint - Chen-Shun Lu; Shilong He; Chunmiao Wang; Jiaxun Guo; Yunzhi Qian; Yonghao Zhu; Xiaoliang Fan; Jiayao Ding; Shen Han; Chao Li; An Xu; Bo Nie; et al. (Water Research, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Shifting paradigms in phosphorus recovery: A comprehensive review from activated sludge to biofilm - Lu Li; Xiaoya Wang; Abraham Mamusha; Ye Zhu; Yong Huang; Min Ni; Yang Pan; Yu-You Li (Resources, Conservation and Recycling, 2026)

A phospho-switch centered on OsAHL23 orchestrates immune homeostasis in rice - Zhaotang Ma; Qi He; Haicheng Liao; Junjie Yin; Xiaobo Zhu; Xiang Lu; Li Song; Long Wang; Hai Qing; Yu Fang; Kangjian Niu; Langqing Chen; et al. (Science Bulletin, 2026)

Streptochlorin from Streptomyces youssoufiensis YMF3.862 as a potential ecological fungicide for controlling Fusarium head blight on wheat - Min Chen; Chen-Xin Ma; Madjiengui Grace Dieuveille; Xiu-Min Zhang; Lu Wang; Li Ma; Yi Cao; Zi-Xiang Yang; Pei-Ji Zhao; Ming-He Mo (Pesticide Biochemistry and Physiology, 2026)

Pilot-scale verification and mechanism analysis of IFAS enhancing phosphorus recovery and nitrogen removal: A comparison with conventional activated sludge - Xiaoya Wang; Xiangyu Fei; Tianyu Pan; Ye Zhu; Min Ni; Yong Huang; Yang Pan; Lu Li (Journal of Environmental Chemical Engineering, 2026)

Warming-acidification synergy amplifies plastisphere-mediated nitrous oxide emissions - Muhammad Ayaz; Liu Wenjing; Min Deng; Lu Li; Kang Song (Journal of Environmental Management, 2026)

Inhibition of the TLR-TNF-HIF-1α pathway attenuates trimethylamine and inflammation by arabinoxylan and glycolysis inhibitors - Yanxiao Chen; Qian Li; Yu Song; Lu Zhang; Min Zhang (Food Bioscience, 2026)

Characterization and biological activity of djulis (Chenopodium formosanum) phytosomes and in vivo cosmeceutical applications - Chien-Shan Chiu; Yung-Jia Chan; Min-Hsuan Wu; Bing-Lun Hua; Wen-Chien Lu; Zeng-Chin Liang; Po-Hsien Li (Food Bioscience, 2026)

Dynamic cultivar-soil interactions drive accelerating genetic gains in a dryland wheat system - Yuan Li; Yong-He Zhu; He-Peng Lu; Neng Wang; Fu-Ying Cheng; Yan-Lei Du; Feng-Min Li (Field Crops Research, 2026)

Unveiling the modulatory role of microplastics in the release of chlorinated organophosphorus flame retardants from landfill soils - Li Lu; Yujie Xuan; Xuke Wang; Beixiao Ge; Yuyang Long; Jiali Shentu; Dongsheng Shen; Min Zhu (Environmental Research, 2026)

DeepLrn-Source: Deep learning powered landslide source identification - Lu-Yu Ju; Ze-Ning Zhao; Shi-Hao Xiao; Yuan-En Pang; Jian He; Yun-Hong Lv; Ruo-Chen Jiang; Xin He; Li-Min Zhang (Engineering Geology, 2026)

Octopus-inspired photonic-electronic synergistic hydrogel tactile sensor for accurate and reliable health monitoring - Boqing Jia; Changxu Zhang; Yihe Zhao; Lan Yu; Yibo Lv; Gengyu Han; Xinyu Shi; Zhuorui Chen; Xuanting Lu; Jiaxiang Wang; Min Li; Guoxi Luo; et al. (Chemical Engineering Journal, 2026)

Experimental investigation of contaminant dispersion in vertical drainage pipes induced by toilet flushing - Di Mu; Min Chang; Lu Feng; Ruibin Li; Yan Wu; Naiping Gao (Building and Environment, 2026)

Antimicrobial resistance analysis of Escherichia coli isolated from foxes in China - Hao Ni; Jiagong Hou; Qing-Yu Hou; Chao Xu; Xue Leng; Xue-Min Li; Ya Qin; Shuo Liu; Meng-Ting Yang; Lu-Yao Tang; Yu-Zhe Sun; Quan Zhao; et al. (Veterinary Research Communications, 2026)

Improved eradication of apple stem grooving virus and apple chlorotic leaf spot virus in apple rootstocks by combining thermotherapy with electrotherapy - Xiao-Yan Ma; Qing Li; Zhi-Wei Kang; Ming-Yuan Jing; Ya-Ting Zhang; Min-Rui Wang; Dong Zhang; Lu Bao; Juan-Juan Ma (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Non-ignorable dipeptides as nitrogenous precursors in chlor(am)ination: Tyrosyl-L-phenylalanine generates higher toxicity to mammalian cells than aromatic monomeric amino acids - Yiyi Hu; Yao Lu; Yuen Guo; Hua Li; Ying Chen; Min Liu; Wei Hu; Qianyuan Wu; Ye Du (ENGINEERING Environment, 2026)

The application of Milankovitch cycles in determining provenance direction - Ting-yu Zhang; Hui Xue; Ming-guang Hu; Min-shu Wang; Gen Li; Zhen Lu (Applied Geophysics, 2026)

Docosahexaenoic acid alleviates Ornidazole toxicity related to spermatogenic dysfunction by modulating PPARγ-dependent ER-mitochondrial uncoupling - Chuwei Li; Shanmeizi Zhao; Chongli Shi; Shanshan Sun; Zhaowanyue He; Yao Xu; Lu Zheng; Ting Tang; Shengjie Qiu; Kuan Liang; Hong Zhang; Zhichuan Zou; et al. (Science China Life Sciences, 2026)

Enhanced photocatalytic performance of K/O-co-doped crystalline carbon nitride for sulfamerazine degradation and CO2 reduction - Zhendong Hao; Wenjie Li; Wenqing Yao; Shihai Cao; Yao Lu; Haiming Wang; Jong-Min Lee (Chemosphere, 2026)

Submerged plants mitigate nitrous oxide emissions by transforming suspended sediments from free-floating to leaf-attached - Shuni Zhou; Yongxia Huang; Min Deng; Yanlin Xiao; Yuren Wang; Senbati Yeerken; Lu Li; Kang Song (Journal of Environmental Sciences, 2026)

Transition metal-loaded granular activated carbon as efficient three-dimensional electrode for humic acid removal - Jianhong Jiang; Man Yang; Min Huang; Xinyao Guo; Xia Tao; Li Xu; Yue Lu; Lin Tang; Yi Cheng (Journal of Environmental Sciences, 2026)

Lanthanide-polyoxometalate-based anti-swelling luminescent conductive organohydrogel for information encryption and underwater sensing - Xinyu Lu; Jingfang Li; Min Gao; Sicong Zhao; Guangming Li (Chemical Engineering Journal, 2026)

A novel double-layer composite material with excellent radiative cooling and thermal management for electronic devices - Haoxin Lv; Haixuan Liu; Jiahui Lin; Jintao Huang; Hanlin Xie; Xiaofeng Li; Yonggang Min; Xiang Lu (Chemical Engineering Journal, 2026)

Microbial carbon and energy use efficiency after a centennial history of land use - Xinhu Guo; Feifei Yao; Kevin Z. Mganga; Wentao Zhang; Yingxin Lu; Haishui Yang; Feng-Min Li; Lingling Shi; Jie Zhou; Kazem Zamanian (Plant and Soil, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

High-value utilization of chromium ore processing residue (COPR) through corn straw-soda roasting followed leaching processes - Cheng Tian; Zilong Li; Cunfang Lu; Rui Xu; Min Zhang; Lin Yang; Wenlin Xie; Zhengnan Zhong; Yuanyuan He; Juan Wen; Dan Luo (Journal of Environmental Chemical Engineering, 2026)

Source-specific risks of heavy metals in urban–agricultural soils and implications for human health in a liver cancer high-incidence area of Central China - Wei Leng; Lu Li; Haojia Liu; Ling Bai; Min Zhang; Liping Wang; Jiaqi Liu (Journal of Cleaner Production, 2026)

Reductive pyrolysis of heavy metal Gypsum: Impurity phase evolution and transformation pathways - Xiaobo Min; Zidong Tan; Yunyan Wang; Yun Li; Han Lu; Changhao He; Yong Ke; Cong Peng (Journal of Environmental Management, 2026)

Synergistic interactions among ramie (Boehmeria nivea L.), earthworm (Eisenia fetida), and soil microbials in phytoremediation on soil cadmium absorption - Kaiye Li; Chao Zeng; Junliang Liu; Qing Chen; Min Zheng; Yifeng Xu; Chensheng Lu (Journal of Environmental Sciences, 2026)

The strong quantum confinement effect of CsPbI3 quantum dots assists the subthreshold turn-on of light-emitting diodes - Mingze Liu; Min Lu; Rui Li; Junzhe Feng; Chunru Fan; Fujun Zhang; Xue Bai; Yu Zhang (Chemical Engineering Journal, 2026)

Deciphering acetate stress responses in methanogen using D2O-Labeled Single-Cell Raman spectroscopy - Min Li; Xiuxia Meng; Erqi Nie; Dongxue Lu; Rongbo Guo; Shanfei Fu; Jianhua Guo (Bioresource Technology, 2026)

Numerical investigation of toilet flushing and exhaust fan operation on aerosol transmission dynamics in building drainage system - Di Mu; Min Chang; Lu Feng; Ruibin Li; Yan Wu; Naiping Gao (Building and Environment, 2026)

Subcellular Structures in Native Hippocampal Synapses Revealed by Cryo-electron Tomography - Chong-Li Tian; Lei Qi; Zhen-Hang Lu; Shuo Liu; Min-Ling Gu; Wen-Lan Huang; Yi-Tong Yan; Yun-Tao Liu; Jing Wu; Peiyi Wang; Z. Hong Zhou; Guo-Qiang Bi; et al. (Neuroscience Bulletin, 2026)

Quantifying fault-controlled radon degassing induced by Pacific Plate subduction in the Miaodao Archipelago, North China - Shujuan Su; Ying Li; Chang Lu; Yanming Yang; Zhaofei Liu; Fengxia Sun; Jun Liu; Qinglin Wang; Zhigang Liu; Hao Sun; Yaowen Zhang; Chunhong Zou; et al. (International Journal of Earth Sciences, 2026)

The GATA3-RFPL3-ASK1 axis suppresses breast cancer growth and lung metastasis - Kang Li; Chang Liu; Jun-Hui Yin; Yu-Ting He; Zhi-Zhi Xu; Wen-Jing Zhang; Jian-Qi Wang; Lu-Yao Hou; Jing Feng; Le-Min Lin; Xiu-Qing Duan; Yi Zhou; et al. (Apoptosis, 2026)

Leaf Size Variation in Response to Climate Drivers Depends on Plant Life Form - Jiayi Lu; Shihao Wen; Siyu Chen; Yuran Dong; Xiuping Wu; Yao Li; Min Zhang; Zhiwei Ge; Jonathan M. Chase; Lingfeng Mao (Journal of Biogeography, 2026)
Aim Plant leaf size and shape vary across major climatic gradients, reflecting the mechanisms for how plants regulate the balance of carbon, water, and heat. However, the influence of climate on leaf traits can be confounded by multiple factors, and the complex variation among different plant groups remains insufficiently understood. Here, we investigated how climate influences leaf size traits and whether this effect is moderated by plant life form. Location China. Taxon Angiosperms. Methods Based on leaf length, width, and aspect ratio data from 26,726 angiosperm species distributed across major climate gradients in China, we analysed the effects of temperature and precipitation on leaf size traits, and compared differences among plant life forms (woody vs. herbaceous and evergreen vs. deciduous). Additionally, spatial heterogeneity was assessed across eight vegetation zones. Results Leaves are generally larger and rounder in warm and humid areas, and smaller and narrower in cooler and more arid areas. All leaf size traits respond more strongly to precipitation than temperature, with leaf length showing the strongest responses to both climate variables. Herbaceous and deciduous species exhibit stronger climate responses nationwide, whereas woody and evergreen species are more sensitive within vegetation zones. Key responsive traits show clear geographic shifts. Main Conclusions Overall, we find that leaf size and shape vary strongly across China, as a result of climate variation, but these patterns are modified by dominant regional ecological processes and the ecological strategies of plant life forms. These findings not only help clarify variation in plant traits along climatic gradients, but also provide a theoretical framework for predicting how different plant morphologies will respond to ongoing climate change.

Protective role of polysaccharide from the roots of Millettia speciosa Champ in mice with ulcerative colitis induced by dextran sulphate sodium - Yanfei Lu; Rihui Wu; Jiaquan Liu; Jinwen Huang; Qiu Liu; Min Yao; Jingyu Wu; Jiming Ye; Dongli Li; Lishe Gan; Jingwei Jin (Natural Product Research, 2026)

Chronological and climatic insights from Karst Cave Silt Sediment in Southwest China - Yuan-Yuan Mu; Qing-Duo Wang; Chang-Sheng Wang; Tian-Zhou Zhang; Shao-Qin Ma; Jing-Ming Yang; Hai-Cheng; Wen-Jun Sun; Jun-Yun Li; Yan-Min Dong; Lu-Peng Yu; Ting-Yong Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Alleviating microbial nitrogen immobilization by ditch-buried straw return improves wheat yield via enhancing pre-anthesis growth performance - Zhenzhen LI; Xinhu GUO; Lu WANG; Kelsang CHODRON; Jian LIU; Yafeng WEI; Feng-Min LI; Yaguang XUE; Haishui YANG (Pedosphere, 2026)

Microbial efficiency drives depth-dependent soil carbon storage under organic fertilization - Wentao Zhang; Yingxin Lu; Leanne Peixoto; Cheng Ji; Haishui Yang; Kaihua Wang; Jianwei Zhang; Jidong Wang; Lingling Shi; Jie Zhou; Feng-Min Li; Antonio Rafael Sánchez-Rodríguez (Journal of Environmental Management, 2026)

Body size- and water homeostasis-dependent temperature stress tolerance and transcriptional changes in red fire ant workers - Wei Gao; Rui Peng; Jian-min Yang; Jian-lin Lu; Hong-yun Cao; Ying-huan Li; Chun Li; Wen Fu; Jin Xu (Journal of Asia-Pacific Entomology, 2026)

Drying methods impact bioactive compounds in Siraitia grosvenorii fruit: Metabolomic insights - Li Li; Lihong Xie; Ping Yi; Ting Gan; Zhenmei Fan; Min Huang; Shiqi Wang; Dan Luo; Rui Pang; Fenglai Lu; Jinfeng Sheng; Jian Sun; et al. (Food Chemistry, 2026)

AID/APOBEC-like cytidine deaminases are important mediators of VLR-based adaptive immunity in lampreys - Zihao Yan; Jingjing Lu; Yuesi Zhou; Liang Zhao; Ding Li; Huining Jia; Ayqeqan Nurmamat; Min Xiu; Shuyuan Zhang; Ruyu Zhuang; Ya Pang; Tiesong Li; et al. (Fish & Shellfish Immunology, 2026)

Carboxymethyl cellulose-reinforced adhesive bio-patch for sealing wet tissue defects and bioelectronics - Jianpeng Zhang; Haofan Qu; Qiaoling Li; Gongwei Tian; Qingyang Wu; Min Zhang; Jianguo Li; Shengchang Lu; Dianpeng Qi; Hui Wu (Chemical Engineering Journal, 2026)

Integrative combination of gas–liquid-phase plasma mutagenesis and high-throughput screening to enhance eicosapentaenoic acid production by Schizochytrium sp. - Chao Yu; Jialin Zhu; Jinyong Wu; Xiangsong Chen; Shuhuan Lu; Xiangyu Li; Sa Zhao; Weiwei Zhu; Min Shu; Mianbin Wu; Jianming Yao (Journal of Zhejiang University-SCIENCE B, 2026)

Research on the therapeutic effects of recombinant protein PON1Q/R192 intervention on mice poisoned by different categories of organophosphorus compounds - Shuang Zhou; Yue Cui; Lu Li; Pengsi Zhang; Zhe Zhu; Li Yuan; Min Zhao (Toxicology Letters, 2026)

An mRNA microsphere vaccine inhibiting overactivation of DNA sensing mechanisms - Fangke Zhang; Jiancheng Zheng; Fei Wang; Yaping Zhuang; Yunkai Tang; Juan Wang; Yawei Du; Wei-Li Zhao; Min Lu; Weiguo Hu; Wenguo Cui (Science Bulletin, 2026)

Microplastics affect PAH sorption and migration in soil: Insights from experiments and backpropagation neural network modeling - Linghui Wang; Li Lu; Ting Li; Qingtao Wu; Yong Lai; Yi Shen; Jiali Shentu; Shengqi Qi; Min Zhu; Yuyang Long; Dongsheng Shen; Chao Chen (Journal of Environmental Chemical Engineering, 2026)

Effective recovering Pd(II) ions via tuning the Lewis basicity of nanofiber capture vacancy - Nianshou Cheng; Mingyue Wang; Lu Wang; Lin Zhang; Chuanbin Li; Yu Guo; Bo Xing; Haichao Wang; Min Li (Journal of Environmental Sciences, 2026)

Deciphering the microbial complexity of Chinese traditional sourdough through integrated learning - Yan Liu; Jinyu Wang; Shiwei Zhou; Feijiang Li; Honghong Cheng; Zheqing Zhu; Jiale Wang; Aowen Liu; Ting Lu; Yujuan Yu; Senmiao Tian; Min Zhang; et al. (Food Research International, 2026)

Structural integrity of the teleost granuloma: a macrophage barrier driven by coordinated activation of junctional, cytoskeletal and extracellular matrix gene networks - Zhengyang Zhou; Linfeng Kuang; Chenwang Lu; Jie He; Zhengqiang Yu; Zhendong Zhong; Quanxin Xiong; Min Qi; Jinlai Gu; Yuanchang Gao; Sheng Lian; Zhengran Jian; et al. (Fish & Shellfish Immunology, 2026)

Rapid water-transporting spongy-like porous polyelectrolyte hydrogel evaporator for high-salinity seawater evaporation - Zihui Wang; Junfeng Li; Yuquan Li; Zhiwei Gong; Ting Lu; Min Xu; Likun Pan (Chemical Engineering Journal, 2026)

Trade-offs between stock and stability: Reversing land-use for soil carbon sequestration in a warming world - Wenhao Feng; Yingxin Lu; Chunyan Liu; Khatab Abdalla; Wentao Zhang; Kazem Zamanian; Lingling Shi; Haishui Yang; Feng-Min Li; Jie Zhou; Kevin Z. Mganga (Plant and Soil, 2026)

Tetrandrine inhibits IHNV replication and improves rainbow trout survival likely by targeting Asp-81 on viral phosphoprotein - Min Wu; Yi-zhi Shao; Tong-yan Lu; Ai-jun Lv; Li-ming Xu; Jing-zhuang Zhao (Aquaculture, 2026)

Novel analytical approach of vertical vibration of closely spaced pipe pile groups considering soil plug and scattering effects - Kun Meng; Mingchen Zhong; Chunyi Cui; Xiubing Li; Zhenguo Lu; Bo Min (Soil Dynamics and Earthquake Engineering, 2026)

Surface Co-passivation for 1.7 eV wide-bandgap perovskite solar cells with minimal voltage loss to achieve over 23% efficiency - Mengjin Zhang; Yang Guo; Min Wang; Zequn Ma; Xiaogang Yang; Linxing Meng; Hao Lu; Wei Tian; Liang Li (Science Bulletin, 2026)

Pathogen-induced H2O2 triggers phosphorylation of the RNA-binding protein RRM2R to suppress OsMAPKKK18 intron retention for orchestrating rice immunity and growth - Xiang Lu; Yibang An; Wenxiu Lu; Jing Li; Qing Xiong; Miaomiao Zhu; Yao He; Jia Yang; Yue Wang; Zeming Zhang; Xiaorong Gong; Yulong Qian; et al. (Molecular Plant, 2026)

Photocatalytic performance of a new Zn(II)-MOF: Structural insights and dye degradation efficiency - Li Yang; Mithun Kumar Ghosh; Xiangxiang Li; Min Xiong; Lu Lu; Tanmay Kumar Ghorai; Mohd. Muddassir; Zhenjun Song; Minle Han (Journal of Water Process Engineering, 2026)

Curcumin-mediated photodynamic action disturbs TOM70-depedent MIC60 import to damage mitonchondria against breast cancer - Xiang-Yi Zhao; Min Yan; Liang Zheng; Chang-Long Gou; Qi Huang; Liu-Gen Li; Xin-Ran Yu; Jing-Yu Lu; Cui Hu; Si-Han Zhang; Cunqing Kong; Fan Leng; et al. (Journal of Photochemistry and Photobiology B: Biology, 2026)

Synergizing artificial neural networks with SSP-RCP scenarios: Long-Term projection of residential electricity demand in China under climate-economic interactions - Lu Gao; Zhijie Jiang; Min Lei; Qinyun Lei; Ran Liu; Lu Sun; Shuichi Ashina; Zhaoling Li (Journal of Cleaner Production, 2026)

Ecological compensation for national parks based on carbon sink and ecosystem services - Zekun Yi; Donghe Li; Min Lu (Journal of Environmental Management, 2026)

Identification and in-silico screening of ACE-inhibitory peptides from casein hydrolysate via fermentation with different probiotics - Ruiqi Ren; Lu Liu; Xiaodong Li; Xiuxiu Zhang; Min Xu; Zhixing Zhang; Xuezhen Wang; Bingbing Mu; Xianlu Zhang; Aruna Zhou (International Dairy Journal, 2026)

Hypoxanthine accumulation caused by mutations of Bombyx mori xanthine dehydrogenase triggers female sterility - Wen-qing Lai; Zhan-peng Lu; Qiang Zhang; Zuo-min Shao; Han Gao; Xia Sun; Sheng Qin; Xue-yang Wang; Mu-wang Li (Insect Biochemistry and Molecular Biology, 2026)

Sequential thermal processing strategies reduces purine contents in Turkey meat - Chuanli Hou; Lu Xiao; Zhiting Huang; Wanqian Sha; Kaiqiang Li; Min Wang; Yanbo Wang; Jiaoyan Ren (Food Chemistry, 2026)

Copper mediates oxidative stress and immune response in snakehead (Channa argus) through Nrf2 and NF-κB pathway - Xue-qin Wu; Ming-ze Li; Lu Lu; Xiu-mei Chen; Xiao-tian Niu; Yi-di Kong; Gui-qin Wang; Chang-ge Xia; Min Li (Fish & Shellfish Immunology, 2026)

Phosphorus recovery from wastewater by enhanced microbial electrolysis cell: Cathode modification and circulation operation - Xinyu Lu; Wei Pei; Xiang Liu; Lintao Wang; Haoning Zhao; Min Li (Environmental Research, 2026)

Ti3C2-Cl-Bi12O17Cl2/Bi12O17Cl2 Mott-Schottky heterojunction with mixed noncovalent/covalent type to boost ultra-sensitive photoelectrochemical sensing of ciprofloxacin - Chu-Chu Hu; Qi-E Zhang; Shao-Peng Shi; Guo-Qing Zhao; Yan-Sha Gao; Ping Liu; Xun-Kuan Ye; Yan Pan; Hui-Qing Lv; Li-Min Lu (Chemical Engineering Journal, 2026)

Ferroelectric-polarization-induced high-rate performance: 120C achievement with porous Na3Fe2(PO4)P2O7 and nano-BaTiO3 composite cathodes for sodium-ion batteries - Luting Kou; Xi Chen; Huimin Liu; Shuoshuo Cheng; Mengting Wu; Min Li; Ying Bai; Yibo Wang; Qian Dong; Jiahui Qian; Shiyu Li; Wei Lu (Chemical Engineering Journal, 2026)

Corrigendum to “starch and castor oil mutually modified, cross-linked polyurethane for improving the controlled release of urea” [carbohydrate polymers 251 (2021) 117060] - Hongyu Tian; Zeli Li; Panfang Lu; Yong Wang; Cong Jia; Huaili Wang; Zhiguang Liu; Min Zhang (Carbohydrate Polymers, 2026)

Ginsenosides secreted by Panax notoginseng promotes the growth and pathogenicity of Fusarium oxysporum through enhancing antioxidant capacity - Lifen Luo; Rong Lu; Rong Yin; Guangxiang Tian; Yiwen Li; Guixiang Li; Hongwei Zhu; Jianqiang Miao; Jianjun Hao; Xili Liu; Shusheng Zhu; Min Yang (Plant and Soil, 2026)

RrLHY regulates arginine biosynthesis by activating RrNAGS1 in Rosa roxburghii fruit - Xufeng Yang; Nanyu Li; Richard Ludlow; Qianmin Huang; Zhaoxin Wu; Liangliang Li; Hong Nan; Huaming An; Min Lu (Plant Cell Reports, 2026)

Modulating NLRP3 Inflammasome Activity and Enhancing Cortical Synaptic Plasticity: Nanoparticulate Hydrogen’s Role in Relief of Post-traumatic Anxiety-like Behaviors in Rats - Lanxia Wu; Congwen Yang; Yiqin Ding; Xinru Liu; Hao Sun; Xue Li; Yining Lu; Lifen Liu; Qingyang Fu; Min Li; Yingshuai Wang; Yuehan Zhao; et al. (Molecular Neurobiology, 2026)

Spatial aggregation trends of cultivated land quality and landscape patterns: A remote sensing analysis - Mengmeng Tang; Wenlong Cheng; Zhengbao Gao; Fahui Jiang; Shang Han; Danyang Xu; Rongyan Bu; Shan Tang; Rui Zhu; Min Li; Hui Wang; Changai Lu; et al. (Applied Soil Ecology, 2026)

Spatial phylogenetics and biocultural conservation of medicinal plants in ethnic minority communities of china: implications for environmental sustainability - Da-Cheng Hao; Yaoxuan Wang; Zhi-Duan Chen; Li-Min Lu; Pei-Gen Xiao (Biodiversity and Conservation, 2026)

A coral-derived neuropeptide suppresses pentylenetetrazol (PTZ)-induced epileptic seizures and improves recognition memory deficits by modulating NPY-Y1R - Qian Chen; Congshuang Deng; Xiaoshan Huang; Aili Wang; Nan Xu; Kaixun Cao; Min Yang; Shang Li; Qiumin Lu; Guiyi Gong; Simon Ming-Yuen Lee (Archives of Toxicology, 2026)
Epilepsy is a prevalent neurological disorder characterized by recurrent and unprovoked seizures. Despite the availability of anti-epileptic drugs (AEDs), a significant number of patients are still suffering from drug-resistant epilepsy. Neuropeptide Y (NPY) signaling system has emerged as a potential target for the development of anti-epileptic drugs due to its modulation of epileptic activity. In this study, we investigated the therapeutic potential of our previously discovered Scleractinia-derived NPY-like peptide (TpNPY) in seizure disorders. The anticonvulsant effects of TpNPY were evaluated using PTZ-induced seizures in zebrafish and mice in vivo. Furthermore, the underlying molecular mechanisms of TpNPY were assessed using glutamate-induced excitotoxicity models in HT22 mouse hippocampal cells in vitro. Our findings indicated that TpNPY could alleviate PTZ-induced seizure behavior, reduce the expression of seizure-associated immediate-early genes and the production of Reactive Oxygen Species (ROS) in zebrafish. In mice, TpNPY improved seizure behaviors, decreased inflammatory cytokine levels, and ameliorated abnormal glial activation in a PTZ kindling epileptic model. Besides, the administration of TpNPY could attenuate the PTZ-induced anxiety levels and improve recognition memory deficits. Moreover, TpNPY promotes neurogenesis and neural synaptic plasticity through the BDNF/TrkB signaling pathway. Additionally, TpNPY restored cell injury and attenuated oxidative stress in glutamate-challenged HT22 cells through the Nrf2/HO-1 signaling pathway. These results highlight the potential therapeutic efficacy of TpNPY in the treatment of seizures and provide new insights into the development of coral-derived anti-epileptic peptide-based drugs.

Synergistic antifungal activity and mechanism of carvacrol/citral combination against fusarium oxysporum in Dendrobium officinale - Xuemei Lu; Ke Hu; Minggui Ou; Min Li; Xinchun Zhang; Xingyu Zhan; Xun Liao; Ming Li; Rongyu Li (Pesticide Biochemistry and Physiology, 2025)

Investigating key pressure loss factors in the Wufeng-Longmaxi formation shale gas reservoirs, Southern Sichuan: A quantitative approach - Nengwu Zhou; Guangshun Xiao; Shuangfang Lu; Bo Song; Jun Wang; Zhong Chu; Xinyu Jiang; Yang Liu; Wenbiao Li; Pengfei Zhang; Guohui Chen; Min Wang (Marine and Petroleum Geology, 2025)

Unveiling the dual role of Paracoccus versutus XT0.6 in stibnite dissolution: From aerobic promotion to anaerobic inhibition - Min Li; Hongmei Wang; Xuan Qiu; Weiqi Wang; Xinyue Zhang; Deng Liu; Liyuan Ma; Xiaolu Lu (Journal of Hazardous Materials, 2025)

Simultaneous enhancement of phosphorus release of cell and EPS by carbon source to improve biofilm phosphorus recovery concentration: Performance and mechanism - Ruijing Wu; Min Ni; Yujie Zhang; Huijing Gu; Jiahui Gong; Wenyi Shen; Yong Huang; Yanyan Ding; Lu Li; Yang Pan (Journal of Environmental Chemical Engineering, 2025)

Stabilization of casein-based gels by oxidized konjac glucomannan: the role of ozone generation times - Yijia Li; Yuan Luo; Jianwei Fan; Ahmed H. Abdullah; Haoyuan Wang; Zhilong Zeng; Min Zhou; Manman Lu; Xiaoli Qin; Xiong Liu (Food Research International, 2025)

Tailoring dysphagia-oriented deacetylated konjac glucomannan matrices via oxidative modification - Haoyuan Wang; Manman Lu; Yijia Li; Tianqin Fan; Zhaojun Chen; Zhilong Zeng; Jianwei Fan; Min Zhou; Ahmed H. Abdullah; Xiong Liu (Food Chemistry, 2025)

A modified Iwan model for bolt loosening monitoring in engineering structures: Contact evolution and preload relaxation behavior - Xiaohan Lu; Min Zhu; Shengao Wang; Yilong Liu; Zijian Xu; Ziwei Li (Engineering Structures, 2025)

Synergistic engineering of P-doping and oxygen vacancies combined with LSPR effect to enhance hydrogen evolution performance of P-MoO2-x@C - Jiaqi Liang; Qinfen Tian; Xingyu Chen; Xin Li; Guofa Dong; Yali Xie; Ziyu Lian; Yibin Wu; Juan Lu; Min Niu; Jiandong Zhuang (Chemical Engineering Journal, 2025)

Microbial responses of sulfur-metabolism biofilm to perfluorooctane sulfonate accumulation - Zhou-Yang Li; Min Li; Shan Yi; Xue-Ning Zhang; Wei-Qin Zhuang; Kun Zheng; Yi-Lu Sun; Ai-Jie Wang (Chemical Engineering Journal, 2025)

Acetylated glucomannan-CNT scaffolds with dual-drug release promote hiPSCs-driven cortical regeneration by suppressing inflammation and anoikis - Yue Gao; Wenxi Li; Wanting Lu; Fuqiang Tang; Xian Xiao; Yinggang Li; Jiaxing Huang; Zhiqi Liang; Yuqing Wu; Yanwen Li; Qingjian Zou; Liangxue Lai; et al. (Carbohydrate Polymers, 2025)

Piceatannol improves autoimmune hepatitis by inhibiting the immune activities of T cells and macrophages through binding with c-Jun - Cong Xu; Chenqi Lu; Wu Wang; Zhimin Wang; Yang Qiu; Min Han; Jun Yang; Shanglin Li (Immunologic Research, 2025)

Research on the Reinforcement Effect of the Elephant-Foot Method in Aeolian Sand Tunnels - Ji-hua Qin; Xi-peng Li; Ya Wang; Xiao-li Cao; Dong Li; Yi-guo Xue; Fan-meng Kong; Hui-min Gong; Bang-xiang Li; Chao Lu; Guang-kun Li (Applied Geophysics, 2025)

Insights into freshwater lake abiotic and biotic carrier biofilm nitrogen transformation and N₂O emission patterns: A 15N isotope tracing study - Yunpeng Xue; Lu Li; Min Deng; Kang Song; Fengchang Wu; Akihiko Terada (Water Research, 2025)

Recent advances in flavonoids benefiting intestinal homeostasis - Yawen Luo; Yingqi Li; Changxiao Shi; Shengnan Min; Boya Li; Yan Lu; Binghai Cao; Huawei Su; Yang He (Trends in Food Science & Technology, 2025)

Fracture influence on karst development in carbonate reservoirs: Insights from the Lichuan karst region, Hubei, China - Hadi Hussain; Lu Yun; Fei Cao; Min Yang; Yan Wang; Xinhua Li; Lin Pan; Xiao Wang; Wakeel Hussain; Faulo James (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Latest Pleistocene to mid-Holocene vegetation changes revealed by multi-proxy analyses at Lop Nur in the eastern Central Asia - Yi-Feng Yao; Kai-Qing Lu; Feng Qin; Guo-An Wang; Qin-Min Yang; Xin-Ying Zhou; David K. Ferguson; Gan Xie; Jin-Feng Li; Bin Sun; Stephen Blackmore; Yu-Fei Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

The integrated treatment of photodynamic therapy and oncolytic Virotherapy: A dual-modal paradigm for breast Cancer - Yixiang Li; Kaidi Wang; Qianhao Min; Hongyu Lu; Guoqing Zhang; Jianhua Yan (Journal of Photochemistry and Photobiology B: Biology, 2025)

The dual role of organic carbon: Mitigation of nitrogen-induced soil acidification but amplification of greenhouse gas emissions - Lin Zhao; Qinghua Li; Yufang Lu; Hongmei Chen; Ju Min; Ren Fang Shen; Xue Qiang Zhao (Journal of Environmental Management, 2025)

Simulation experiment evaluation and chemical kinetics prediction of the composition of n-alkanes components - Bo Song; Haitao Xue; Shuangfang Lu; Min Wang; Fangwen Chen; Jinbu Li; Nengwu Zhou (Fuel, 2025)

Exploring the prebiotic potential of sugar beet fiber through in vitro fecal fermentation: modulation of gut microbiota and associated metabolic signature - Xianting Li; Yingxuan Feng; Youyang Ye; Min Guo; Wenwei Lu; Jianxin Zhao; Yue Xiao; Wei Chen (Food Bioscience, 2025)

A source-oriented precise risk assessment of trace metal(loid)s in sediments of the Yangtze River Basin - Kuo Pang; Lu Liu; Junlan Yang; Hongjun Zhao; Wei Hu; Xiaonan Ji; Yali Guo; Min Li (Environmental Pollution, 2025)

Preparations of multifunctional iron(III)-TAML bonded cyclodextrin polymers to efficiently inactivate diverse waterborne pathogenic microorganisms - Zhihui Lu; Dingsheng Zhao; Kun Wang; Qingquan Liu; Min Li; Haiyun Zhang; Xiyun Cai (Chemical Engineering Journal, 2025)

Field-deployable automated evanescent wave fluorescence optofluidic biochip for ultrasensitive detection of clenbuterol residues in complex animal urines - Min Wang; Siyan Liu; Laiya Lu; Jingjing Liu; Feng Long; Chunsheng Li (Chemical Engineering Journal, 2025)

Biodegradable polyurethane-decellular extracellular matrix based bioscaffolds promote nerve repair after spinal cord injury - Mingtao Luo; Jingjing Lin; Junhong Li; Min He; Huanrui Hu; Xiao Wang; Jiehua Li; Cong Wu; Lu Ma; Yanchao Wang; Hong Tan (Chemical Engineering Journal, 2025)

Various formation pathways of size-resolved secondary organic aerosols at a coastal site in Eastern China - Meng-Xue Tang; Jia-Yuan Wang; Ke-Jin Tang; Wen-Jie Yu; Li He; Xiao-Feng Huang; Ling-Yan He; Hui Zeng; Si-Hua Lu; Min Hu (Atmospheric Environment, 2025)

Ammonia and nitrite oxidation dynamics in the Changjiang (Yangtze) River Estuary: linking with productivity and oxygen consumption - Zhen-Zhen Zheng; Yutan Wang; Guiyi Ma; Qianhui Li; Jin-Yu Terence Yang; Anshuai Lu; Sijing Kang; Moyang Li; Xiuli Yan; Min Nina Xu; Li-Wei Zheng; Ehui Tan; et al. (Acta Oceanologica Sinica, 2025)

Development and Application of Infectious Hematopoietic Necrosis Virus Antigen-Specific DAS-ELISA Detection Method - Jing-Zhuang Zhao; Min Wu; Li-Ming Xu; Yi-Zhi Shao; Wei-Tong Liu; Tong-Yan Lu (Fishes, 2025)
Infectious hematopoietic necrosis virus (IHNV), a salmonid rhabdovirus, causes severe mortality exceeding 90% in both wild and farmed salmon and trout. Frequent outbreaks of IHNV highlight the urgent need for rapid detection methods to support effective prevention and control. This study developed a double-antibody sandwich ELISA (DAS-ELISA) targeting the nucleocapsid (N) protein of IHNV. Two peptides derived from the N protein—selected for their strong antigenicity, high level of conservation, and surface accessibility—were used as immunogens to generate two specific monoclonal antibodies. Following optimization, the DAS-ELISA was established using monoclonal antibody N-15 as the capture antibody and horseradish peroxidase (HRP)-conjugated antibody N-106 as the detection antibody. The results of this study demonstrated that DAS-ELISA exhibited high specificity for multiple IHNV strains and showed no cross-reactivity with IPNV, SVCV, or VHSV. The detection sensitivity of DAS-ELISA for IHNV was determined to be 103 TCID50/mL. Parallel analysis of 293 clinical samples using DAS-ELISA and WOAH reference method demonstrated a concordance rate of 92.83% (κ = 0.856). These results confirm that the established DAS-ELISA exhibits high sensitivity, specificity, broad-spectrum applicability, and repeatability. In conclusion, this DAS-ELISA provides a reliable and efficient tool for high-throughput early detection of IHNV infection in clinical settings.

Deep learning-based species identification of gymnosperm xylem: The practice in digital forestry - Chang Zheng; Tuo He; Lichao Jiao; Yang Lu; Shoujia Liu; Tianxiao Li; Yuanyuan Miao; Dejun Feng; Jian Lin; Xian Feng; Zhonghua Huang; Min Yu; et al. (Computers and Electronics in Agriculture, 2025)

Unraveling the influence of naphthalene on methane production from anaerobic digestion of waste activated sludge - Yanxin Wu; Junyi Li; Min Lu; Ke Tian; Chao Wu; Manyu Wang; Zifan Guo (Science of The Total Environment, 2025)

Phylogenomic insights into historical biogeography and species delimitation of African Ampelocissus (Vitaceae) - Romer Narindra Rabarijaona; Jin-Ren Yu; Zhi-Yong Tang; Rindra Manasoa Ranaivoson; Russell L. Barrett; Mijoro Rakotoarinivo; Bing Liu; Yi-Chen You; Samaila S. Yaradua; Romeo Gbiribou; Jun Wen; Zhi-Duan Chen; et al. (Molecular Phylogenetics and Evolution, 2025)

Effect of dimethyl phthalate and salinity on barium bioavailability and bioaccessibility in the soil-plant-human systems near a shale gas development area - Yan Li; Xingmin Cen; Weihan Yu; Xiaoyu Wang; Yutong Li; Min Xu; Aqiang Ding; Daijun Zhang; Junou Pan; Hongcheng Bai; Peili Lu (Journal of Hazardous Materials, 2025)

Sediment remediation by La-MOF/PP fabric coupled with phosphate solubilizing bacteria: Phosphate activation and removal - Qinqin He; Wenhao Lu; Hang Zhou; Xiaonan Ji; Wei Hu; Kuo Pang; Zedong Teng; Xin Zhao; Lintao Wang; Keyu Fan; Feichao Hu; Min Li (Journal of Environmental Chemical Engineering, 2025)

Simultaneous removal and efficient enrichment of low-concentration phosphate in municipal sewage by biofilm process - Yanyan Ding; Jingzi Shi; Lu Li; Min Ni; Xingyu Zhang; Yong Huang; Yang Pan (Journal of Environmental Chemical Engineering, 2025)

Application potential of submicron-sized bamboo cellulose as natural Pickering emulsion stabilizers: Structural properties and stabilization mechanisms - Chen-long Hou; Hao-tian Wei; Chang Liu; Hui-min Yang; Li-Chun Chen; Jian-ping Xu; Lu-yao Wang; Xiu-hua Rao; Jian-jun Huang; Qing Ge (Food Chemistry, 2025)

Microplastics transport and impact on nitrogen cycling and N2O emissions in estuaries - Muhammad Ayaz; Yoong-Sin Oon; Yoong-Ling Oon; Kifayatullah Khan; Min Deng; Lu Li; Kang Song; Xiaoyan Jiang; Zhiwei Xia (Environmental Pollution, 2025)

Associations of urinary biomarkers of exposure to drinking-water disinfection by-products with haematological parameters and systemic inflammation indices among women undergoing assisted reproductive technology treatment - A-Xue Liu; Yu Miao; Min Zhang; Xiao-Ying Liu; Yan-Ling Deng; Jia-Yue Zeng; Yang-Juan Li; Wen-Qing Lu; Chang-Jiang Liu; Qiang Zeng (Environmental Pollution, 2025)

A high-efficiency urea electrolysis catalyst: Sulfur-doped lignin-derived carbon-encapsulated NiCo@MoO2 with triphasic interface and superhydrophilic/superaerophobic surfaces - Jiawei Li; Yunpeng Wang; Changzhou Chen; Xinyu Cao; Liancen Li; Yihao Xu; Ruyu Zhang; Jinli Chen; Minsheng Lu; Douyong Min; Guangfu Qian (Chemical Engineering Journal, 2025)

Construction of efficient proton channels with silica-encapsulated carbon nanotubes for proton exchange membrane water electrolysers - Min Huang; Yang Li; Haochen Lu; Siyi Gao; Felix Kwofie; Xinyao Guo; Quentin Meyer; Yi Wang; Chuan Zhao; Nanwen Li; Yi Cheng (Chemical Engineering Journal, 2025)

Catalyzing polysulfides redox reactions by p-d orbital hybridized ZnCoSe with built-in electric field - Zhengwei Yang; Peng Zhou; Tianyu Zhang; Jiali Liu; Ningxi Lu; Dengke Li; Min Liu; Guang Li; Jincang Su; Manfang Chen; Xiukang Yang; Hongbo Shu; et al. (Chemical Engineering Journal, 2025)

Biofilm-mediated mitigation of N2O emissions in submerged macrophytes area of freshwater lake - Yongxia Huang; Min Deng; Xiaoyan Jiang; Lu Li; Shuni Zhou; Zezheng Wang; Kang Song; Fengchang Wu (Chemical Engineering Journal, 2025)

HMGA2 Attenuates Tendon Stem/Progenitor Cell Senescence Via PI3K/AKT-Mediated Mitophagy Activation and SASP Suppression - Hao Wang; Guang-Chun Dai; Yu-Cheng Gao; Xiao-Yu Liu; Pan-Pan Lu; Mu-Min Cao; Ren-Wang Sheng; Liu Shi; Zhang Cheng; Ying-Juan Li; Yun-Feng Rui (Stem Cell Reviews and Reports, 2025)

Genetic burden and multidimensional predictors in prenatal diagnosis of fetal congenital diaphragmatic hernia - Ruibin Huang; Fang Fu; Shanshan Mei; Liyuan Liu; Wei Zhong; Jin Han; Qiuxia Yu; Hang Zhou; Chunling Ma; Li Zhen; Min Pan; Qiong Deng; et al. (Human Genetics, 2025)

Dietary calcium promotes growth, lipid metabolism and energy metabolism by activating the Ca2+-Camkkβ-AMPK signaling pathway in Pacific white shrimp (Litopenaeus vannamei) - Yu He; Tiantian Xu; Min Jin; Xiaoru Chen; Yinzhao Zhang; Feng Tang; Lu Zhang; Tingting Zhu; Yi Wu; Jinlin Wang; Shuqin Li; Qicun Zhou (Aquaculture, 2025)

Spectral characteristics of organic matter from algae and its complexation with copper: a case study of Ulva prolifera - Tian-Zi Zhang; Li-Min Zhou; Yu-Yuan Wang; Lu Han; Xiao-Yan Cao; Gui-Peng Yang (Marine Environmental Research, 2025)

ABA is involved in OsDSR3-mediated regulation of alkali tolerance in rice - Xuping Lu; Weifang Min; Yangmengfei She; Tinglu Liao; Donghao Xiao; Lei Tian; Peifu Li; Chengke Luo (Journal of Plant Physiology, 2025)

Mechanisms linking triclocarban biotransformation to functional response in sulfur-metabolism biofilm - Zhou-Yang Li; Min Li; Xue-Ning Zhang; Kun Zheng; Han-Bing Xiao; Ai-Jie Wang; Yi-Lu Sun (Journal of Hazardous Materials, 2025)

Humic and fulvic acid-mediated dissimilatory iron reduction coupled with phosphate solubilizing bacteria inducing secondary mineral formation for efficient cadmium immobilization - Gongting Wang; Wenqing Luo; Zedong Teng; Xin Zhao; Yuxin Cheng; Yanzhong Wang; Bin Liu; Mengnan Lu; Min Li (Journal of Hazardous Materials, 2025)

Prebiotic roles and anti-aging effects of xylo-oligosaccharide: Keystone responsive bacteria and their metabolic interactions - Yingxuan Feng; Yue Xiao; Xianting Li; Min Guo; Lijuan Huang; Wenwei Lu; Jianxin Zhao; Wei Chen (Food Research International, 2025)

Phospholipid-cholesterol interactions and their effect on the physicochemical, structural, and in vitro lipid digestion properties of mimicking human milk fat emulsions - Yue Pan; Xueying Zhang; Jiayi Zhao; Xiaodong Li; Lu Liu; Yin Pei; Yimeng Geng; Min Xu (Food Chemistry, 2025)

An injectable carrier-free and self-assembling nanofiber hydrogel with anti-inflammatory and spatiotemporally-controllable anti-VEGF releasing capability for treatment of choroidal neovascularization - Yanghui Xiu; Hui Yuan; Yuanrong Fan; Yu Su; Yujie Zhang; Yuan Xu; Sijie Zhao; Ziqing Gao; Ting Hu; Yan Qiu; Jia-Min Lu; Yuhang Li (Chemical Engineering Journal, 2025)

Poly(acrylic acid)-grafted cellulose nanocrystal reinforced supramolecular adhesives: Ultrahigh strength, humidity resistance, and pH-controlled recyclability - Liying Zhang; Yihan Sun; Shasha Huang; Hongze Xu; Zejun Zhang; Min Jiang; Boxiao Li; Lu Zong; Shuxue Wang; Jianming Zhang (Carbohydrate Polymers, 2025)

Integrative Approaches Identify Genetic Determinants of Levodopa Induced Dyskinesia - Ying Wan; Lu Rong; Qingyuan Li; Suzhi Liu; Wentao Li; Min Ye; Weifeng Luo; Anmu Xie; Jingsong Shao; Dengjun Guo; Xiaoping Zhang; Kezhong Zhang; et al. (Molecular Neurobiology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

(±)-Laevigiol A, a pair of new enantiomeric phenylpropanoids from the leaves and twigs of Croton laevigatus Vahl. and their anti-Alzheimer’s disease activities - Yu-Bin Lu; Mi-Na Yang; Hui-Jie Li; Li-Jia Ye; Le-Le Guo; Miao Zhang; Chun-Min Liu; Xin Wang; Yi-Nan Yang; Zhan-Xin Zhang; Dong-Qing Fei (Phytochemistry Letters, 2025)

Heat stroke-induced central nervous system injury: Mechanisms and therapeutic perspectives - Wenjun Yang; Zhen Gao; Chengjin Wang; Min Wang; Yuan Cao; Yun Li; Shaoqing Shi; Yiqi Wu; Lu Wang; Hongjun Kang (Journal of Thermal Biology, 2025)

Cumulative inhibitory effect of 6:2 chlorinated polyfluorooctane ether sulfonate in anaerobic digestion processes - Zhou-Yang Li; Min Li; Bin Liu; Xue-Ning Zhang; Shan Yi; Wei-Qin Zhuang; Wen Wang; Yi-Lu Sun; Ai-Jie Wang (Journal of Hazardous Materials, 2025)

Environmental high-risk efflux pumps mediate concurrent enhancement of resistance and virulence in reclaimed water from urban wastewater treatment plants - Shanqi Shen; Zhong He; Siya Zhao; Zezhang Zhu; Xinyi Wang; Yechao Tian; Yuze Han; Min Hu; Chang Lu; Aimin Li (Journal of Hazardous Materials, 2025)

De-aggregation of sonosensitizers enhances bactericidal activity in sonodynamic therapy of deep-seated bacterial osteomyelitis - Gang Zhao; Qiang Yu; Ming Li; Guanghua Lu; Hanqing Li; Li Wei; Jiong Zhang; Shen Wang; Min Lu (Chemical Engineering Journal, 2025)

Predicting wind-driven rain amount on building facade based on machine learning models - Biao Lu; Yunjie Li; Xianqi Huang; Min Jiang; Chi Feng (Building and Environment, 2025)

Identification of gut microbiota causally associated with aging and longevity and mediation roles of the cerebrospinal fluid proteins: proteomic genetic evidence from Mendelian randomization - Ruonan Liu; Zheng Zhu; Yuanyue Zhu; Xin Lin; Hongjie Li; Tiange Wang; Jie Zheng; Mian Li; Zhiyun Zhao; Yu Xu; Jieli Lu; Weiqing Wang; et al. (GeroScience, 2025)

Dietary hydroxymethionine-chelated manganese improved growth and Mn deposition, regulated lipid metabolism and enhanced antioxidant capacity by reducing endoplasmic reticulum stress and autophagy for juvenile Litopenaeus vannamei - Shuqin Li; Hongyu Peng; Min Jin; Lu Zhang; Jinlin Wang; Yu He; Chaokai Huang; Yushan Zou; Xiaoru Chen; Yinzhao Zhang; Feng Tang; Qicun Zhou (Aquaculture, 2025)

Experimental evaluation of the effectiveness of stable isotopic ratios to characterize soil and groundwater evaporation in watersheds - Yundi Hu; Lu Zhao; Zhongfa Zhou; Min Zhao; Qiuwen Zhou; Cheng Zeng; Yuchao Zhang; Zhengzhou Huang; Dengchao Wang; Yueqing Zhang; Hongdai Fan; Hang Li; et al. (Journal of Hydrology, 2025)

Minimizing byproduct formation in bioelectrochemical denitrification with anammox bacteria - Hyejeong Kwon; Bo Li; Min Xu; Qingshi Wang; Tahir Maqbool; Huijie Lu; Mari Winkler; Daqian Jiang (Journal of Hazardous Materials, 2025)

Innovative strategy for dechlorination of halogenated organic Pollutants: Microbial-Derived formate production and Immobilized-PdNP biosynthesis - Yang-Yang Fan; Wen-Wen Liu; Yu-Han Chai; Jing Huang; Min Wang; Xin Wang; Xin-Lu Cai; Li Zhang; Xiang Xiao (International Biodeterioration & Biodegradation, 2025)

Investigating the fine structures of ginkgo starch during kernel development and their correlations with thermal properties - Yan Lu; Lian Zhou; Cai-Yun Zhang; Yan Qi; Xiao-Min Zhang; Zhang Pan; Hong-Jia Zhang; Yu-Ping Ling; Qing Liu; Chang-Quan Zhang; Li Wang (Food Chemistry, 2025)

Characteristics of microbial carbon pump in the sediment of kelp aquaculture zone and its contribution to recalcitrant dissolved organic carbon turnover: insights into metabolic patterns and ecological functions - Jun-Yang Ma; Ji-Hua Liu; Cheng-Zhuang Chen; Yi-Ze Zhang; Zhan-Sheng Guo; Min-Peng Song; Feng Jiang; Zi-Tong Chai; Zhu Li; Su-Xian Lv; Yu-Jiao Zhen; Lu Wang; et al. (Environmental Research, 2025)

Efficient recovery of Zn, Pb and Cu from High–Zinc melts by CO-blowing bath reduction - Xiaobo Min; Xin Wang; Yun Li; Qingyu Huang; Jiawei Lu; Yunyan Wang; Cong Peng; Zongliang Zhang; Yong Ke (Chemical Engineering Journal, 2025)

Autofluorescence cascade nanozyme catalyzes in vivo ROS scavenging for precisive anti-neuroinflammation therapy - Xiyu Du; Gang Zhao; Yifei Fu; Yushan Zhou; Li Yang; Zhaoshun Jiang; Songbin Liu; Xixue Zhang; Kaiqi Zhu; Li Wei; Weidong Gu; Han Lu; et al. (Chemical Engineering Journal, 2025)

Non-negligible emissions of amines from vehicle and ship exhausts in China - Dazhou Li; Xinfeng Wang; Jing Chen; Chunying Lu; Shuwei Dong; Zhiyi Liu; Min Li; Likun Xue; Wenxing Wang (Atmospheric Environment, 2025)

Establishment of a visualization platform for ADR query and analysis: an example of severe skin adverse reactions caused by sulfonylureas - Hui-Min Yu; Ya-Min Huang; Jian Xiao; Lu Zhang; Hang-Xing Huang; Ling Huang; Jing-Yang Li; Xin-qiong Huang (European Journal of Clinical Pharmacology, 2025)

Emissions characteristics of polycyclic aromatic hydrocarbons, water-soluble heavy metals, and oxidative potential from indoor non-energy combustion sources - Si-Min Zhao; Wen-Xin Liu; Qi-Yu Miao; Jia-Min Li; Lu-Min Sun; Shui-Ping Wu (Environmental Science and Pollution Research, 2025)

Genome-wide identification, expression analysis and transcriptional regulation of major histocompatibility complex class I genes in mandarin fish Siniperca chuatsi - Jing Hou; Min Chang Li; Lu Qi; Wei Hao; Lan Hao Liu; Zhen Gan; Bei Huang; Wen Shu Huang; Li Wang; Li Li; Shan Nan Chen; Pin Nie (Aquaculture, 2025)

Microbial volatile organic compounds produced during the anaerobic digestion process can serve as potential indicators of microbial community stability - Dongxue Lu; Min Li; Erqi Nie; Rongbo Guo; Shanfei Fu (Water Research, 2025)

Mushroom biochar-based catalysts for high-efficient activated peroxymonosulfate to degrade ketoprofen in the water - Zhilun Liu; Lei Zhao; Shuang Lu; Xiaohan Hou; Ding Hou; Bo Sun; Min Zhao; Xueyan Li; Jun Ma (Journal of Environmental Chemical Engineering, 2025)

Isolation, identification, and virulence of three strains of Beauveria bassiana from silkworms, Bombyx mori - Qiang Zhang; Wenqing Lai; Qin Li; Xiaoying Zhang; Zhan-peng Lu; Jiawei Jiang; Wenjing Yu; Zuo-min Shao; Xue-yang Wang; Mu-wang Li (Journal of Asia-Pacific Entomology, 2025)

Mechanisms of milk fat globule membranes to alleviate acute colitis and aging by regulating intestinal flora and intestinal barrier - Xiaojun Zhu; Xiaodong Li; Lu Liu; Yongming Zhu; Haowen Ji; Jiaxin Qiu; Min Xu; Jinglong Xu; Wanzhen Bai; Xianlu Zhang (Food Bioscience, 2025)

A simulation-enabled slope digital twin for real-time assessment of rain-induced landslides - Lu-Yu Ju; Te Xiao; Jian He; Wei-Fan Xu; Shi-Hao Xiao; Li-Min Zhang (Engineering Geology, 2025)

Amine-Functionalized SiC nanowires aerogel synchronizes high capacity and ultra-rapid kinetics for CO2 capture - Yanni Ran; Kang Peng; Ziyan Li; Xingwang Guo; Honglin Chen; Shengxuan Cai; Lei Su; Min Niu; De Lu; Hongjie Wang (Chemical Engineering Journal, 2025)

Astronomically forcing hydrological controls on salinity variations during the late Ordovician-early Silurian in the Upper Yangtze area: Responses to the monsoon climate and HICE - Min Xiong; Lei Chen; Chongjie Liao; Xin Chen; Xiucheng Tan; Jian Cao; Shuaicai Wu; Hexing Qin; Zuyou Zhang; Gaoxiang Wang; Dazhong Li; Jiaxun Lu (Chemical Geology, 2025)

Tenecteplase Plus Butyphthalide for Stroke Within 4.5–6 Hours of Onset (EXIT-BT): a Phase 2 Study - Hui-Sheng Chen; Ming-Rui Chen; Yu Cui; Xin-Yu Shen; Hong Zhang; Jiang Lu; Li-Wei Zhao; Ying-Jie Duan; Jing Li; Ya-Mei Wang; Lian-Qiu Min; Li-Hong Zhao; et al. (Translational Stroke Research, 2025)

Design, synthesis, and antifungal activity of novel pyrazole carboxamide derivatives containing benzimidazole moiety as potential SDH inhibitors - Fei Jin; Feng Peng; Xiang-Yi Kong; Wen-Rui Li; Jian-Qi Chai; Min Chen; Ai-Min Lu; Chun-Long Yang; Guo-Hua Li (Molecular Diversity, 2025)

Synaptic-mitochondrial transport: mechanisms in neural adaptation and degeneration - Yang Ding; Huan Yang; Jie Gao; Can Tang; Yu-Yuan Peng; Xin-Mei Ma; Sen Li; Hai-Yan Wang; Xiu-Min Lu; Yong-Tang Wang (Molecular and Cellular Biochemistry, 2025)

Membrane Protein of SARS-CoV-2 Promotes the Production of CXCL10 and Apoptosis of Myocardial Cells - Xiaoguang Wu; Lu Tang; Wen Huang; Min Gao; Changhao Xu; Peng Li; Xiangqing Kong (Cardiovascular Toxicology, 2025)

Overview and Prospect of Data Assimilation in Numerical Weather Prediction - Lili Lei; Fuzhong Weng; Wansuo Duan; Yaodeng Chen; Lin Zhang; Ruichun Wang; Jun Yang; Xiaohao Qin; Wei Han; Jun Li; Jinzhong Min; Zhifang Xu; et al. (Journal of Meteorological Research, 2025)

Record High Temperatures in the Ocean in 2024 - Lijing Cheng; John Abraham; Kevin E. Trenberth; James Reagan; Huai-Min Zhang; Andrea Storto; Karina Von Schuckmann; Yuying Pan; Yujing Zhu; Michael E. Mann; Jiang Zhu; Fan Wang; et al. (Advances in Atmospheric Sciences, 2025)
Heating in the ocean has continued in 2024 in response to increased greenhouse gas concentrations in the atmosphere, despite the transition from an El Niño to neutral conditions. In 2024, both global sea surface temperature (SST) and upper 2000 m ocean heat content (OHC) reached unprecedented highs in the historical record. The 0–2000 m OHC in 2024 exceeded that of 2023 by 16 ± 8 ZJ (1 Zetta Joules = 10 21 Joules, with a 95% confidence interval) (IAP/CAS data), which is confirmed by two other data products: 18 ± 7 ZJ (CIGAR-RT reanalysis data) and 40 ± 31 ZJ (Copernicus Marine data, updated to November 2024). The Indian Ocean, tropical Atlantic, Mediterranean Sea, North Atlantic, North Pacific, and Southern Ocean also experienced record-high OHC values in 2024. The global SST continued its record-high values from 2023 into the first half of 2024, and declined slightly in the second half of 2024, resulting in an annual mean of 0.61°C ± 0.02°C (IAP/CAS data) above the 1981–2010 baseline, slightly higher than the 2023 annual-mean value (by 0.07°C ± 0.02°C for IAP/CAS, 0.05°C ± 0.02°C for NOAA/NCEI, and 0.06°C ± 0.11°C for Copernicus Marine). The record-high values of 2024 SST and OHC continue to indicate unabated trends of global heating.

The underlying mechanism of Porcine Teschovirus 2 3Cpro antagonizing the NLRP3 inflammasome - Xin-yu Zhang; Yu-ying Li; Wei Chen; Yi-min Zhou; Lin Zhou; Lu-lu Xie; Yan-Qing Hu; Hai-xin Huang; Chen-chen Zhao; Yan Qin; Tian Lan; Wen-chao Sun (Veterinary Microbiology, 2025)

Woody plant cell walls: Fundamentals and utilization - Wei Li; Ying-Chung Jimmy Lin; Ying-Lan Chen; Chenguang Zhou; Shuang Li; Nette De Ridder; Dyoni M. Oliveira; Lanjun Zhang; Baocai Zhang; Jack P. Wang; Changzheng Xu; Xiaokang Fu; et al. (Molecular Plant, 2025)

Investigating the co-transport and combined toxicity effect of micro-/nano-plastics and PAHs in ryegrass - Li Lu; Jiawei Zhao; Jiali Shentu; Yuyang Long; Dongsheng Shen; Shengqi Qi; Min Zhu; Cai Hui (Journal of Environmental Management, 2025)

Aroma composition and sensory correlation in Jiaodong shrimp paste: A comparative analysis of solid, liquid, and oil phases - Yang Li; Kuan Lu; Min Wang; Xingyue Wang; Haoen Li; Wancui Xie (Food Research International, 2025)

Advances in valorization of Camellia oleifera Abel. Seed cake: A review on the bioactive components, health benefits, extraction methods, and potential food applications - Nanjie Jiang; Zhenxia Xu; Shuaijun Lu; Xiaoyang Xia; Min Li; YongJun Miao; Xia Xiang (Food Research International, 2025)

Study on the mechanisms of efficient phosphorus recovery by a pilot-scale biofilm sequencing batch reactor under low carbon demand - Yujie Zhang; Xumeng Lu; Shengqi Yu; Huijing Gu; Xiangyu Fei; Tianyu Pan; Lu Li; Yanyan Ding; Min Ni; Yang Pan (Environmental Research, 2025)

Bonding of wood with high strength and excellent water resistant cellulose colloidal adhesives - Yuyan Jiang; Tian Ju; Liangxian Liu; Haiyu Li; Yue Zhang; Na Wang; Zetan Lu; Ming Wei; Dexiu Min; Yanjun Xie; Jian Li; Yonggui Wang; et al. (Chemical Engineering Journal, 2025)

Exploring the role of dipole moment at the upper interface of inverted perovskite solar cells through a bi-molecular host–guest strategy - Guoqiang Xu; Imran Muhammad; Danish Khan; Xiaojian Zheng; Yu Zhang; Min Xin; Huaxi Gao; Jiahao Li; Junyu Wang; Di Lu; Shehzad Ahmed; Peng You; et al. (Chemical Engineering Journal, 2025)

Study on the Storage Characteristics of Sturgeon Protein Prepared by Subcritical Dimethyl Ether Extraction During Cold Storage - Zhengmei Yin; Min Zhang; Kexin Lu; Yifan Wang; Yunye Li; Yiwen Lu; Yejing Sun; Bo Jiang; Yizhou Fang (Journal of Aquatic Food Product Technology, 2025)

Potential role of Mc3r and Mc4r in ovarian metabolism and development in female red crucian carp (Carassius auratus red var.) - Faxian Yu; Lu Huang; Xinxin Yu; Shuxin Zhang; Shengnan Li; Rong Zhou; Wenjing Tao; Lanying Yang; Min Tao; Qizhi Liu; Shaojun Liu (Aquaculture, 2025)

Comammox Nitrospira are the dominant ammonia oxidizers in the Yangtze estuarine biofilms - Xiu-feng Tang; Xing-pan Guo; Lu Kuang; Xin-jie Chen; Nazupar Sidikjan; Ting-ting Xu; Shan Jiang; Min Liu; Li-jun Hou; Yi Yang (Water Research, 2025)

Piperidine and bis-piperidine alkaloids from the peels of Areca catechu and their monoamine oxidases inhibitory activity - Song Wang; De-Zhi Wang; Xia Zhang; Zi-Wei Li; Dong-Hao Lu; Zheng-Jin Jiang; Min Ma; Min Song; Xiao-Qi Zhang (Phytochemistry, 2025)

Enhanced visible-light-driven photocatalytic degradation of tetracycline wastewater using surfactant-modified Au-loaded CeO2 nanorods - Junzi Huang; Mengjie Lu; Min Liu; Yahong Xie; Peng Wei; Huihui Xie; Liang Li; Weitao Han; Zhiwei Zhang; Ying Qi (Journal of Environmental Management, 2025)

Preparation of a La(OH)CO3/NiAl-LDHs interface junction photoinitiated activator: Excellent photoinitiated activity and the photoactive pathway for destruction of phenol in wastewater - Hui-Min Zhao; Wei-Peng Jia; Rui Dang; Xiang-Rong Ma; Yang Ma; Shuang-Yu Li; Xin Han; Nai-Cai Xu; Yu-Hong Kang; Yong Gao; Hua-Rui Hao; Rui Bai; et al. (Journal of Environmental Chemical Engineering, 2025)

Unraveling the interaction of dissolved organic matter and microorganisms with internal phosphorus cycling in the floodplain lake ecosystem - Lan Lu; Ning Tang; Ziqian Zhu; Ronghan Wang; Xiang Gao; Min Yan; Tingting Hu; Han Ma; Guoyu Li; Weixiang Li; Jingyi Zhang; Xiaodong Li; et al. (Environmental Research, 2025)

Wind-generated flow modeling and future circulation prediction of lakes under complex wind field - A case study of Qinghai Lake - Junyang Li; Yuanfu Zhang; Yuxiu Li; Kai Ma; Zhikang Wang; Xiaohan Zhang; Yuchuan Yi; Pengxiang Lu; Zhiqian Gao; Min Wang (Environmental Modelling & Software, 2025)

Screening of Spinal Muscular Atrophy Carriers and Prenatal Diagnosis in Pregnant Women in Yancheng, China - Huilin Sun; Jianli Zheng; Qing’e Zhang; Feifei Ying; Yadong Fu; Yongjuan Guan; Jing Wu; Yueyun Zhou; Jingjing Dong; Mengjun Xu; Fangfang Yang; Ning An; et al. (Biochemical Genetics, 2025)

Botryorhodine J, a new anti-MRSA depsidone isolated from endophytic fungus Alternaria alternata Pas11 - Wen-Yuan Li; Cheng-Cheng Hu; Jin-Hai Liu; Heng-Jie Wang; Ling-Pan Lu; Min Qiao; Ya-Ling Jiang; Rui Wu (Natural Product Research, 2025)

The Arabidopsis heterotrimeric G protein α subunit binds to and inhibits the inward rectifying potassium channel KAT1 - Jiang-Fan Guo; Hui Zhou; Zhuo-Ran Hu; Ya-Lan Yang; Wen-Bin Wang; Yan-Ru Zhang; Xue Li; Nuerkaimaier Mulati; Ying-Xin Li; Lu Wu; Yu Long; Jun-Min He (Plant Science, 2025)

Butyrylated modification of corn starch alleviates autism-like behaviors by modulating 5-hydroxytryptamine metabolism and gut-brain neural activity - Wentian Li; Qingmin Kong; Min Guo; Linlin Wang; Peijun Tian; Jingyu Lu; Jianxin Zhao; Wei Chen; Gang Wang (Carbohydrate Polymers, 2025)

Forest Microclimate as a Driver of Epiphytic Bryophyte Diversity Along a Subtropical Elevational Gradient - Zun Dai; Shi‐chen Xing; S. Robbert Gradstein; Min Li; Shu‐wen Tu; Xing Chen; Xue Yao; Shuang Gao; Rui‐ping Shi; Lu‐yan Tang; Ran Zhang; Zhao‐chen Zhang; et al. (Journal of Biogeography, 2025)
Aim Considering the importance of microclimate in maintaining the diversity of epiphytic bryophytes, we investigated epiphytic bryophytes along an elevational gradient in the subtropical forest of eastern China to unravel the diversity patterns of epiphytic liverworts and mosses along the elevational gradients and the roles of forest microclimates, topographic variables and host plant composition attributes in shaping these elevational diversity patterns. Location Tianmushan National Nature Reserve, Zhejiang, China. Taxon Epiphytic bryophytes. Methods Species diversity patterns of liverworts and mosses were compared based on an inventory of 16 plots along an elevational gradient from 367 to 1470 m. In situ microclimatic data of air temperature and moisture were collected under constant monitoring for over 3 years. Spatial linear models and structural equation models were used to assess the relative roles of the environmental variables in shaping the patterns of species diversity along elevation. Results We found that epiphytic liverwort and moss richness showed different elevational patterns; overall richness patterns of epiphytic bryophytes were largely driven by mosses. Epiphytic mosses exhibited a decline, followed by a hump‐shaped pattern of species richness with increasing elevation, while epiphytic liverworts showed a mid‐elevation plateau with a richness maximum between 800 and 1300 m. Forest microclimate, topography and host plant composition attributes influence epiphytic moss and liverwort patterns differently and interact in a complex way. Overall, species richness of epiphytic liverworts was most strongly affected by microclimate (mean annual air temperature of growing season) and of epiphytic mosses richness by topography (slope). Further, epiphytic liverwort species richness was more influenced by temperature than moisture. Main Conclusions This study highlights the importance of collecting climatic factors at a fine scale (microhabitats) for understanding the patterns and drivers of bryophyte diversity. Further, our findings demonstrate the differences between liverworts and mosses in terms of their response to different environments in the forest ecosystem.

PbSO4 reaction mechanism in oxygen and reduction atmospheres during co-smelting process with primary lead material - Yunyan Wang; Maixin Yu; Yu Liu; Xiaobo Min; Zelong Huang; Cong Peng; Yong Ke; Pingsheng Zeng; Xingwu Lu; Yun Li (Waste Management, 2025)

CMOPEO-OP: Constrained multi-objective population extremal optimization-based optimal planning of standalone microgrids - Guo-Qiang Zeng; Zhen Qin; Kang-Di Lu; Li-Min Li (Swarm and Evolutionary Computation, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Circadian nutrition: is meal timing an elixir for fatigue? - Zhihui Zhang; Lu Yan; Jonas T. Treebak; Min-Dian Li (Science Bulletin, 2025)

Highly efficient Z-scheme CeO2/Bi2MoO6 heterojunction strengthened by redox mediator for photoelectrochemical detection of tetracycline with enhanced sensitivity - Li Li; Yanyu Xie; Chuanfa Luo; Guanwei Pen; Zi Min; Xigen Huang; Rumin Fu; Yansha Gao; Zongde Wang; Limin Lu (Food Chemistry, 2025)

The influence of carbon dioxide on fermentation products, microbial community, and functional gene in food waste fermentation with uncontrol pH - Xin-Rong Pan; Pei-Ken Shang-Guan; Shu-Hui Li; Chu-Hao Zhang; Jia-Min Lou; Liang Guo; Lu Liu; Yin Lu (Environmental Research, 2025)

Impact of different continuous fertilizations on the antibiotic resistome associated with a subtropical triple-cropping system over one decade - Jin Zheng; Ya-Ying Li; Yu-Sheng Lu; Dan Wang; Chong Liu; Huan-Long Peng; Chao-Hong Shi; Kai-Zhi Xie; Kun Zhang; Li-Li Sun; Chang-Min Zhou; Wen-Jie Gu (Environmental Pollution, 2025)

Effect of materials types of water-land junction settings on soil bacterial community structure in Shanghai riverside ecological corridor - Wei Guan; Songshuo Li; Qing Wang; Chenyan Sha; Jinghua Su; Min Wang; Ming Nie; Meng Lu (Ecological Engineering, 2025)

Fluids and fault structures underlying the complex foreshock sequence of the 2021 Mw 6.1 Yangbi earthquake - Min Liu; Yen Joe Tan; Hao Guo; Hongyi Li; Renqi Lu; Jinzhong Jiang (Earth and Planetary Science Letters, 2025)

Multifunctional MnO2 nanosheet based DNA tetrahedron- photosensitizer nanoplatform for gene-photodynamic modulation - Yanlin Zheng; Fei Li; Xiaohui Zhu; Min Wang; Yuantao Wen; Tao Zeng; Wukun Zhong; Chao Xing; Chunhua Lu (Chemical Engineering Journal, 2025)

Glycogen-accumulating organisms promote phosphate recovery from wastewater by pilot-scale biofilm sequencing batch reactor: Performance and mechanism - Min Ni; Yang Pan; Jiahui Gong; Zhiqiang Chen; Dapeng Li; Yong Huang; Lu Li; Yanyan Ding; Zhen Bi (Bioresource Technology, 2025)

Tree root-mediated soil metabolome in agroforestry enhancing the growth and quality of Panax notoginseng - Cuiying Wang; Guomin Mao; Yingbin Li; Wenjing Zi; Qingying Wang; Huichuan Huang; Min Yang; Fei Du; Xinyue Mei; Weiping Deng; Jian Lu; Shusheng Zhu; et al. (Plant and Soil, 2025)
Purpose The ecological cultivation of Panax notoginseng under a forest canopy relies on the coupling of the P. notoginseng growth environment and the forest ecosystem Methods In this study, six tree species, such as Platycladus orientalis (L.) Franco, were chosen to research the effects of species interactions on the growth, quality, and disease occurrence under intercropping with P. notoginseng , with single P. notoginseng serving as the control. Results Intercropping P. notoginseng with PO ( Platycladus orientalis , a coniferous tree species) or with SW ( Schima wallichii Choisy, a broad-leaved tree species) promoted the accumulation of P. notoginseng biomass, reduced the occurrence of root rot, improved the contents of nitrogen, phosphorus and potassium in P. notoginseng , and increased the saponin concentration. Then, 43 differentially abundant metabolites were screened in the P. notoginseng -tree intercropping system by soil metabolism analysis and compared with those in the monocropped system. Indole-3-carboxaldehyde showed a significant negative relationship with the occurrence of root rot disease and inhibited Fusarium oxysporum . In addition, 2-naphthalenesulfonic acid was significantly positively correlated with biomass and increased the dry weight in the underground part of P. notoginseng in the pot experiments. Conclusions Thus, the coniferous tree species PO and the broad-leaved tree species SW are potentially good neighbours of P. notoginseng , and soil metabolic changes may be important mechanisms for the growth and disease resistance benefits observed in the understorey of P. notoginseng .

Combining resistance indicators, metabolomes and transcriptomes to reveal correlations in disease and cold resistance in tea plant and analyze the key domain NB-ARC - Min Li; Wenting Wang; Xiaodan Chen; Xiumei Lu; Yahui Huang (Plant Cell Reports, 2025)

Design, synthesis and herbicidal activity of novel cyclohexanedione derivations containing pyrazole and pyridine groups as potential HPPD inhibitors - Shuai-Tao Hou; Ling Han; Wen-Rui Li; Guang-Yu Dai; Yu Liu; Ai-Min Lu; Chun-Long Yang; Min Chen (Molecular Diversity, 2025)

H-NS represses fliD transcription for lateral flagellar filament cap in Vibrio parahaemolyticus - Kui Liu; Min Chen; Jingyang Chang; Jing Yang; Daqing Wang; Xuefeng Ding; Ming Yang; Yiquan Zhang; Renfei Lu; Li Chen (Archives of Microbiology, 2025)

The role of microorganisms in phosphorus cycling at river-lake confluences: Insights from a study on microbial community dynamics - Jie Liang; Min Yan; Ziqian Zhu; Lan Lu; Junjie Ding; Qinxue Zhou; Xiang Gao; Ning Tang; Shuai Li; Xiaodong Li; Guangming Zeng (Water Research, 2025)

Corrigendum to “Vimentin rearrangement by phosphorylation is beneficial for porcine reproductive and respiratory syndrome virus replication in vitro” [Vet. Microbiol. 259 (2021) 109133] - Xin-xian Zheng; Rui Li; Songlin Qiao; Xin-xin Chen; Longxiang Zhang; Qingxia Lu; Guangxu Xing; En-min Zhou; Gaiping Zhang (Veterinary Microbiology, 2025)

Occurrence characteristics and factors that influence shale oil in the Jurassic Lianggaoshan Formation, northeastern Sichuan Basin - Xuefeng Bai; Xin Wang; Min Wang; Junhui Li; Shuangfang Lu; Xinyi Yang; Yidong Jia; Rong Wu; Tianyi Li; Youzhi Wang (Marine and Petroleum Geology, 2025)

Corrigendum to “Cobalt induces neurodegenerative damages through Pin1 inactivation in mice and human neuroglioma cells” [J Hazard Mater 419 (2021) 126378] - Fuli Zheng; Yuqing Li; Fengshun Zhang; Yi Sun; Chunyan Zheng; Zhousong Luo; Yuan-Liang Wang; Michael Aschner; Hong Zheng; Liqiong Lin; Ping Cai; Wenya Shao; et al. (Journal of Hazardous Materials, 2025)

Comparative effects of chemical dispersants and rhamnolipid biosurfactants on oil biodegradation and microbial community in coastal sediments - Linjie Deng; Chao Peng; Shun Li; Ruiyu Yang; Chenyao Yan; Min Li; Lu Lu (International Biodeterioration & Biodegradation, 2025)

Structural characterization and proteomic profiling of oviposition secretions across three rice planthopper species - Jia-Bao Lu; Peng-Peng Ren; Ying Tian; Yan-Yan Yang; Qing-Kai Feng; Xiao-Ya Zhang; Fang He; Hai-Jian Huang; Jian-Ping Chen; Jun-Min Li; Chuan-Xi Zhang (Insect Biochemistry and Molecular Biology, 2025)

Comprehensive understanding of impacts of steam explosion on facilitated extraction and transformation of flavonoids from Astragali Radix - Xueyan Fan; Youla Su; Yue Wu; Min Li; Yan Lu; Huiting Xue; Guanhua Li (Food Chemistry, 2025)

Enhancing freeze-thaw stability of frozen dough with deacetylated konjac glucomannan: The role of degree of deacetylation - Jianwei Fan; Zhaojun Chen; Haoyuan Wang; Zhilong Zeng; Min Zhou; Manman Lu; Yao Li; Xiaoli Qin; Xiong Liu (Food Hydrocolloids, 2025)

Phthalate exposures, blood coagulation function, and assisted reproductive technology outcomes: Results from the TREE cohort study - Chong Liu; Chang-Jiang Liu; Wen-Qu Tian; Wen Yao; Yu Miao; Min Zhang; Xiao-Qiong Yuan; Yan-Ling Deng; Wen-Qing Lu; Yu-Feng Li; Qiang Zeng (Environmental Research, 2025)

Reverse osmosis process combining energy consumption analysis and mass transfer in the concentration of lithium-enriched brine - Zhilu Li; Youjing Zhao; Yan Li; Jianjiang Lu; Min Wang (Desalination, 2025)

Insights into the role of attapulgite clay on the efficient removal of microplastics by sand filters in various waters - Jizhe Lu; Shuo Sun; Xiaolong Jiang; Dongfang Wang; Yanan Liu; Quanyuan Chen; Hyunjung Kim; Xiaopeng Min; Li Cai (Chemical Engineering Journal, 2025)

A tetrahedral DNA nanoplatform with ultrasound-triggered biomimetic nanocarriers for targeted siMCM2 delivery and reversal of imatinib resistance in gastrointestinal stromal tumors - Li Han; Quan Dai; Chuanshi He; Jinshun Xu; Likun Cui; Xiaoxiao Xie; Zijian Zhang; Min Zhuang; Xiangyu Li; Man Lu (Chemical Engineering Journal, 2025)

Ordered self-assembled monolayer improved the buried interface of wide bandgap perovskite for efficient and stable semi-transparent solar cells - Peiran Hou; Shenghan Hu; Yuxi Zhang; Junye Pan; Min Hu; Jiahui Chen; Bingxin Duan; Li Wan; Pin Lv; Yanqing Zhu; Shengqiang Xiao; Yi-Bing Cheng; et al. (Chemical Engineering Journal, 2025)

Metagenomic sequencing reveals the mechanism for inhibiting N2O production in PN systems with long-term exposure to PPCPs - Yuren Wang; Lu Li; Yikun Hu; Min Deng; Kang Song (Chemical Engineering Journal, 2025)

A chitosan/gelatin/aldehyde hyaluronic acid hydrogel coating releasing calcium ions and vancomycin in pH response to prevent the formation of bacterial biofilm - Yuange Li; Hong Sung Min; Chen Chen; Haojie Shan; Yiwei Lin; Fuli Yin; Yixian Chen; Liheng Lu; Xiaowei Yu (Carbohydrate Polymers, 2025)

Navβ2 Intracellular Fragments Contribute to Aβ1-42-Induced Cognitive Impairment and Synaptic Deficit Through Transcriptional Suppression of BDNF - Min-Nan Lu; Dan Wang; Chen-Jun Ye; Guo-Ji Yan; Jing-Feng Song; Xin-Ying Shi; Shan-Shan Li; Li-Na Liu; Hui-Xiang Zhang; Xiao-Han Dong; Tao Hu; Xu-Yang Wang; et al. (Molecular Neurobiology, 2025)

Intermittent fasting shifts the diurnal transcriptome atlas of transcription factors - Min Fu; Siyu Lu; Lijun Gong; Yiming Zhou; Fang Wei; Zhigui Duan; Rong Xiang; Frank J. Gonzalez; Guolin Li (Molecular and Cellular Biochemistry, 2025)

Electrochemistry–glucosemeter–smartphone integrated multi-mode biosensor for accurate detection of aflatoxin B1 - Zhiguang Suo; Tao Lu; Jiahui Liu; Jiayi Li; Li Wang; Yong Liu; Min Wei (Analytica Chimica Acta, 2025)

Potassium status and the risk of type 2 diabetes, cardiovascular diseases, and mortality: a meta-analysis of prospective observational studies - Yahui Fan; Min Wu; Lu Ding; Huixin Ji; Jinping Zhao; Xiaohui Li; Zhaofang Li; Sijiao Liu; Hong Jiang; Jia Shi; Haoyuan Lei; Mingxu Wang; et al. (Critical Reviews in Food Science and Nutrition, 2024)

Pollution status and assessment of seven heavy metals in the seawater and sediments of Hangzhou Bay, China - Rong Zhu; Yan-Yan Zeng; Li-Min Liu; Lu Yin; Kai-Ping Xu; Wei-Feng Chen; Shang-Chun Li; Xiao-Feng Zhou (Marine Pollution Bulletin, 2024)

Inhibition of ATP1V6G3 prompts hepatic stellate cell senescence with reducing ECM by activating Notch1 pathway to alleviate hepatic fibrosis - Xiao-Pei Xue; Yu Sheng; Qi-Qi Ren; Shi-Meng Xu; Min Li; Zhao-Xiu Liu; Cui-Hua Lu (Tissue and Cell, 2024)

MAT2A is essential for zygotic genome activation by maintaining of histone methylation in porcine embryos - Xiao-Han Li; Song-Hee Lee; Qin-Yue Lu; Cheng-Lin Zhan; Gyu-Hyun Lee; Ji-Dam Kim; Jae-Min Sim; Hyeon-Ji Song; Xiang-Shun Cui (Theriogenology, 2024)

Terrestrial dissolved organic matter inputs affect the nitrous oxide emission revealed by FT-ICR MS - Zezheng Wang; Lu Li; Chengchao Liao; Min Deng; Xiaoyan Jiang; Yongxia Huang; Zhiwei Xia; Kang Song (Science of The Total Environment, 2024)

Predicting bioavailable barium transfer in soil-bok choy systems: A study induced by shale gas extraction in Chongqing, China - Yan Li; Xiaoyu Wang; Weihan Yu; Xingmin Cen; Yutong Li; Xin Zhang; Min Xu; Daijun Zhang; Peili Lu; Hongcheng Bai (Science of The Total Environment, 2024)

Seasonal urban surface thermal environment analysis based on local climate zones: A case study of Chongqing - Rongxiang Wang; Tao Lu; Bo He; Fang Wang; Qiao Huang; Zihua Qian; Jie Min; Yuechen Li (Science of The Total Environment, 2024)

Synergistic singlet oxygen and UV irradiation for efficient intracellular ARGs removal via peroxymonosulfate/catalytic membrane-UV system - Xuan Hou; Yunxin Zhang; Min Wang; Jiajun Lu; Defang Ma; Qian Li; Ling Li; Zhining Wang; Baoyu Gao; Yan Wang (Journal of Hazardous Materials, 2024)

Antibiotic resistance at environmental multi-media interfaces through integrated genotype and phenotype analysis - Chen-Xi Fu; Chen Chen; Qian Xiang; Yi-Fei Wang; Lu Wang; Feng-Yuan Qi; Dong Zhu; Hong-Zhe Li; Li Cui; Wei-Li Hong; Matthias C. Rillig; Yong-Guan Zhu; et al. (Journal of Hazardous Materials, 2024)

The synchronized dynamic release behavior of microplastics during farmland soil erosion process - Ying Hu; Jia Jia; Fanping Zhou; Dongsheng Shen; Jiali Shentu; Li Lu; Shengqi Qi; Min Zhu; Yuyang Long (Journal of Environmental Management, 2024)

Structural properties and antioxidant capacity of different aminated starch-phenolic acid conjugates - Feng-Kun An; Meng-Yun Li; Hai-Lu Luo; Xing-Long Liu; Zhen Fu; Min-Hong Ren (Food Chemistry, 2024)

Enhancement of flavor quality in oyster hydrolysate through fermentation with oyster-derived lactic acid bacteria - Xiangzhi Lu; Min Shi; Li Liu; Zefan Chen; Xinxing Xu; Guangxin Feng; Mingyong Zeng (Food Bioscience, 2024)

Antihypertensive mechanism of the medicine food homology compound solution with high ACE inhibition rate based on network pharmacology and molecular docking - Min Xu; Ruiqi Ren; Zhixing Zhang; Xiaodong Li; Lu Liu; Hongyu Liu; Yu Xia; Md Masumuzzaman (Food Bioscience, 2024)

Multifunctional property of N,N-bis (carboxymethyl) glutamic acid modified biomass material: adsorption and degradation removals of cationic dyes in wastewater - Min He; Lang Zhao; Hongbin Hu; Lu Yao; Yinghuai Guo; Chunjiang Hou; Shaokun Gao; Rong Li (Environmental Research, 2024)

Concurrent removal of Fe(II), Cu(II), and Zn(II) cations from acid mine drainage by an industrial solid waste - Steel slag: Behaviors and mechanisms - Mingyuan Yang; Cunfang Lu; Shuo Zhang; Yelei Wang; Rui Xu; Min Zhang; Juan Wen; Zilong Li (Environmental Research, 2024)

Endogenous silicon-activated rice husk biochar prepared for the remediation of cadmium-contaminated soils: Performance and mechanism - Tao Lu; Wenzhan Ge; Anyu Li; Shengjun Deng; Tao Min; Guohong Qiu (Environmental Pollution, 2024)

Vermiculite-derived MgFe nanosheet-enhanced hydrogel with dual photothermal and photocatalytic Fenton functions for solar water purification - Yi Lu; Zongze Li; Jiawei Liang; Xueling Xu; Guangyao Zhang; Huihua Min (Desalination, 2024)

Cellulose aerogel evaporators with vertical channels inspired by lotus rods for highly efficient solar water evaporation - Zihui Wang; Fanyue Meng; Xinjuan Liu; Zhiwei Gong; Yuquan Li; Ting Lu; Yefeng Yao; Min Xu; Likun Pan (Desalination, 2024)

Heteroatom-regulated iron single-atom nanozymes for universal colorimetric discrimination of mycotoxins and metal ions - Zhiwei Shen; Peijie Wang; Xiang Li; Min Zhang; Xuerong Shi; Na Lu (Chemical Engineering Journal, 2024)

CMPK2 Promotes CD4+ T Cell Activation and Apoptosis through Modulation of Mitochondrial Dysfunction in Systemic Lupus Erythematosus - Ya-Nan Tan; Ge-Ge Jiang; Xiang-Wen Meng; Zhi-Yuan Lu; Yan-Ma; Jin Li; Nan-Xiang; Xiao-Ge Sun; Qian Wang; Xue Wang; Xiao-Yi Jia; Min Zhang (Cell Biochemistry and Biophysics, 2024)

Trophic homogeneity due to seasonal variation in nitrogen in shallow subtropical lakes - Yun Li; Min Zhang; Xia Liu; Lu Zhang; Feizhou Chen (Water Research, 2024)

Rapid and extensive SARS-CoV-2 Omicron variant infection wave revealed by wastewater surveillance in Shenzhen following the lifting of a strict COVID-19 strategy - Yinghui Li; Chen Du; Ziquan Lv; Fuxiang Wang; Liping Zhou; Yuejing Peng; Wending Li; Yulin Fu; Jiangteng Song; Chunyan Jia; Xin Zhang; Mujun Liu; et al. (Science of The Total Environment, 2024)

PbSO4 decomposition kinetic and phase transformation mechanism during lead waste recycling - Yun Li; Yu Liu; Liyuan Chai; Xin Wang; Dezhou Zhang; Yongming Chen; Yunyan Wang; Shenghai Yang; Yong Ke; Cong Peng; Pingsheng Zeng; Xingwu Lu; et al. (Process Safety and Environmental Protection, 2024)

Identification and performance of endophytic actinobacteria Ahn65 with functions of growth promotion and disease resistance for rice - Hua Yang; Zhan Hu; Rong Xiao; Zhu-dong Liu; Min Zhang; Yi-Lu Li; Shan-dong Wu; Zu-jiao Fu (Physiological and Molecular Plant Pathology, 2024)

Development of the compound intensity measure and seismic performance assessment for aqueduct structures considering fluid-structure interaction - Min Du; Sherong Zhang; Chao Wang; Ze Li; Ji Yao; Tong Lu (Ocean Engineering, 2024)

Enlarging effects of microplastics on adsorption, desorption and bioaccessibility of chlorinated organophosphorus flame retardants in landfill soil particle-size fractions - Yujie Xuan; Dongsheng Shen; Yuyang Long; Jiali Shentu; Li Lu; Min Zhu (Journal of Hazardous Materials, 2024)

Evaluating the role of high N2O affinity complete denitrifiers and non-denitrifying N2O reducing bacteria in reducing N2O emissions in river - Senbati Yeerken; Min Deng; Lu Li; Co Thi Kinh; Zezheng Wang; Yongxia Huang; Yanlin Xiao; Kang Song (Journal of Hazardous Materials, 2024)

Unraveling the impact of perfluorooctanoic acid on sulfur-based autotrophic denitrification process - Hong-Xu Bao; Zhou-Yang Li; Chen Chen; Min Li; Xue-Ning Zhang; Kang Song; Yi-Lu Sun; Ai-Jie Wang (Journal of Hazardous Materials, 2024)

Study of ship-based carbon capture optimization considering multiple evaluation factors and main engine loads - Zhonghao Wang; Mingjian Lu; Shengjie Dong; Min Tang; Xinping Yan; Ke Li; Haoran Yang (Journal of Cleaner Production, 2024)

Experimental study on the influence of rock pore structure on pressure stimulated voltage variations based on nuclear magnetic resonance - Shan He; Min Li; Shiliang Shi; Yi Lu; Deming Wang (Engineering Geology, 2024)

High-performance circularly polarized electroluminescence UV-OLED based on hot exciton molecules with preferred horizontal dipole orientation - Sinuo Geng; Min Wang; Huihui Li; Hua Lu; Zujin Zhao; Xin Jiang Feng (Chemical Engineering Journal, 2024)

Formation mechanism of high biofilm phosphorus storage capacity and its effect on phosphorus uptake-release and carbon source consumption - Xiaoya Wang; Jun Zhang; Lu Li; Ye Zhu; Yue Zhang; Min Ni; Yanyan Ding; Yong Huang; Yang Pan (Bioresource Technology, 2024)

Genome-wide identification of Aux/IAA gene family members in grape and functional analysis of VaIAA3 in response to cold stress - Shixiong Lu; Min Li; Yongjuan Cheng; Huimin Gou; Lili Che; Guoping Liang; Juan Mao (Plant Cell Reports, 2024)

Estimation of Regional Evapotranspiration Based on the Decouple Model and Remote Sensing Information ——a Case Study in Beijing City and Nearby Region - Su-Chuang Di; Zhao-Liang Li; Yanmin Ren; Meng Liu; Ya-Zhen Jiang; Fan-Dong Zheng; Xue-Min Li; Yan-Bing Qi; Hong-Lu Liu; Ronglin Tang (International Journal of Remote Sensing, 2024)

Particle-ozone complex pollution under diverse synoptic weather patterns in the Yangtze River Delta region: Synergistic relationships and the effects of meteorology and chemical compositions - Yangzhihao Zhan; Min Xie; Bingliang Zhuang; Da Gao; Kuanguang Zhu; Hua Lu; Tijian Wang; Shu Li; Mengmeng Li; Yi Luo; Runqi Zhao (Science of The Total Environment, 2024)

In situ surface-enhanced Raman spectroscopy for the detection of nanoplastics: A novel approach inspired by the aging of nanoplastics - Xiaoxin Huang; Jinchan Huang; Meilin Lu; Yu Liu; Guangzheng Jiang; Min Chang; Wenhui Xu; Zhenqing Dai; Chunxia Zhou; Pengzhi Hong; Chengyong Li (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

“Development of the compound intensity measure and seismic performance assessment for aqueduct structures considering fluid-structure interaction” [Ocean Eng. 11 1 (2024) 118838] - Min Du; Sherong Zhang; Chao Wang; Ze Li; Ji Yao; Tong Lu (Ocean Engineering, 2024)

RAD-seq data for Engelhardia roxburghiana provide insights into the palaeogeography of Hainan Island and its relationship to mainland China since the late Eocene - Pei-Han Huang; Tian-Rui Wang; Min Li; Zi-Jia Lu; Ren-Ping Su; Ou-Yan Fang; Lang Li; Shi-Shun Zhou; Yun-Hong Tan; Hong-Hu Meng; Yi-Gang Song; Jie Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Multi-scale matching and simulating flows of ecosystem service supply and demand in the Wuhan metropolitan area, China - Ying Chen; Yina Lu; Ruolin Meng; Suran Li; Linzi Zheng; Min Song (Journal of Cleaner Production, 2024)

Perfluorooctanoic acid effect and microbial mechanism to methane production in anaerobic digestion - Lu Li; Wenkai Li; Yunpeng Xue; Zezheng Wang; Yuren Wang; Renhui Li; Min Deng; Yifeng Xu; Lai Peng; Kang Song (Journal of Environmental Management, 2024)

Facile preparation of hollow covalent organic frameworks as superior and universal matrix clean-up micro-structures for high throughout determination of food hazards - Tong Zhai; Dan Qiao; Jing Wang; Chun-Yang Li; Lu Yang; Jin Wang; Jing Wu; Qisijing Liu; Jing-Min Liu; Shuo Wang (Food Chemistry, 2024)

Dose-dependent effects of polystyrene nanoplastics on growth, photosynthesis, and astaxanthin synthesis in Haematococcus pluvialis - Yingying Zhang; Jian Ju; Min Li; Zhuyi Ma; Wenyan Lu; Hui Yang (Environmental Pollution, 2024)

Digital twin-based virtual modeling of the Poyang Lake wetland landscapes - Hao Chen; Xin Xiao; Chao Chen; Min Chen; Chaoyang Li; Kai Lu; Hui Lin; Chaoyang Fang (Environmental Modelling & Software, 2024)

Efficient and low-cost Ni-NiO/Al2O3 catalysts with dual-active-sites for selective catalytic conversion of phthalic anhydride to phthalide - Liang-Liang Zhang; Xiao-Min Duan; Kai-Xuan Yang; Yu-Bo Xu; Jia-Ping Lu; Wan-Xi Li; Bo-Qiong Li; Cai-Long Xue; Ya-Jie Liu (Chemical Engineering Journal, 2024)

Excellent electrocaloric performance achieved by the high-entropy strategy - Xiaofan Sun; Cuiping Xu; Yanzhou Lu; Min Zhao; Shulin Jiao; Zheng Tang; Dong Li; Hong-Ling Cai; X.S. Wu (Chemical Engineering Journal, 2024)

Dietary vitamin B6 could improve the utilization of high carbohydrate diet by promoting carbohydrate degradation and lipid synthesis in Pacific white shrimp (Litopenaeus vannamei) - Xinyue Tao; Tingting Zhu; Ming Li; Jingling Lu; Min Jin; Weijian Liu; Qicun Zhou (Animal Feed Science and Technology, 2024)

Targeting HSP90 in Gynecologic Cancer: Molecular Mechanisms and Therapeutic Approaches - Lu Min; Xuewei Li; Lily Liang; Zheng Ruan; Shaohui Yu (Cell Biochemistry and Biophysics, 2024)

A novel iron oxide (Fe3O4)-laden titanium carbide (Ti3C2) MXene stacks for the efficient removal of tetracycline from aqueous solution - Xinyu Hu; Guizhen Li; Yao Zhang; Mingrong Lu; Wei Pu; Yansu Dai; Min Yang; Hongbin Wang (Chemosphere, 2024)

Characteristics and release potential of microplastics in municipal solid waste incineration bottom ash - Liwei Luo; Shuli Guo; Dongsheng Shen; Jiali Shentu; Li Lu; Shengqi Qi; Min Zhu; Yuyang Long (Chemosphere, 2024)

Faecal contamination in China: Trends, sources, and driving mechanisms - Xiaoshu Hou; Lu Qin; Fangli Wang; Min Xu; Chunxue Yu; Yali Zhang; Tao Zhang; Bo Wu; Dong Wang; Miao Li (Water Research, 2024)

Evaluation of the collapse susceptibility of loess using machine learning - Qing-yi Mu; Tian-qi Song; Zhao Lu; Te Xiao; Li-min Zhang (Transportation Geotechnics, 2024)

Ozone sensitivity regimes vary at different heights in the planetary boundary layer - Xin Li; Wenjie Wang; Suding Yang; Yafang Cheng; Limin Zeng; Xuena Yu; Sihua Lu; Ying Liu; Min Hu; Shaodong Xie; Xiaofeng Huang; Jun Zhou; et al. (Science of The Total Environment, 2024)

Rac1 promotes the lipopolysaccharide-induced inflammatory response and contraction-associated proteins (CAPs) expression in mouse uterine smooth muscle cells - Min Diao; Yunkai Tao; Qian Liu; Lu Huang; Hao Li; Xuemei Lin (Reproductive Biology, 2024)

Expression analysis of pathogenesis-related protein genes revealed the key RrPRs involved in SA- and MeJA-mediated top-rot disease resistance in Rosa roxburghii fruit - Qi Wang; Mingui Li; Min Lu; Xiaomao Wu; Huaming An (Physiological and Molecular Plant Pathology, 2024)

Nano- and microplastics drive the dynamic equilibrium of amoeba-associated bacteria and antibiotic resistance genes - Min Zhou; Lu Ma; Zihe Wang; Shicheng Li; Yijun Cai; Meicheng Li; Lin Zhang; Cheng Wang; Bo Wu; Qingyun Yan; Zhili He; Longfei Shu (Journal of Hazardous Materials, 2024)

Fusion and integrated interpretation of multisource geoscience datasets for mineral exploration - Min Ma; Wenhui Zhou; Liancun Xiu; Xinqian Wang; Yongchun Li; Weixing Li; Junjie Yun; Zhen Lu (Journal of Applied Geophysics, 2024)

Hydrogeochemistry of geothermal water in Huangshadong and adjacent areas of Guangdong province: Implications for water-rock interaction - Lu Liu; Guiling Wang; Yalu Li; Zhengan Wei; Wenjing Lin; Xianan Qin; Min Zhang; Shihua Qi; Xiting Long (Geothermics, 2024)

Water flush boosts performance of elemental sulfur-based denitrification packed-bed systems: Optimization and mechanisms - Jia-Min Xu; Heng Dong; Hao-Ran Xu; Yi-Lu Sun; Yang Yu; Li-Ying Zhang; Gen-Ping Yi; Wen-Ke He; Chang-Min Wu; Ai-Jie Wang; Hao-Yi Cheng (Bioresource Technology, 2024)

Research advances in the function and anti-aging effects of nicotinamide mononucleotide - Min Wang; Yuan Cao; Yun Li; Lu Wang; Yuyan Liu; Zihui Deng; Lianrong Zhu; Hongjun Kang (Journal of Zhejiang University-SCIENCE B, 2024)
Aging and age-related ailments have emerged as critical challenges and great burdens within the global contemporary society. Addressing these concerns is an imperative task, with the aims of postponing the aging process and finding effective treatments for age-related degenerative diseases. Recent investigations have highlighted the significant roles of nicotinamide adenine dinucleotide (NAD + ) in the realm of anti-aging. It has been empirically evidenced that supplementation with nicotinamide mononucleotide (NMN) can elevate NAD + levels in the body, thereby ameliorating certain age-related degenerative diseases. The principal anti-aging mechanisms of NMN essentially lie in its impact on cellular energy metabolism, inhibition of cell apoptosis, modulation of immune function, and preservation of genomic stability, which collectively contribute to the deferral of the aging process. This paper critically reviews and evaluates existing research on the anti-aging mechanisms of NMN, elucidates the inherent limitations of current research, and proposes novel avenues for anti-aging investigations.

MLKL deficiency alleviates acute alcoholic liver injury via inhibition of NLRP3 inflammasome - Yue Shen; Dongliang Chen; Min Linghu; Bo Huang; Shangfu Xu; Lisheng Li; Yuanfu Lu; Xia Li (Toxicology, 2024)

Enhancing phosphorus uptake in biofilms by dissolved oxygen: Mechanistic insights from cellular and EPS perspectives - Bo Huang; Jihui Huang; Xiaoya Wang; Yue Chen; Min Ni; Yanyan Ding; Yong Huang; Lu Li; Yang Pan (Journal of Water Process Engineering, 2024)

Zero-valent iron-loaded Ti3C2-MXene activated by persulfate for the degradation of tetracycline hydrochloride: Efficiency and mechanism - Hongyang Zheng; Yao Zhang; Mingrong Lu; Honglin Xie; Junxiu Ye; Hongbin Wang; Min Yang; Guizhen Li (Journal of Environmental Chemical Engineering, 2024)

A yarn-based sweat-activated battery constructed with conjugated electrospun nanofiber separators as a durable and high-capacity power source in textile electronics - Yanling Zheng; Huijun Sun; Yanjun Cheng; Wenhu Gao; Chenyu Wang; Jun Ju; Min Li; Xuemei Xiang; Wei Sun; Wei Wang; Zhisong Lu; Yan Qiao (Chemical Engineering Journal, 2024)

Multidimensional combinatorial screening for high-level production of erythritol in Yarrowia lipolytica - Lei Li; Qianqian Zhang; Ruirui Shi; Mingdong Yao; Kangming Tian; Fuping Lu; Hui-Min Qin (Bioresource Technology, 2024)

Exploration of Positive and Negative Schizophrenia Symptom Heterogeneity and Establishment of Symptom-Related miRNA-mRNA Regulatory Network: Based on Transcriptome Sequencing Data - Mengdi Jin; Mengtong Xie; Lin Dong; Fengyu Xue; Weizhen Li; Lintong Jiang; Junnan Li; Min Zhang; Haideng Song; Qingxing Lu; Qiong Yu (Molecular Neurobiology, 2024)

Genetic analysis of inflorescence length in Solanum pimpinellifolium - Junling Hu; Xin Li; Hui Zhang; Xiaoxiao Lu; Feng Pan; Chunyang Pan; Wenyue Su; Min Zhang; Maomao Xu; Chen Zhang; Lianfeng Shi; Yanmei Guo; et al. (Genetic Resources and Crop Evolution, 2024)

Correction to: Association of sudden sensorineural hearing loss with meteorological factors: a time series study in Hefei, China, and a literature review - Xiao‑Bo Li; Yan‑Xun Han; Zi‑Yue Fu; Yu‑Chen Zhang; Min Fan; Shu‑Jia Sang; Xi‑Xi Chen; Bing‑Yu Liang; Yu‑Chen Liu; Peng‑Cheng Lu; Hua‑Wei Li; Hai‑Feng Pan; et al. (Environmental Science and Pollution Research, 2024)

Revealing core functional microorganisms in the fermentation process of Qicaipaojiao (Capsicum annuum L.) based on microbial metabolic network - Ju Chen; Yubing Huang; Xueya Wang; Jianwen He; Wenxin Li; Min Lu; Xiaojing Sun; Yong Yin (Food Research International, 2024)

Ultra-trace Ag doped carbon quantum dots with peroxidase-like activity for the colorimetric detection of glucose - Wei Tan; Guixiang Yao; Hang Yu; Yanzhi He; Mingrong Lu; Tianru Zou; Xiaopei Li; Pengyuan Yin; Pei Na; Wenrong Yang; Min Yang; Hongbin Wang (Food Chemistry, 2024)

Effect of sheep bone protein hydrolysate on promoting calcium absorption and enhancing bone quality in low-calcium diet fed rats - Guanhua Hu; Xueying Sun; Shiqi Hao; Xiaotong Li; Min Qian; Lu Dou; Min Zhang; Puxin Hou; Lin Su; Lihua Zhao; Lina Sun; Ye Jin (Food Chemistry, 2024)

Dietary cholesterol intervention could alleviate the intestinal injury of Oreochromis niloticus induced by plant-based diet via the intestinal barriers - Jiayuan Jiang; Xing Lu; Li-Xue Dong; Di Peng; Jian-Min Zhang; Juan Tian; Hua Wen; Ming Jiang (Fish & Shellfish Immunology, 2024)

Association of sudden sensorineural hearing loss with meteorological factors: a time series study in Hefei, China, and a literature review - Xiao-Bo Li; Yan-Xun Han; Zi-Yue Fu; Yu-Chen Zhang; Min Fan; Shu-Jia Sang; Xi-Xi Chen; Bing-Yu Liang; Yu-Chen Liu; Peng-Cheng Lu; Hua-Wei Li; Hai-Feng Pan; et al. (Environmental Science and Pollution Research, 2024)
Air pollution can cause disease and has become a major global environmental problem. It is currently believed that air pollution may be related to the progression of SSNHL. As a rapidly developing city in recent years, Hefei has serious air pollution. In order to explore the correlation between meteorological variables and SSNHL admissions, we conducted this study. This study investigated the short-term associations between SSNHL patients admitted to the hospital and Hefei climatic variables. The daily data on SSNHL-related hospital admissions and meteorological variables containing mean temperature (T-mean; °C), diurnal temperature range (DTR; °C), atmospheric pressure (AP; Hp), and relative humidity (RH; %), from 2014 to 2021 (2558 days), were collected. A time-series analysis integrating distributed lag non-linear models and generalized linear models was used. PubMed, Embase, Cochrane Library, and Web of Science databases were searched. Literature published up to August 2023 was reviewed to explore the potential impact mechanisms of meteorological factors on SSNHL. The mechanisms were determined in detail, focusing on wind speed, air pressure, temperature, humidity, and air pollutants. Using a median of 50.00% as a baseline, the effect of exceedingly low T-mean in the single-day hysteresis effect model began at a lag of 8 days (RR = 1.032, 95% CI: 1.001 ~ 1.064). High DTR affected the admission rate for SSNHL on lag 0 day. The significance of the effect was the greatest on that day (RR = 1.054, 95% CI: 1.007 ~ 1.104) and then gradually decreased. High and exceedingly high RH affected the admission rate SSNHL on lag 0 day, and these effects lasted for 8 and 7 days, respectively. There were significant associations between all grades of AP and SSNHL. This is the first study to assess the effect of meteorological variables on SSNHL-related admissions in China using a time-series approach. Long-term exposures to high DTR, RH values, low T-mean values, and all AP grades enhance the incidence of SSNHL in residents. Limiting exposure to extremes of ambient temperature and humidity may reduce the number of SSNHL-related hospital visits in the region. It is advisable to maintain a suitable living environment temperature and avoid extreme temperature fluctuations and high humidity. During periods of high air pollution, it is recommended to stay indoors and refrain from outdoor exercise.

Comparison of the osteogenic potential of fibroblasts from different sources - Jiaojiao Li; Liangliang Fu; Qian Lu; Shuling Guo; Si Chen; Ting Xia; Min Wang; Liangwen Chen; Yi Bai; Haibin Xia (Tissue and Cell, 2024)

Cultivation of phosphate-accumulating biofilm: Study of the effects of acyl-homoserine lactones (AHLs) and cyclic dimeric guanosine monophosphate (c-di-GMP) on the formation of biofilm and the enhancement of phosphate metabolism capacity - Yimeng Zhao; Jun Zhang; Min Ni; Yang Pan; Lu Li; Yanyan Ding (Science of The Total Environment, 2024)

Antibiotic resistome in landfill leachate and impact on groundwater - Wei-Li Jia; Min Zhang; Fang-Zhou Gao; Hong Bai; Lu-Xi He; Liang-Ying He; Ting Liu; Yu Han; Guang-Guo Ying (Science of The Total Environment, 2024)

Overall and geographic pattern of incidence, fatality and mortality of sepsis among hospitalized non-child cancer patients in China: A nationwide cross-sectional study - Bin Lu; Yang Xu; Na Li; Yueyang Zhou; Xudong Ma; Yan Chen; Run Dong; Xiang Zhou; Min Dai; Hongda Chen; Li Weng; Bin Du (Science Bulletin, 2024)

Prioritizing of potential environmental exposure carcinogens beyond IARC group 1–2B based on weight of evidence (WoE) approach - Lu Zhang; Min Li; Dalong Zhang; Wenbo Yue; Zhiyong Qian (Regulatory Toxicology and Pharmacology, 2024)

A DUF966 gene family member OsDSR3 positively regulates alkali stress tolerance in rice - Xuping Lu; Yan Li; Maryam Akhtar; Caixia Liu; Tianli Ma; Weifang Min; Xiaorong Bai; Yangmengfei She; Liang Chen; Lei Tian; Peifu Li; Chengke Luo (Plant Science, 2024)

Photocatalytic degradation of organic pollutants in sewage using CeO2/ZnO 3D nanoflowers - Junzi Huang; Mengjie Lu; Peng Wei; Yahong Xie; Huihui Xie; Min Liu; Liang Li; Jindou Hu; Zhiwei Zhang; Ying Qi (Journal of Environmental Chemical Engineering, 2024)

Preparation of slag-based foam concrete and its carbon dioxide sequestration performance - Jing Zhao; Yu-qing Li; Jing-jing Yang; Xiao-qiang Cao; Jun-xiang Wang; Gang Wang; Lu-lu Sun; Qi-ming Huang; Wei-min Cheng; Zhi-wen Lyu (International Journal of Greenhouse Gas Control, 2024)

Synergistic chemo-photodynamic therapy based on hollow mesoporous organosilica nanoparticles for reducing psoriasis-like inflammation - Zhijia Fan; Gang Zhao; Yixiao Gan; Li Wei; Rong Xia; Min Lu; Zhicheng Wang (Chemical Engineering Journal, 2024)

3D printed dual network Cross-Linked hydrogel electrolytes for high area capacity flexible zinc ion Micro-Batteries - Yongyi Lu; Zongyang Li; Xin Wang; Zhihao Wang; Min Li; Xinyu Hu; Yuehui Wang; Haimei Liu; Yonggang Wang (Chemical Engineering Journal, 2024)

Exogenous application of salicylic acid improves eradication of apple stem grooving virus and apple chlorotic leaf spot virus in apple - Xiao-Yan Ma; Jin-Wei Li; Qing Li; Zi-Han Yan; Xi Cheng; Min-Rui Wang; Zhibo Hamborg; Lu Bao; Dong Zhang; Min-Ji Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Expert Consensus on Big Data Collection of Skin and Appendage Disease Phenotypes in Chinese - Shuang Zhao; Zhongling Luo; Ying Wang; Xinghua Gao; Juan Tao; Yong Cui; Aijun Chen; Daxing Cai; Yan Ding; Heng Gu; Jianying Gu; Chao Ji; et al. (Phenomics, 2024)

Design, synthesis, and evaluation of 2,2’-bipyridyl derivatives as bifunctional agents against Alzheimer’s disease - Ren-Xian Tan; Wei-Hao Li; Jia-Min Pang; Si-Min Zhong; Xin-Yi Huang; Jun-Ze Deng; Lu-Yi Zhou; Jia-Qiang Wu; Xiao-Qin Wang (Molecular Diversity, 2024)

Transcriptomic analysis reveals molecular characterization and immune landscape of PANoptosis-related genes in atherosclerosis - Zhipeng Zheng; Kaiyuan Li; Zhiyuan Yang; Xiaowen Wang; Cheng Shen; Yubin Zhang; Huimin Lu; Zhifeng Yin; Min Sha; Jun Ye; Li Zhu (Inflammation Research, 2024)

Single-Cell Sequencing Technology and Its Application in the Study of Central Nervous System Diseases - Yang Ding; Yu-Yuan Peng; Sen Li; Can Tang; Jie Gao; Hai-Yan Wang; Zai-Yun Long; Xiu-Min Lu; Yong-Tang Wang (Cell Biochemistry and Biophysics, 2024)

Characteristics of typical intermediate and semi volatile organic compounds in Shanghai during China International Import Expo event - Taikui An; Yingjie Li; Rui Wang; Sheng'ao Jing; Yaqin Gao; Shuyu Liu; Dandan Huang; Min Zhou; Haixia Dai; Cheng Huang; Jun Lu; Hongli Wang; et al. (Chemosphere, 2024)

Simulation and experiment of air-duct heating equipment using electricity in a sheep barn using computational fluid dynamics - Zichen Liu; Honglei Cen; Min Lu; Jingbin Li; Qiang Cai; Jing Nie; Baoqin Wen; Yalei Xu (Computers and Electronics in Agriculture, 2024)

A newly isolated strain of Bacillus subtilis W2Z exhibited probiotic effects on juvenile red claw crayfish, Cherax quadricarinatus - Ze-Long Zhang; Jia-Jun Li; Si-Wen Xing; Yao-Peng Lu; Pei-Hua Zheng; Jun-Tao Li; Chen-Guang Hao; Jia-Rui Xu; Jian-An Xian; Li-Min Zhang; Xiu-Xia Zhang (Aquaculture, 2024)

Antihypertensive treatment during pregnancy induces long-term changes in gut microbiota and the behaviors of the attention deficit hyperactivity disorder offspring - Hong-Bao Li; Meng-Lu Xu; Wen-Jie Xia; Yuan-Yuan Dong; Bo Peng; Qing Su; Xiao-Min Wang; Jia-Yue Yu; Ya-Nan Gao; Jun-Zhe Wu; Meng-Yue Xu; Jin-Bao Yang; et al. (Toxicology and Applied Pharmacology, 2024)

Greenhouse gases emissions from aquaculture ponds: Different emission patterns and key microbial processes affected by increased nitrogen loading - Min Deng; Senbati Yeerken; Yuren Wang; Lu Li; Zhouyang Li; Yoong-Sin Oon; Yoong-Ling Oon; Yunpeng Xue; Xugang He; Xiaoli Zhao; Kang Song (Science of The Total Environment, 2024)

Occurrence and fate of pharmaceuticals and personal care products in a wastewater treatment plant with Bacillus bio-reactor treatment - Xi-Ze Min; Zi-Feng Zhang; Xi-Mei Lu; Jia-Cheng Chen; Wan-Li Ma; Li-Yan Liu; Wen-Long Li; Yi-Fan Li; Roland Kallenborn (Science of The Total Environment, 2024)

Crustal thickness variation of the Dabie orogenic belt: Insights from detrital zircon evidence and geological significance - Cheng Cheng; Shuangying Li; Xiangyang Xie; Wei Xie; Dongdong Yang; Guanglu Chai; Yanlin Lu; Xing Wei; Min Li; Bo Hu; Arthur B. Busbey; Xujie Shu (Gondwana Research, 2024)

Emergence of blaNDM-5–bearing IncHI2/ST2 and p0111 multidrug-resistance plasmids and widespread distribution of IncHI2/ST3–blaNDM-5 plasmids across foods, animals, and humans - Lu-Chao Lv; Cheng-Zhen Wang; Jing-Jing Yu; Yan-Xiang Jiao; Li-Min Deng; Wan-Yun He; Guo-Long Gao; Xiao-Yu Zhang; Li-Tao Lu; Xun Gao; Yi-Yun Liu; Jian-Hua Liu (Food Control, 2024)

Lipopolysaccharide modification enhances the inhibitory effect of clodronate liposomes on hepatic fibrosis by depletion of macrophages and hepatic stellate cells - Luyao Zhang; Min Tao; Hengyan Zhang; Shichao Zhang; Xiaojuan Hou; Chen Zong; Gangqi Sun; Shiyao Feng; Haixin Yan; Ying Lu; Xue Yang; Lixin Wei; et al. (Chemico-Biological Interactions, 2024)

Experimental optimization and mechanism analysis of extracting flavonoids with the supramolecular solvents-based methods - Zhi-lu Yu; Shi-yi Hou; Li-mei Lin; Yu-ran Chu; Ya-mei Li; Zhi-min Zhang; Jing Yan; Bo-hou Xia (Sustainable Chemistry and Pharmacy, 2024)

Nitrogen isotopic characteristics of aerosol ammonium in a Chinese megacity indicate the reduction from vehicle emissions during the lockdown period - Zhengjie Li; Hongwei Xiao; Wendell W. Walters; Meredith G. Hastings; Juan Min; Linlin Song; Weizhi Lu; Libin Wu; Wende Yan; Shuguang Liu; Yunting Fang (Science of The Total Environment, 2024)

Petrogenetic link between leucogranite and spodumene pegmatite in Lhozhag, eastern Himalaya: Constraints from U–(Th)–Pb geochronology and Li–Nd–Hf isotopes - Lei Yang; Jia-Min Wang; Xiao-Chi Liu; Fang-Yang Hu; Kang-Shi Hou; Jian-Gang Fu; Guang-Ming Li; Yu-Lu Tian; Fu-Yuan Wu (Lithos, 2024)

Co-foliar application of zinc and nano-silicon to rice helps in reducing cadmium exposure risk: Investigations through in-vitro digestion with human cell line bioavailability assay - Qiang Lin; Yasir Hamid; Honhang Wang; Min Lu; Xuerui Cao; Tong Zou; Zhiqin Chen; Bilal Hussain; Ying Feng; Tingqiang Li; Zhenli He; Xiaoe Yang (Journal of Hazardous Materials, 2024)

Stibnite dissolution and Sb oxidation by Paraccocus versutus XT0.6 via direct and indirect contact - Min Li; Weiqi Wang; Mengxiaojun Wu; Jingwen Lei; Xiaolu Lu; Hongmei Wang (Journal of Hazardous Materials, 2024)

Microplastics plastisphere is an important eco-site for nitrous oxide emission in lakes: A case study of various lakes in Wuhan, China - Lu Li; Zezheng Wang; Chenxi Wu; Min Deng; Zhiwei Xia; Renhui Li; Kang Song (Journal of Cleaner Production, 2024)

Seasonal patterns, fate and ecological risk assessment of pharmaceutical compounds in a wastewater treatment plant with Bacillus bio-reactor treatment - Zi-Feng Zhang; Ying-Ying Fan; Xi-Mei Lu; Xi-ze Min; Wan-Li Ma; Li-Yan Liu; Yi-Fan Li; Wen-Long Li (Journal of Environmental Management, 2024)

Analysis of novel In2S3/polyimide Z-scheme heterojunctions with enhanced photocatalytic target compound degradation efficiency - Min Fu; Mei Yang; Jinwu Bai; Yi Li; Meng Fang; Peng Lu; Xue Kuang (Journal of Environmental Chemical Engineering, 2024)

Highly-sensitive, broad-range, and highly-dynamic MXene pressure sensors with multi-level nano-microstructures for healthcare and soft robots applications - Boqing Jia; Zhikang Li; Tengfei Zheng; Jiaxiang Wang; Zhi-Jun Zhao; Libo Zhao; Bin Wang; Jijian Lu; Kang Zhao; Guoxi Luo; Min Li; Qijing Lin; et al. (Chemical Engineering Journal, 2024)

The Vitis yeshanensis U-box E3 ubiquitin ligase VyPUB21 enhances resistance to powdery mildew by targeting degradation of NIM1-interacting (NIMIN) protein - Leilei Wang; Lu Bian; Qiaofang Shi; Xufei Li; Yadan Sun; Min Li; Anqi Zhao; Xingyuan Peng; Yihe Yu (Plant Cell Reports, 2024)

Eupatilin attenuates doxorubicin-induced cardiotoxicity by activating the PI3K-AKT signaling pathway in mice - Yanyu Lu; Qianqian Min; Xiaoyan Zhao; Li Li; Guojun Zhao; Jianzeng Dong (Molecular and Cellular Biochemistry, 2024)

Long-term cadmium exposure induces epithelial-mesenchymal transition in breast cancer cells by activating CYP1B1-mediated glutamine metabolic reprogramming in BT474 cells and MMTV-Erbb2 mice - Jingdian Li; Peng Gao; Mingke Qin; Junhua Wang; Yan Luo; Ping Deng; Rongrong Hao; Lei Zhang; Mindi He; Chunhai Chen; Yonghui Lu; Qinlong Ma; et al. (Science of The Total Environment, 2024)

RETRACTED: Biochar's dual role in greenhouse gas emissions: Nitrogen fertilization dependency and mitigation potential - Hongzhao Li; Liwen Lin; Yutao Peng; Yongzhou Hao; Zhen Li; Jing Li; Min Yu; Xuewen Li; Yusheng Lu; Wenjie Gu; Baige Zhang (Science of The Total Environment, 2024)

Temporal and spatial variations in the sub-daily precipitation structure over the Qinghai–Tibet Plateau (QTP) - Hou-Liang Lu; Jun Qiu; Meng-Jia Li; Hui-Min Zuo; Jin-Li Li; Bill X. Hu; Fang-Fang Li (Science of The Total Environment, 2024)

Feasibility of reconstructing atmospheric chloride deposition rates based on tritium tracer in the unsaturated zone - Yanwei Lu; Peiyue Li; Min Li; Haoyan Wei; Mingyi Wen; Yupu Ming; Bingcheng Si (Journal of Hydrology, 2024)

Enzymatic hydrolysis of oat core flour improves physiochemical and sensory behaviors for oat milk - Min Zhang; Kai Huang; Jun Lu; Anni Lu; Xiao Guan; Yu Zhang; Sen Li; Hongdong Song; Hongwei Cao; Zhu Sun; Zhiquan Yu (Journal of Cereal Science, 2024)

Comparison of the flight ability of diapausing and post-diapause Osmia excavata Alfken (Hymenoptera: Megachilidae) at different temperatures - Zhaoyun Lyu; Haigang Liu; Ting Zhou; Min Feng; Zengbin Lu; Lei Nie; Guiping Wang; Guangzhao Wang; Lili Li; Xingyuan Men; Meng Sun; Yi Yu (Journal of Asia-Pacific Entomology, 2024)

Customized self-assembled bimetallic hybrid nanoflowers promoting the robustness of D-allulose 3-epimerase - Xin Gao; Senbiao Fang; Xuanzhen Ma; Tong Wang; Chao Li; Fuping Lu; Hui-Min Qin (Chemical Engineering Journal, 2024)

Combating drug-resistant helicobacter pylori infection with zinc peroxide-based nanoparticles: A ROS reservoir via photochemical reaction - Ka Ioi Wong; Shen Wang; Ming Li; Gang Zhao; Caixia Wang; Lei Wu; Huizhen Fan; Min Yao; Min Lu (Chemical Engineering Journal, 2024)

Enhanced hydroisomerization of n-heptane over bifunctional catalysts with highly dispersed Pd nanoparticles supported on H-Yβ composite zeolite - Yu-Hong Kang; Xiao-Qi Zhang; Juan Gao; Guang-Hui Liu; Yan-Jun Li; Yong Gao; Jin-Jun Bai; Ai-Min Wang; Xian-Yong Wei; Cui-Ying Lu (Chemical Engineering Journal, 2024)

Nitric oxide and ion channels mediate l-cysteine-induced inhibition of colonic smooth muscle contraction - Xiaojing Quan; Min Zhang; Zhaojun Qiao; Xuan Kou; Qiong Xue; Jinhai Wang; Lu Li (Journal of Muscle Research and Cell Motility, 2024)

Structural Features and Phylogenetic Implications of Crinoid Echinoderms Based on Thirteen Novel Mitochondrial Genomes - Qinzeng Xu; Min Lu; Yuyao Sun; Zhong Li; Yixuan Li; Yue Dong; Xuying Hu; Qian Zhang; Bing Liu; Xuebao He (Journal of Marine Science and Engineering, 2024)
Crinoids, as integral echinoderms, play a crucial ecological role in benthic communities, serving as significant indicators reflecting the health of marine ecosystems. However, the phylogenetic relationships within crinoids are unclear. More molecular data can help to facilitate biodiversity assessment and elucidate evolutionary relationships by the phylogenetic tree. In this study, 13 complete mitochondrial genomes of the Crinoidea class were sequenced, annotated, and compared with other same class species available on NCBI. The results reveal five different gene order patterns among these mitochondrial genomes, indicating that crinoids have undergone gene rearrangements during evolution. The complete mitochondrial genome length of crinoids ranges from 15,772 bp to 16,850 bp. High A + T content, ranging from 64.5% to 74.2%, was observed. Additionally, our analysis of protein-coding genes highlights a preference for A + T nucleotides, along with specific start and stop codon usage, offering insights into codon bias and its implications for protein synthesis and function. The phylogenetic topology shows that the stalkless crinoid and stalked crinoid are distinct, and the phylogenetic trees generated based on maximum likelihood and Bayesian inference are almost identical at the family and order topology levels. The phylogenetic relationships of each family were fully clarified in four orders. A total of eleven positive selection sites were detected within six genes: cytb, nad2, nad3, nad4, nad4L and nad5. This study reveals the phylogenetic relationships of crinoid species, the mitochondrial gene differences, and the selective pressure on the evolution of stalked crinoids. This study significantly enhanced the crinoid mitochondrial genome database and contributed to a better understanding of the phylogenetic relationships among crinoid echinoderms.

Effects of different stocking densities and feeding frequencies on growth, physiological and biochemical indexes, and intestinal microflora of largemouth bass (Micropterus salmoides) under land-based round pond - Yu-Xiang Xie; Xue-Ming Yang; Gen Kaneko; Jun-Neng Liang; Lu-Ting Wen; Yi-Jian Li; Qui-Wei Ao; Li-Ming Huang; Pan Li; Wen-Wu Min; Lin-Yuan Jiang; Qiong Yang; et al. (Aquaculture, 2024)

Long-term exposure to the mixture of phthalates induced male reproductive toxicity in rats and the alleviative effects of quercetin - Li-Lan Liu; Jun-Zhe Yue; Zhen-Yu Lu; Ru-Ya Deng; Can-Can Li; Ye-Na Yu; Wen-Jin Zhou; Min Lin; Hai-Tao Gao; Jiaming Liu; Ling-Zi Xia (Toxicology and Applied Pharmacology, 2024)

CncC-Keap1-P450s pathway is involved in the detoxification of emamectin benzoate in the spongy moth Lymantria dispar - Zhe Xu; Jianyang Bai; Mengru Min; Jingyu Cao; Yue Zhang; Lu Li; Jingxin Cao; Xiaoqian Ma; Yanchun Xu; Ling Ma (Pesticide Biochemistry and Physiology, 2024)

Catalytic hydroconversion of guaiacol and a poplar lignin derivate to cyclanes over Ni20%/β25 - Qian-Qian Kong; Xiang Bai; Xian-Yong Wei; Yierxiati. Dilixiati; Zi-Chun Fan; Zhuang Li; Ji Zhao; Jia-Hao Li; Li Li; Kun-Lang Lu; Zhi-Min Zong (Fuel, 2024)

Composite aerogel incorporating low temperature phase change microcapsules for enhanced thermal insulation - Bin Yan; Min Li; Honglang Lu; Menghan Pi; Jiahao Mu; Wei Cui; Rong Ran (Chemical Engineering Journal, 2024)

Prenatal exposures to phthalates and bisphenols in relation to oxidative stress: single pollutant and mixtures analyses - Jia-Yue Zeng; Min Zhang; Xu-Hui Chen; Chong Liu; Yan-Ling Deng; Pan-Pan Chen; Yu Miao; Fei-Peng Cui; Tian Shi; Ting-Ting Lu; Xiao-Ying Liu; Yang Wu; et al. (Environmental Science and Pollution Research, 2024)

Laccase-evoked removal of antibiotics: Reaction kinetics, conversion mechanisms, and ecotoxicity assessment - Kai Sun; Mei-Hua Chen; Xue-Min Qi; Dan Hong; Ling-Zhi Dai; Shun-Yao Li; Yi-Chen Lu; Han-Qing Yu (Critical Reviews in Environmental Science and Technology, 2024)

Microplastic, a possible trigger of landfill sulfate reduction process - Shuli Guo; Zixiao Wu; Xianghang Li; Dongsheng Shen; Jiali Shentu; Li Lu; Shengqi Qi; Min Zhu; Yuyang Long (Science of The Total Environment, 2024)

Basin-scale reconstruction of late Pleistocene-Holocene fluvial landform evolution and its mechanisms in transitional areas between Taihang Mountain and North China Plain - Yan Tian; Panpan Chen; Peng Lu; Ye Li; Hui Wang; Liang Zhou; Xiaohu Zhang; Shugang Yang; Xingguo Zhang; Xiaoyu Chai; Haiguo Zhai; Min Liu; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Woody plant cell walls: Fundamentals and utilization - Wei Li; Ying-Chung Jimmy Lin; Ying-Lan Chen; Chenguang Zhou; Shuang Li; Nette De Ridder; Dyoni M. Oliveira; Lanjun Zhang; Baocai Zhang; Jack P. Wang; Changzheng Xu; Xiaokang Fu; et al. (Molecular Plant, 2024)

Aging in soil increases the disturbance of microplastics to the gut microbiota of soil fauna - Jing Ding; Zhaoqin Liang; Min Lv; Xiuyu Li; Shuang Lu; Suyu Ren; Xiaoyong Yang; Xiaoqiang Li; Chen Tu; Dong Zhu; Lingxin Chen (Journal of Hazardous Materials, 2024)

LED-driven photocatalytic degradation of tetracycline by chromite ore processing residue (COPR): Mechanism, pathway, toxicity assessment - Shuo Zhang; Cunfang Lu; Yelei Wang; Cheng Tian; Peng Chen; Mingyuan Yang; Min Zhang; Rui Xu; Yuanyuan He; Zilong Li (Journal of Cleaner Production, 2024)

An in-situ blocking strategy for improved anti-interference inspection of AFB1 based on hollow covalent organic framework capsules with commodious and undisturbed microenvironment - Lu Yang; Jing Wang; Chun-Yang Li; Man-Man Wang; Jing-Min Liu; Shuo Wang (Food Chemistry, 2024)

Peroxymonosulfate activation by microplastics coagulated sludge-derived iron-carbon composite for effective degradation of tetracycline hydrochloride: Performance and mechanism - Min Yang; Wenyu Wang; Huifang Ma; Xi Lu; Lei Chen; Yi Li; Hongfang Ma (Chemical Engineering Journal, 2024)

Voluntary running wheel exercise induces cognitive improvement post traumatic brain injury in mouse model through redressing aberrant excitation regulated by voltage-gated sodium channels 1.1, 1.3, and 1.6 - Dan Wang; Hui-Xiang Zhang; Guo-Ji Yan; Hao-Ran Zhao; Xiao-Han Dong; Ya-Xin Tan; Shan Li; Min-Nan Lu; Rong Mei; Li-Na Liu; Xu-Yang Wang; Yan-Bin Xiyang (Experimental Brain Research, 2024)
Traumatic brain injury (TBI) leads to disturbed brain discharge rhythm, elevated excitability, anxiety-like behaviors, and decreased learning and memory capabilities. Cognitive dysfunctions severely affect the quality of life and prognosis of TBI patients, requiring effective rehabilitation treatment. Evidence indicates that moderate exercise after brain injury decreases TBI-induced cognitive decline. However, the underlying mechanism remains unelucidated. Our results demonstrate that TBI causes cognitive impairment behavior abnormalities and overexpression of Nav1.1, Nav1.3 and Nav1.6 proteins inside the hippocampus of mice models. Three weeks of voluntary running wheel (RW) exercise treatments before or/and post-injury effectively redressed the aberrant changes caused by TBI. Additionally, a 10% exercise-conditioned medium helped recover cell viability, neuronal sodium current and expressions of Nav1.1, Nav1.3 and Nav1.6 proteins across cultured neurons after injury. Therefore, the results validate the neuroprotection induced by voluntary RW exercise treatment before or/and post-TBI. The RW exercise-induced improvement in cognitive behaviors and neuronal excitability could be associated with correcting the Nav1.1, Nav1.3, and Nav1.6 expression levels. The current study proves that voluntary exercise is an effective treatment strategy against TBI. The study also highlights novel potential targets for rehabilitating TBI, including the Navs proteins.

Dietary inositol improved glucose and lipid metabolism mediated by the Insulin-PI3K-Akt signaling pathway in Pacific white shrimp (Litopenaeus vannamei) - Jingjing Lu; Xinyue Tao; Ming Li; Xin Zhang; Qicun Zhou; Jiaxiang Luo; Tingting Zhu; Lefei Jiao; Min Jin (Aquaculture, 2023)

Antagonizing pathological α-synuclein-mediated neurodegeneration by J24335 via the activation of immunoproteasome - Zhijian Pan; Chao-Wu Yu; Chen Zhao; Min Shao; Xuanjun Yang; Xiaonan Liang; Haitao Li; Yucong Lu; Qingqing Ye; Ji-Wang Chern; Jiahong Lu; Hefeng Zhou; et al. (Toxicology and Applied Pharmacology, 2023)

Chronic cadmium exposure triggered ferroptosis by perturbing the STEAP3-mediated glutathione redox balance linked to altered metabolomic signatures in humans - Ping Deng; Jingdian Li; Yonghui Lu; Rongrong Hao; Mindi He; Min Li; Miduo Tan; Peng Gao; Liting Wang; Huihui Hong; Jiawen Tao; Muxue Lu; et al. (Science of The Total Environment, 2023)

Archaea are better adapted to antimony stress than their bacterial counterparts in Xikuangshan groundwater - Weiqi Wang; Jingwen Lei; Min Li; Xinyue Zhang; Xing Xiang; Hongmei Wang; Xiaolu Lu; Liyuan Ma; Xiaoyan Liu; Olli H. Tuovinen (Science of The Total Environment, 2023)

The role of satellite remote sensing in mitigating and adapting to global climate change - Shaohua Zhao; Min Liu; Minghui Tao; Wei Zhou; Xiaoyan Lu; Yujiu Xiong; Feng Li; Qiao Wang (Science of The Total Environment, 2023)

Vertical distribution rules and factors influencing phytoplankton in front of a drinking water reservoir outlet - Yongao Lu; Youcai Tuo; Linglei Zhang; Xiangying Hu; Bin Huang; Min Chen; Zhenghe Li (Science of The Total Environment, 2023)

Dynamic characteristics of net anthropogenic phosphorus input to the upper Yangtze River Basin from 1989 to 2019: Focus on the phosphate ore rich area in China - Junlan Yang; Min Li; Lu Liu; Hongjun Zhao; Wenqing Luo; Yali Guo; Xiaonan Ji; Wei Hu (Journal of Environmental Management, 2023)

Fabrication of a novel acid-resistant nanofiltration membrane with dual-charged functional layer for metal ions recovery - Lu Bai; Zhilu Li; Zhengjun Peng; Youjing Zhao; Hongjun Yang; Min Wang (Journal of Environmental Chemical Engineering, 2023)

A mathematical model to simulate the release of Fe and Mn from sediments in a drinking water reservoir - Wenyan He; Jia Li; Min Chen; Hailong Sun; Linglei Zhang; Yongao Lu; Yunxiao Jia; Hong Zhang (Environmental Research, 2023)

Metagenomics, metatranscriptomics, and proteomics reveal the metabolic mechanism of biofilm sequencing batch reactor with higher phosphate enrichment capacity under low phosphorus load - Min Ni; Yang Pan; Dapeng Li; Yong Huang; Zhiqiang Chen; Lu Li; Zhen Bi; Ruijing Wu; Zuowei Song (Environmental Research, 2023)

Decoupling the heterogeneity of sediment microbial communities along the urbanization gradients: A Bayesian-based approach - Jie Liang; Junjie Ding; Ziqian Zhu; Xiang Gao; Shuai Li; Xin Li; Min Yan; Qinxue Zhou; Ning Tang; Lan Lu; Xiaodong Li (Environmental Research, 2023)

Low-temperature structural deformation and fragmentation of lead styphnate by in-situ experiments and calculation - Momang Tian; Qian Yu; Yuewen Lu; Ji-Min Han; Li Yang (Chemical Engineering Journal, 2023)

Mettl13 protects against cardiac contractile dysfunction by negatively regulating C-Cbl-mediated ubiquitination of SERCA2a in ischemic heart failure - Shuting Yu; ZhiYong Sun; Xiuzhu Wang; Tiantian Ju; Changhao Wang; Yingqi Liu; Zhezhe Qu; KuiWu Liu; Zhongting Mei; Na Li; Meixi Lu; Fan Wu; et al. (Science China Life Sciences, 2023)

Micropeptides: origins, identification, and potential role in metabolism-related diseases - Yirui Lu; Yutong Ran; Hong Li; Jiao Wen; Xiaodong Cui; Xiaoyun Zhang; Xiumei Guan; Min Cheng (Journal of Zhejiang University-SCIENCE B, 2023)

Subsoil Tillage and Organic Fertilization Benefit Rice Root Growth and Yield by Ameliorating Soil Compaction and Fertility - Rongyan Bu; Min Li; Wenlong Cheng; Shang Han; Hui Wang; Shan Tang; Changai Lu; Ji Wu (Journal of Soil Science and Plant Nutrition, 2023)

Depletion of PIEZO1 expression is accompanied by upregulating p53 signaling in mice with perioperative neurocognitive disorder - Fuhai Bai; Lu Huang; Zonghong Long; Min Zhang; Qiangting Deng; Jing Huang; Xiaohang Bao; Xianglin Hao; Hong Li (Functional & Integrative Genomics, 2023)

Highly specific detection of Neisseria gonorrhoeae based on recombinase polymerase amplification-initiated strand displacement amplification - Mengnan Fan; Jianru Yang; Xiaosu Wang; Yongjie Xu; Bing Li; Hui Yang; Qin Lu; Xun Min; Meirong Huang; Jian Huang (Analytica Chimica Acta, 2023)

The phase variation between wrinkly and smooth colony phenotype affects the virulence of Vibrio parahaemolyticus - Qimin Wu; Xue Li; Miaomiao Zhang; Xingfan Xue; Tingting Zhang; Hui Sun; Shuhui Xiong; Renfei Lu; Yiquan Zhang; Min Zhou (Archives of Microbiology, 2023)

Developing a model-ready highly resolved HONO emission inventory in Guangdong using domestic measured emission factors - Xiaohong Yin; Feng Tang; Zhijiong Huang; Songdi Liao; Qinge Sha; Peng Cheng; Menghua Lu; Zhen Li; Fei Yu; Yuanqian Xu; Min Shao; Junyu Zheng (Science of The Total Environment, 2023)

Mineralogy, petrology and P-T conditions of the spodumene pegmatites and surrounding meta-sediments in Lhozhag, eastern Himalaya - Jia-Min Wang; Kang-Shi Hou; Lei Yang; Xiao-Chi Liu; Ru-Cheng Wang; Guang-Ming Li; Jian-Gang Fu; Fang-Yang Hu; Yu-Lu Tian; Fu-Yuan Wu (Lithos, 2023)

Widely targeted metabolomics provides insights into the effect of parboiling treatment on the nutritional quality of black rice based on its improved cooking characteristics - Xin Wu; Xingxing Zhang; Min Liu; Tang Tang; Yanhua Li; Hao Chen; Qun Lu; Rui Liu (Journal of Cereal Science, 2023)

A novel colorimetric/fluorescent dual-signal probe based on silver nanoparticles functionalized with L-cysteine and rhodamine 6G derivatives for copper ion detection and cell imaging - Mingrong Lu; Yao Zhang; Shaoqing Li; Yifei Zhang; Shuju Fang; Wenrong Yang; Min Yang; Hongbin Wang (Environmental Research, 2023)

Hydrogel-based intelligent greenhouse films for simultaneous fogging prevention and indoor environmental monitoring - Honglang Lu; Huanxiong Liang; Jianle Liu; Hui Zhou; Menghan Pi; Min Li; Bin Yan; Wei Li; Wei Cui; Rong Ran (Chemical Engineering Journal, 2023)

Assessing the causal relationship between immune traits and systemic lupus erythematosus by bi-directional Mendelian randomization analysis - Jie Gu; Guan-Min Yan; Xiao-Lin Kong; Yin-Ying Zhang; Li-Hong Huang; Hui-Min Lu (Molecular Genetics and Genomics, 2023)

Unraveling the genomic diversity and ecological potential of the genus Demequina: insights from comparative analysis of different saline niche strains - Lei Gao; Bao-Zhu Fang; Chun-Yan Lu; Kun-Hui Hong; Xin-Yu Huang; Ting-Ting She; Min Xiao; Wen-Jun Li (Frontiers in Marine Science, 2023)
During an investigation of the culturable microbial diversity of sediments with salinity from tidal flats and saline lake, seven strains of the genus Demequina were harvested. The genomic analysis and physiological characteristics of strains of this genus have unveiled their significant potential in degrading complex carbon source such as lignin, hemicellulose, chitin, and oligosaccharides. In addition, these strains show potential abilities in nitrite ammonification and sulfide oxidation. These findings not only improved our understanding of their metabolic model, but also provided valuable insights into their ecological roles. Four new species of the genus Demequina are described: Demequina litoralis sp. nov., with SYSU T00192 T designated as the type species; Demequina zhanjiangensis sp. nov., with SYSU T00b26 T as the type species; Demequina lignilytica sp. nov., with SYSU T00068 T as the type species; and Demequina muriae sp. nov., with EGI L300058 T as the type species. Additionally, strains SYSU T0a273, SYSU T00039-1, and SYSU T00039 are identified as different strains of Demequina lignilytica . Our study thus sheds light on the diversity, biological significance, and ecological contribution of the Demequina genus in different habitats.

A Novel TTBK2 Mutation in a Chinese Pedigree with Spinocerebellar Ataxia 11 - Yin-Qian Lu; Jian-Min Chen; Ya-Li Huang; Zhang-Yu Zou (The Cerebellum, 2023)

Age-specific difference in the temporal relationships between updated cardiovascular health construct and arterial stiffness in middle-aged and older adults - Jiaojiao Huang; Xiaoli Xu; Yingxia Zhou; Zhuojun Xin; Qiuyu Cao; Ruixin He; Tianzhichao Hou; Yi Ding; Jieli Lu; Tiange Wang; Zhiyun Zhao; Yu Xu; et al. (GeroScience, 2023)

The regulative effect and repercussion of probiotics and prebiotics on osteoporosis: involvement of brain-gut-bone axis - Yuan-Wei Zhang; Mu-Min Cao; Ying-Juan Li; Guang-Chun Dai; Pan-Pan Lu; Ming Zhang; Li-Yong Bai; Xiang-Xu Chen; Cheng Zhang; Liu Shi; Yun-Feng Rui (Critical Reviews in Food Science and Nutrition, 2023)

Chemical constituents from the leaves of Cinnamomum camphora and their α-glucosidase inhibitory activities - Xing Jiang; Xi-Han Zhang; Yu-Xin Li; Kai Chen; Bin Lin; Tian-Qi Lu; Min Yang; Guang-Tong Chen; Bo-Yi Fan; Wen-Li Wang (Phytochemistry Letters, 2023)

Inter-comparison of extraction methods for plant water isotope analysis and its indicative significance - Mingyi Wen; Xining Zhao; Bingcheng Si; Dong He; Min Li; Xiaodong Gao; Yaohui Cai; Yanwei Lu; Yubao Wang (Journal of Hydrology, 2023)

An efficiency-driven approach for global ecological industrial parks - Shih-Fang Lo; Wen-Min Lu; Che-Wei Chang; Shiu-Wan Hung; Li-Ling Yang (Journal of Cleaner Production, 2023)

Application of a novel adsorbent UiO-66 modified by Ce to tetracycline removal in water bodies - Xinyu Hu; Yao Zhang; Mingrong Lu; Min Yang; Jianmin Li; Zhengmei Wang; Guizhen Li; Hongbin Wang (Journal of Environmental Chemical Engineering, 2023)

Multiple path-dominated activation of peroxymonosulfate by MOF-derived Fe2O3/Mn3O4 for catalytic degradation of tetracycline - Chensi Tang; Min Cheng; Cui Lai; Ling Li; Zhen Wei; Dengsheng Ma; Li Du; Guangfu Wang; Lu Yang; Lin Tang (Journal of Environmental Chemical Engineering, 2023)

Effect and microbial mechanism of suspended sediments particle size on nitrous oxide emission in eutrophic lakes - Senbati Yeerken; Lu Li; Min Deng; Kang Song; Fengchang Wu (Environmental Pollution, 2023)

Seismic fragility assessment of aqueduct bent structures subjected to mainshock-aftershock sequences - Min Du; Sherong Zhang; Chao Wang; Lei She; Jiabei Li; Tong Lu (Engineering Structures, 2023)

Correction: Angiotensin-(1–9) prevents Angiotensin II-induced endothelial apoptosis through CNPY2/PERK pathway - Chun-ling Guo; Hui-min Liu; Bao Li; Zhao-yang Lu (Apoptosis, 2023)

Serum exosomal hsa_circRNA_0001842 is the potential biomarker for diagnosing lower limb vascular disease in type 2 diabetes mellitus - Qian-Qian Liu; Xing-Hui Liu; Hai-Ming Wang; Li-Min Xu; Xiao-Jing Zhao; Shu-Guang Han; Zuo-Hua Lu (Journal of Genetics, 2023)

Periodically reversing electrocoagulation technique for efficient removal of short-chain perfluoroalkyl substances from contaminated groundwater around a fluorochemical facility - Yang Liu; Meng-Yuan Lu; Jia Bao; Li-Xin Shao; Wen-Jing Yu; Xiao-Min Hu; Xin Zhao (Chemosphere, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Molecular mechanism by which StSN2 overexpression inhibits the enzymatic browning of potato - Li-qin Li; Yu-lu Mu; Jing Chen; Qiang Wang; Yi-fei Lu; Sun Xin; Shi-min Yang; Xue-li Huang; Xi-yao Wang; Li-ming Lu (Postharvest Biology and Technology, 2023)

Phytochemistry and biological activities of corynanthe alkaloids - Jun Li; Jia-Xing Li; Hua Jiang; Min Li; Lin Chen; Yue-Yue Wang; Lu Wang; Ning Zhang; He-Zhe Guo; Kai-Long Ma (Phytochemistry, 2023)

An integrated approach to identify the source apportionment of potentially toxic metals in shale gas exploitation area soil, and the associated ecological and human health risks - Yan Li; Hongcheng Bai; Yutong Li; Xin Zhang; Lilan Zhang; Daijun Zhang; Min Xu; Hong Zhang; Peili Lu (Journal of Hazardous Materials, 2023)

Tuning the intrinsic catalytic sites of magnetite to concurrently enhance the reduction of H2O2 and O2: Mechanism analysis and application potential evaluation - Ling Li; Min Cheng; Eydhah Almatrafi; Lei Qin; Shiyu Liu; Huan Yi; Lu Yang; Zhexin Chen; Dengsheng Ma; Mingming Zhang; Xuerong Zhou; Fuhang Xu; et al. (Journal of Hazardous Materials, 2023)

A new insight in enhancing phosphate enrichment in biofilm process: Comparison of the key metabolic pathways in highly-efficient and dominant PAOs based on metagenomics - Min Ni; Yimeng Zhao; Yang Pan; Dapeng Li; Yong Huang; Zhiqiang Chen; Lu Li; Zuowei Song (Journal of Environmental Management, 2023)

Individual and joint associations of urinary phthalate metabolites with polycystic ovary and polycystic ovary syndrome: Results from the TREE cohort - Min Zhang; Chong Liu; Xiao-Qiong Yuan; Fei-Peng Cui; Yu Miao; Wen Yao; Dan-Yu Qin; Yan-Ling Deng; Pan-Pan Chen; Jia-Yue Zeng; Xiao-Ying Liu; Yang Wu; et al. (Environmental Toxicology and Pharmacology, 2023)

Corrigendum to “Effectiveness and appropriateness of core areas in an integrated protected area: A case study of Ecological Protected Areas in Yangmingshan National Park, Taiwan” [Environ. Sci. Policy 145 (2023) 175–187] - Li-Wen Chung; Chin-Liang Chao; Min-Chun Liao; Chieh-Wen Kao; Dau-Jye Lu (Environmental Science & Policy, 2023)

An electrochemical sensing platform for biomonitoring the potential toxicity of plastic particles by detecting NO - Jiancheng Zhang; Congcong Zhang; Yuyang Li; Jingjing Xiao; Yilun Zhang; Min Jia; Lixia Lu; Hongyan Zhang; Jun Zhou; Zhenguo Zhang; Xin Du (Chemical Engineering Journal, 2023)

Spautin-1 Protects Against Mild TBI-Induced Anxiety-Like Behavior in Mice via Immunologically Silent Apoptosis - Hui-Tao Miao; Rong-Xin Song; Yue Xin; Lu-Ying Wang; Jin-Meng Lv; Na-Na Liu; Zhi-You Wu; Wei Zhang; Yan Li; Dong-Xue Zhang; Li-Min Zhang (NeuroMolecular Medicine, 2023)

PPARɑ Ligand Caudatin Improves Cognitive Functions and Mitigates Alzheimer’s Disease Defects By Inducing Autophagy in Mice Models - Senthilkumar Krishnamoorthi; Ashok Iyaswamy; Sravan Gopalkrishnashetty Sreenivasmurthy; Abhimanyu Thakur; Karthick Vasudevan; Gaurav Kumar; Xin-Jie Guan; Kejia Lu; Isha Gaurav; Cheng-Fu Su; Zhou Zhu; Jia Liu; et al. (Journal of Neuroimmune Pharmacology, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Exploring the role of detoxification genes in the resistance of Bursaphelenchus xylophilus to different exogenous nematicidal substances using transcriptomic analyses - Jingxin Cao; Xin Hao; Yang Li; Ruina Tan; Zhixin Cui; Lu Li; Yue Zhang; Jingyu Cao; Mengru Min; Liwei Liang; Zhe Xu; Wei Ma; et al. (Pesticide Biochemistry and Physiology, 2023)

Synthetic phylogenetically diverse communities promote denitrification and stability - Min Zhou; Xiaotong Guan; Ting Deng; Ruiwen Hu; Lu Qian; Xueqin Yang; Bo Wu; Juan Li; Qiang He; Longfei Shu; Qingyun Yan; Zhili He (Environmental Research, 2023)

Emerging roles of air pollution and meteorological factors in autoimmune eye diseases - Fan Cao; Zhuo-Ran Liu; Qin-Yu Ni; Chen-Kai Zha; Shu-Jie Zhang; Jia-Min Lu; Yue-Yang Xu; Li-Ming Tao; Zheng-Xuan Jiang; Hai-Feng Pan (Environmental Research, 2023)

Design and operation insights concerning a pilot-scale S0-driven autotrophic denitrification packed-bed process - Yi-Lu Sun; Zhuo-Ran Li; Xue-Ning Zhang; Heng Dong; Zhi-Min Qian; Shan Yi; Wei-Qin Zhuang; Hao-Yi Cheng; Ai-Jie Wang (Chemical Engineering Journal, 2023)

Highly stretchable phase change composites for simultaneous health monitoring and thermotherapy - Yi-Cun Zhou; Jie Yang; Wu-Di Li; Peng Yu; Zheng-Min Zhang; Lu Bai; Rui-Ying Bao; Wei Yang (Chemical Engineering Journal, 2023)

Residual status and source analysis of phthalate esters in Ulungur Lake, China - Manli Wang; Jianjiang Lu; Li Zhou; Youzhi Su; Han Yao; Min Li; Xiaowen Yin (Environmental Geochemistry and Health, 2023)

Effect of curcumin on the formation of polycyclic aromatic hydrocarbons in grilled chicken wings - Huixin Tian; Jing Yu; Min Li; Jing Li; Yifeng Lu; Xiaobo Yu; Shaoyan Lin; Xianming Zeng; Xinglian Xu; Minyi Han (Food Chemistry, 2023)

Effectiveness and appropriateness of core areas in an integrated protected area: A case study of Ecological Protected Areas in Yangmingshan National Park, Taiwan - Li-Wen Chung; Chih-Liang Chao; Min-Chun Liao; Chieh-Wen Kao; Dau-Jye Lu (Environmental Science & Policy, 2023)

Engineering highly efficient NIR-II FRET platform for Background-Free homogeneous detection of SARS-CoV-2 neutralizing antibodies in whole blood - Lei Zhao; Qingwei Song; Weikang Mai; Min Deng; Yu Lei; Lu Chen; Weiya Kong; Lei Zhang; Lin Zhang; Yantao Li; Huiru Ye; Yiru Qin; et al. (Chemical Engineering Journal, 2023)

Beta-naphthoflavone increases the differentiation of osteoblasts and suppresses adipogenesis in human adipose derived stem cells involving STAT3 pathway - Ming Lu; Min Li; Tao Luo; Yongsui Li; Mingxin Wang; Huashi Xue; Mengchen Zhang; Qiu Chen (Molecular & Cellular Toxicology, 2023)

Application of the metal ions as potential population biomarkers for wastewater-based epidemiology: estimating tobacco consumption in Southern China - Lei Xu; Yu-ting Lu; Dong-feng Wu; Xuan Li; Min Song; Tai-jun Hang; Meng-xiang Su (Environmental Geochemistry and Health, 2023)

The interspecific competition of tree plants in the presence of AM fungi and litter facilitates root morphological development and nutrition when compared with intraspecific competition - Yun Guo; Kaiping Shen; Tingting Xia; Yuejun He; Wenda Ren; Pan Wu; Yan Lin; Bangli Wu; Xu Han; Lu Gao; Jinting Li; Xiaorun Hu; et al. (Environmental Science and Pollution Research, 2023)

Field variation of groundwater recharge and its uncertainty via multiple tracers' method in deep loess vadose zone - Han Li; Min Li; Changhong Miao; Bingcheng Si; Yanwei Lu (Science of The Total Environment, 2023)

Mariculture affects antibiotic resistome and microbiome in the coastal environment - Lu-Xi He; Liang-Ying He; Fang-Zhou Gao; Min Zhang; Jun Chen; Wei-Li Jia; Pu Ye; Yu-Wei Jia; Bai Hong; Si-Si Liu; You-Sheng Liu; Jian-Liang Zhao; et al. (Journal of Hazardous Materials, 2023)

Hollow-structured molecularly imprinted polymers enabled specific enrichment and highly sensitive determination of aflatoxin B1 and sterigmatocystin against complex sample matrix - Lu Yang; Jing Wang; Chun-Yang Li; Qisijing Liu; Jin Wang; Jing Wu; Huan Lv; Xue-Meng Ji; Jing-Min Liu; Shuo Wang (Journal of Hazardous Materials, 2023)

Facile treatment of municipal solid waste incineration fly ash by one-step microwave hydrothermal method: Hazards detoxification and tobermorite synthesis - Ruirui Yuan; Xiaohui Fan; Min Gan; Qianqian Zhao; Siping Lu; Shixian Li (Journal of Environmental Chemical Engineering, 2023)

Steam explosion improves extractability, antioxidant activity and α-glucosidase inhibitory activity of the constituents of Java tea (Clerodendranthus spicatus) - Jia Wang; Xiaoyu Zhang; Junyu Liu; Ruilin Li; Jingna Zhou; Mingyue Li; Jingyang Lu; Guangyu Zhao; Xiang Li; Wenjie Sui; Min Zhang; Haixia Chen (Innovative Food Science & Emerging Technologies, 2023)

Selective catalytic hydroconversion of crude phenols to cyclohexanols over a carbon-based nickel catalyst and separation of condensed arenes from a low-temperature coal tar - Jia-Hao Li; Xian-Yong Wei; Zheng Yang; Dao-Guang Teng; Li Li; Zhuang Li; Zi-Chun Fan; Qian-Qian Kong; Ji Zhao; Kun-Lang Lu; Fan Yin; Zhi-Min Zong (Fuel, 2023)

Complexity of initiation and evolution of the 2013 Yunlong earthquake swarm - Min Liu; Lu Li; Miao Zhang; Xinglin Lei; Mladen R. Nedimović; Alexandre P. Plourde; Rumeng Guo; Weitao Wang; Hongyi Li (Earth and Planetary Science Letters, 2023)

High nitrous oxide (N2O) greenhouse gas reduction potential of Pseudomonas sp. YR02 under aerobic condition - Yuren Wang; Min Deng; Biqing Li; Lu Li; Yoong-Sin Oon; Xiaoli Zhao; Kang Song (Bioresource Technology, 2023)

Ndufa4 Regulates the Proliferation and Apoptosis of Neurons via miR-145a-5p/Homer1/Ccnd2 - Fang Fu; Chen Chen; Kun Du; Lu-shan Li; Ru Li; Ting-ying Lei; Qiong Deng; Dan Wang; Qiu-xia Yu; Xin Yang; Jin Han; Min Pan; et al. (Molecular Neurobiology, 2023)
The Dandy–Walker malformation (DWM) is characterized by neuron dysregulation in embryonic development; however, the regulatory mechanisms associated with it are unclear. This study aimed to investigate the role of NADH dehydrogenase 1 alpha subcomplex 4 (NDUFA4) in regulating downstream signaling cascades and neuronal proliferation and apoptosis. Ndufa4 overexpression promoted the proliferation of neurons and inhibited their apoptosis in vitro, which underwent reverse regulation by the Ndufa4 short hairpin RNAs. Ndufa4 -knockout (KO) mice showed abnormal histological alterations in the brain tissue, in addition to impaired spatial learning capacity and exploratory activity. Ndufa4 depletion altered the microRNA expressional profiles of the cerebellum: Ndufa4 inhibited miR-145a-5p expression both in the cerebellum and neurons. miR-145a-5p inhibited the proliferation of neurons and promoted their apoptosis. Ndufa4 promoted and miR-145a-5p inhibited the expression of human homer protein homolog 1 and cyclin D2 in neurons. Thus, Ndufa4 promotes the proliferation of neurons and inhibits their apoptosis by inhibiting miR-145a-5p, which directly targets and inhibits the untranslated regions of Homer1 and Ccnd2 expression.

Clinical and genome-wide association analysis of chemoradiation-induced hearing loss in nasopharyngeal carcinoma - Yong-Qiao He; Lu-Ting Luo; Tong-Min Wang; Wen-Qiong Xue; Da-Wei Yang; Dan-Hua Li; Hua Diao; Ruo-Wen Xiao; Chang-Mi Deng; Wen-Li Zhang; Ying Liao; Yan-Xia Wu; et al. (Human Genetics, 2023)
Chemoradiation-induced hearing loss (CRIHL) is one of the most devasting side effects for nasopharyngeal carcinoma (NPC) patients, which seriously affects survivors’ long-term quality of life. However, few studies have comprehensively characterized the risk factors for CRIHL. In this study, we found that age at diagnosis, tumor stage, and concurrent cisplatin dose were positively associated with chemoradiation-induced hearing loss. We performed a genome-wide association study (GWAS) in 777 NPC patients and identified rs1050851 (within the exon 2 of NFKBIA ), a variant with a high deleteriousness score, to be significantly associated with hearing loss risk (HR = 5.46, 95% CI 2.93–10.18, P = 9.51 × 10 –08 ). The risk genotype of rs1050851 was associated with higher NFKBIA expression, which was correlated with lower cellular tolerance to cisplatin. According to permutation-based enrichment analysis, the variants mapping to 149 hereditary deafness genes were significantly enriched among GWAS top signals, which indicated the genetic similarity between hereditary deafness and CRIHL. Pathway analysis suggested that synaptic signaling was involved in the development of CRIHL. Additionally, the risk score integrating genetic and clinical factors can predict the risk of hearing loss with a relatively good performance in the test set. Collectively, this study shed new light on the etiology of chemoradiation-induced hearing loss, which facilitates high-risk individuals’ identification for personalized prevention and treatment.

Juvenile hormone regulates the photoperiodic plasticity of elytra coloration in the ladybird Harmonia axyridis - Jia‐Xu Li; Zhong Tian; Xing‐Feng Liu; Bei Li; Hao‐Min An; Colin S. Brent; Jia‐Lu Wang; Xiao‐Ping Wang; Wen Liu (Molecular Ecology, 2023)
Many animals, including insects, exhibit plasticity of body colour in response to environmental changes. Varied expression of carotenoids, major cuticle pigments, significantly contributes to body colour flexibility. However, the molecular mechanisms by which environmental cues regulate carotenoid expression remain largely unknown. In this study, we used the ladybird Harmonia axyridis as a model to investigate the photoperiodic‐responsive plasticity of elytra coloration and its endocrine regulation. It was found that H. axyridis females under long‐day conditions develop elytra that are much redder than those under short‐day conditions, resulting from the differential accumulation of carotenoids. Exogenous hormone application and RNAi‐mediated gene knockdown indicate that carotenoid deposition was directed through the juvenile hormone (JH) receptor‐mediated canonical pathway. Moreover, we characterized an SR‐BI/CD36 ( SCRB ) gene SCRB10 as the carotenoid transporter responding to JH signalling and regulating the elytra coloration plasticity. Taken together, we propose that JH signalling transcriptionally regulates the carotenoid transporter gene for the photoperiodic coloration plasticity of elytra in the beetles, which reveals a novel role of the endocrine system in the regulation of carotenoid‐associated animal body coloration under environmental stimuli.

The natural products discovered in marine sponge-associated microorganisms: structures, activities, and mining strategy - Peishan Li; Hongmei Lu; Yanzhu Zhang; Xuejiao Zhang; Lianliang Liu; Min Wang; Liwei Liu (Frontiers in Marine Science, 2023)
It is well known that microorganisms are abundant in sponges, which make up 50%-60% of the host biomass. Moreover, mounting evidence suggests that bacteria, fungi, and cyanobacteria, all associated with sponges, are the true creators of the bioactive compounds identified from sponges. The discovery of 774 structurally active compounds from 1998 to 2017 presents a good overview of natural product resources in sponge-associated microorganisms. During the last 5 years, many new molecules, including peptides, polyketides, alkaloids, and terpenes, have been identified from sponge-associated microorganisms through various mining strategies, exhibiting a wide range of biological activities, such as anti-microbial, anti-cancer, enzyme inhibition, and antioxidant properties. In this paper, 140 compounds produced by sponge-associated microorganisms from 2017 to 2022 are systematically discussed in terms of their structures, biological activities, and strain sources, as well as the mining strategies, which not only further updates the natural product library of sponge-associated microorganisms but also provides a new guideline for exploring the “dark matter” in sponges.

Derivation of copper water quality criteria in Bohai Bay for the protection of local aquatic life and the ecological risk assessment - Yang Li; Di Mu; Hong-Qing Wu; Hai-Jiao Liu; Yong-Hui Wang; Guo-Chen Ma; Xue-Min Duan; Jian-Jun Zhou; Chun-Ming Zhang; Xing-Hua Lu; Xian-Hua Liu; Jun Sun; et al. (Marine Pollution Bulletin, 2023)

Dynamic risk analysis of oil depot storage tank failure using a fuzzy Bayesian network model - Qing-Yun Zhou; Bei Li; Yi Lu; Jie Chen; Chi-Min Shu; Ming-shu Bi (Process Safety and Environmental Protection, 2023)

Effects and mechanisms of extremely cold environment on body response after trauma - Yu-Yuan Peng; Xiu-Min Lu; Sen Li; Can Tang; Yang Ding; Hai-Yan Wang; Ce Yang; Yong-Tang Wang (Journal of Thermal Biology, 2023)

Accurate prediction of the eating and cooking quality of rice using artificial neural networks and the texture properties of cooked rice - Fei Deng; Hui Lu; Yujie Yuan; Hong Chen; Qiuping Li; Li Wang; Youfeng Tao; Wei Zhou; Hong Cheng; Yong Chen; Xiaolong Lei; Guiyong Li; et al. (Food Chemistry, 2023)

Clonal fragmentation drives performance deterioration of epiphytic and lithophytic ferns in a karst forest - Qian Dai; Yu-Xuan Mo; Quan Chen; Liang Song; Li-Min Zhang; Gbadamassi G.O. Dossa; Hua-Zheng Lu (Flora, 2023)

Design of a highly efficient Cu-based catalyst with two functional areas: The role of Cu0 and oxygen vacancies in Fenton-like system - Cui Lai; Lu Yang; Ling Li; Dengsheng Ma; Min Cheng; Shiyu Liu; Mingming Zhang; Huchuan Yan; Chensi Tang; Zhexin Chen; Lin Tang (Chemical Engineering Journal, 2023)

LncRNA PVT1 influences breast cancer cells glycolysis through sponging miR-145-5p - Huan Qu; Xingxing Li; Fei Chen; Min Zhang; Xun Lu; Yun Gu; Mingming Lv; Cheng Lu (Genes & Genomics, 2023)
Background Long-non-coding RNA PVT1 (lncRNA PVT1) can be used as an oncogenic regulatory non-coding RNA (ncRNA) for many cancers. However, its function and mechanism in breast cancer (BRCA) are still not clearly elucidated. Objective We attempt to explain the mechanism of PVT1’s role in breast cancer from different perspectives. Methods We analyzed the expression of PVT1 and its correlation with the breast cancer related clinical data in the The Cancer Genome Atlas (TCGA) database. We used PVT1 overexpression and knockdown lentivirus to infect breast cancer MDA-MB-231 cell line for cell function verification, in vitro using CCK-8 to measure proliferation, flow cytometry to measure apoptosis, transwell test to measure invasion and migration ability, detecting cell extracellular acidification rate (ECAR) to assess glycolysis metabolism and explore the biological functions of PVT1 in breast cancer cells. Transcriptome sequencing was used to analyze the changes of related genes in cells after overexpression of PVT1. In vivo we used a xenograft model to study the effect of PVT1 on breast cancer. Results PVT1 was up-regulated in breast cancer tissues and was positively correlated with the clinical stage of breast cancer patients. Overexpression of PVT1 in vitro promoted cell proliferation, migration and invasion, and promoted tumor growth in vivo. Knockdown of PVT1 led to the opposite biological consequence. Further bioinformatics analysis showed that PVT1 changes the glycolysis metabolism of tumors through regulation of glycolysis-related genes. In addition, the expression of miR-145-5p is negatively correlated with PVT1. We consider the possibility of PVT1 promoting cell proliferation and metastasis by regulating the aerobic glucose metabolism in breast cancer cells through sponging the miR-145-5p. Conclusion Our results reveal a potential pathway for competing endogenous RNA to regulate breast cancer glucose metabolism. PVT1 regulates glycolysis related genes expression by competitively binding to endogenous miR-145-5p in breast cancer cells to change the metabolic phenotype. This may Provide new ideas for precise molecular therapy targets for breast cancer.

Changes of dissolved organic matter fractions and formation of oxidation byproducts during electrochemical treatment of landfill leachates: Development of spectroscopic indicators for process optimization - Bi-Cun Jiang; Ye-Chao Tian; Ai-Min Li; Yu-Ze Han; Ze-Tao Wu; Chang Lu; Hai-Ou Song; Rong Ji; Wen-Tao Li; Gregory V. Korshin (Water Research, 2023)

WITHDRAWN: Construction and evaluation of risk prediction model for kidney injury in patients treated with PD-1 inhibitors - Peiyu Lu; Li Tian; Aihua Wu; Hua Zhou; Min Yang (Toxicology and Applied Pharmacology, 2023)

Apoptosis-related long non-coding RNA LINC5438 of Bombyx mori promotes the proliferation of BmNPV - Peng Chen; Min Cai; Yu-Jie Feng; Cong Li; Zhan-Qi Dong; Wen-Fu Xiao; Liang Tang; Yan Zhu; Ting Tian; Bo-Yuan Deng; Min-Hui Pan; Cheng Lu (Pesticide Biochemistry and Physiology, 2023)

Disturbance and restoration of soil microbial communities after in-situ thermal desorption in a chlorinated hydrocarbon contaminated site - Jiali Shentu; Qianqian Chen; Yuxue Cui; Yangyang Wang; Li Lu; Yuyang Long; Min Zhu (Journal of Hazardous Materials, 2023)

An investigation into the modification of microwave-assisted oxidation in the macromolecular structure of coal via XRD and Raman spectroscopy - Chaoping Xu; He Li; Jiexin Lu; Yi Lu; Shiliang Shi; Qing Ye; Min Li; Zheng Wang (Fuel, 2023)

Heavy metal contamination and risk assessment in winter jujube (Ziziphus jujuba Mill. cv. Dongzao) - Min Xu; Qiusheng Chen; Xiabing Kong; Lingxi Han; Qiang Zhang; Qingjun Li; Bianqing Hao; Xubo Zhao; Lu Liu; Haoliang Wan; Jiyun Nie (Food and Chemical Toxicology, 2023)

Robust cellulose-based hydrogel marbles with excellent stability for gas sensing - Na Li; Hongying Wanyan; Shengchang Lu; He Xiao; Min Zhang; Kai Liu; Xiuliang Li; Bihui Du; Liulian Huang; Lihui Chen; Yonghao Ni; Hui Wu (Carbohydrate Polymers, 2023)

Targeting Senescent Tendon Stem/Progenitor Cells to Prevent or Treat Age-Related Tendon Disorders - Hao Wang; Guang-Chun Dai; Ying-Juan Li; Min-Hao Chen; Pan-Pan Lu; Yuan-Wei Zhang; Ming -Zhang; Mu-Min Cao; Yun-Feng Rui (Stem Cell Reviews and Reports, 2023)

Angiotensin-(1–9) prevents angiotensin II-induced endothelial apoptosis through CNPY2/PERK pathway - Chun-ling Guo; Hui-min Liu; Bao Li; Zhao-yang Lu (Apoptosis, 2023)

Research on the utilization of ultra-long carbon nanotubes in lithium-ion batteries based on an environment-friendly society - Xuanyu Yang; Ziling Xie; Xibin Lu; Min Wei; Xinxin Tan; Haihua Ling; Ying Li (Environmental Science and Pollution Research, 2023)

Economic, environmental, energy and exergy analysis and multi-objective optimization for efficient purification of a friendly gasoline additive by extractive distillation coupled with pervaporation - Yuyang Jiao; Min Yan; Xianlong Wang; Jianhui Zhong; Yusen Chen; Wenguang Zhu; Xin Li; Zhaoyou Zhu; Peizhe Cui; Yanyue Lu; Yinglong Wang (Fuel, 2023)

ZIF-8 sacrificial-templated hollow COF architectures enabled highly efficient enrichment, determination and regulation of food hazards from infant formulas - Lu Yang; Lin-Qing Nie; Jing Wang; Chun-Yang Li; Jin Wang; Jing-Min Liu; Shuo Wang (Food Chemistry, 2023)

Identification and characterization of two long-type peptidoglycan recognition proteins, PGRP-L1 and PGRP-L2, in the orange-spotted grouper, Epinephelus coioides - Jing Hou; Wei Hao; Min Chang Li; Zhen Gan; Shan Nan Chen; Yi Shan Lu; Li Qun Xia (Fish & Shellfish Immunology, 2023)

Changes of Iodine Nutritional Status in the Elderly after Replacing Iodized Salt with Non-Iodized Salt for Half a Year - Min Li; Rui Wang; Jiaxi Lu; Weidong Li; Yichun Hu; Jing Chen; Wei Ma; Lichen Yang (Biological Trace Element Research, 2023)

Comprehensive analysis and energy efficient process design for separation of four high purity components from organosilicon system - Haixia Li; Chen Li; Min Yan; Yinglong Wang; Zhaoyou Zhu; Peizhe Cui; Xin Li; Yanyue Lu (Process Safety and Environmental Protection, 2023)

Improving ACE inhibitory activity of hazelnut peptide modified by plastein: Physicochemical properties and action mechanism - Wentian Song; Junxi Fu; Qi Zeng; Hongyan Lu; Ji Wang; Li Fang; Xiaoting Liu; Weihong Min; Chunlei Liu (Food Chemistry, 2023)

Directional immobilization of D-allulose 3-epimerase using SpyTag/SpyCatcher strategy as a robust biocatalyst for synthesizing D-allulose - Xin Gao; Cancan Wei; Hongbin Qi; Chao Li; Fuping Lu; Hui-Min Qin (Food Chemistry, 2023)

Transcriptome analysis and functional gene identification reveals potential mechanisms of heat stress response of Lactiplantibacillus plantarum CGMCC8198 - Jia-Yi Da; Mao-Sheng Xi; Han-Lu Li; Min-Min Liu; Cheng-Hui Zhou; Zhong-Yuan Li; Ya-Jian Song; Sa Zhou; Tong-Cun Zhang; Xue-Gang Luo (Food Bioscience, 2023)

Probing the stability of perovskite solar cell under working condition through an ultra-thin silver electrode: Beyond the halide ion diffusion and metal diffusion - Hao Li; Zheng Yan; Min Li; Xiaoyan Wen; Shuo Deng; Sisi Liu; Wallace C.H. Choy; Lijie Li; Ming-Yu Li; Haifei Lu (Chemical Engineering Journal, 2023)

Dopaminergic Dysfunction and Glucose Metabolism Characteristics in Parkin-Induced Early-Onset Parkinson’s Disease Compared to Genetically Undetermined Early-Onset Parkinson’s Disease - Feng-Tao Liu; Jia-Ying Lu; Yi-Min Sun; Ling Li; Yu-Jie Yang; Jue Zhao; Jing-Jie Ge; Ping Wu; Jie-Hui Jiang; Jian-Jun Wu; Chuan-Tao Zuo; Jian Wang (Phenomics, 2023)

Development and application of a multiplex qPCR assay for the detection of duck circovirus, duck Tembusu virus, Muscovy duck reovirus, and new duck reovirus - Yan Wen Yin; Chenyong Xiong; Kai Chuang Shi; Shou Yu Xie; Feng Long; Jun Li; Min Zheng; Xian Kai Wei; Shuping Feng; Sujie Qu; Wenjun Lu; Hongjin Zhou; et al. (Virus Genes, 2023)

Influence of pH on bioclogging in porous media during managed aquifer recharge (MAR): Effectiveness and mechanism - Tianyuan Zheng; Min Li; Lu Xia; Xin Li; Yunhai Fang; Xilai Zheng (Journal of Contaminant Hydrology, 2023)

Preparation of Metal-Acid bifunctional catalyst Ni/ZSM-22 for palmitic acid catalytic deoxygenation - Xiaoxian Li; Min Lin; Rui Li; Qiang Lu; Mingde Yang; Yulong Wu (Fuel, 2023)

Catalytic hydroconversion of an organic waster oil to cyclanes over Ni/SiO2 - Li Li; Xian-Yong Wei; Chang-Wang Shao; Zhuang Li; Jia-Hao Li; Zi-Chun Fan; Kun-Lang Lu; Fang-Jing Liu; Qian-Qian Kong; Ji Zhao; Zhong-Qiu Liu; Zhi-Min Zong (Fuel, 2023)

Dynamic processes in conjunction with microbial response to unveil the attenuation mechanisms of tris (2-chloroethyl) phosphate (TCEP) in non-sanitary landfill soils - Min Zhu; Lisha He; Jiayi Liu; Yuyang Long; Jiali Shentu; Li Lu; Dongsheng Shen (Environmental Pollution, 2023)

In vitro toxicity assessment of haloacetamides via a toxicogenomics assay - Dong Li; Wen Cheng; Jiehui Ren; Lu Qin; Xing Zheng; Tian Wan; Min Wang (Environmental Toxicology and Pharmacology, 2023)

Structural performance of composite connections with a uniaxial symmetric steel-beam section - Ying-lu Xu; Yao-xuan Su; Yong-fang Shang; Zi-long Liu; Li-min Tian (Engineering Structures, 2023)

Power laws for accurate determination of landslide volume based on high-resolution LiDAR data - Lu-Yu Ju; Li-Min Zhang; Te Xiao (Engineering Geology, 2023)

Hypervalent potassium xanthate modified SnO2 for highly efficient perovskite solar modules - Pin Lv; Yufei Yang; Neng Li; Yuxi Zhang; Min Hu; Bo Huang; Yanqing Zhu; Yulong Wang; Junye Pan; Shifeng Wang; Bo Zhang; Fuzhi Huang; et al. (Chemical Engineering Journal, 2023)

IL-18BP Alleviates Anxiety-Like Behavior Induced by Traumatic Stress via Inhibition of the IL-18R-NLRP3 Signaling Pathway in a Mouse Model of Hemorrhagic Shock and Resuscitation - Li-Min Zhang; Dong-Xue Zhang; Rong-Xin Song; Jin-Meng Lv; Lu-Ying Wang; Zhi-You Wu; Hui-Tao Miao; Yan-Bo Zhou; Wei Zhang; Yue Xin; Yan Li (Molecular Neurobiology, 2023)

Correction to: Behavioral and brain functional characteristics of children with attention-defcit/hyperactivity disorder and anxiety trait - Zhao-Min Wu; Peng Wang; Juan Liu; Lu Liu; Xiao-Lan Cao; Li Sun; Qing-Jiu Cao; Li Yang; Yu-Feng Wang; Bin-Rang Yang (Brain Imaging and Behavior, 2022)

Behavioral and brain functional characteristics of children with Attention-Deficit/Hyperactivity disorder and anxiety trait - Zhao-Min Wu; Peng Wang; Juan Liu; Lu Liu; Xiao-Lan Cao; Li Sun; Qing-Jiu Cao; Li Yang; Yu-Feng Wang; Bin-Rang Yang (Brain Imaging and Behavior, 2022)

Pollution characteristics and risk assessment of heavy metals in surface water of Manas River, Xinjiang, China - Shaohua He; Bingbing Tian; Fengyu Liu; Junqi Wang; Shuyi Gong; Jianjiang Lu; Min Li (Arabian Journal of Geosciences, 2022)

Estimation of the most suitable nitrogen concentration for sporocarp formation in Laccaria japonica colonizing Pinus densiflora seedlings through in vitro mycelial culture - Shijie Zhang; Momi Tsuruta; Chaofeng Li; Lu-Min Vaario; Yan Xia; Norihisa Matsushita; Hiroyuki Kurokochi; Ruiyang Xu; Jiali Li; Chunlan Lian (Mycorrhiza, 2022)

Complete genome analysis of a novel chuvirus from a southern green stink bug (Nezara viridula) - Peng-Peng Ren; Zhuang-Xin Ye; Sai-Nan Wang; Jun-Min Li; Jian-Ping Chen; Chuan-Xi Zhang; Jia-Bao Lu (Archives of Virology, 2022)

Identification and expression analysis of the grape pentatricopeptide repeat (PPR) gene family in abiotic stress - Lili Che; Shixiong Lu; Guoping Liang; Huimin Gou; Min Li; Baihong Chen; Juan Mao (Physiology and Molecular Biology of Plants, 2022)

Determination of extractable and non-extractable florfenicol residues as florfenicol amine in eggs by UPLC-MS/MS - Xia Li; Yu Zhang; Qifan Sun; Min Ding; Zengmei Li; Hui Yue; Ligang Deng; Lu Chen (Food Additives & Contaminants: Part A, 2022)

The Effects of Acidic Compost Tea on Activation of Phosphorus, Fe, Zn, and Mn in Calcareous Soil and Cotton (Gossypium hirsutum L.) Growth in Xinjiang, China - Tong Luo; Weidan Lu; Lili Chen; Tao Min; Sibo Ru; Changzhou Wei; Junhua Li (Journal of Soil Science and Plant Nutrition, 2022)

Instantaneous discharge characteristics and its methane ignition mechanism of coal mine rock damage - Min Li; Huan Lv; Yi Lu; Deming Wang; Shiliang Shi; Runqiu Li (Environmental Science and Pollution Research, 2022)

Interdecadal change in the influence of El Niño in the developing stage on the central China summer precipitation - Lin Chen; Gen Li; Shang-Min Long; Chujie Gao; Zhiyuan Zhang; Bo Lu (Climate Dynamics, 2022)

Alterations to cognitive abilities and functional networks in rats post broad-band intense noise exposure - Xiao-Min Xu; Yu-Qun Zhang; Feng-Chao Zang; Chun-Qiang Lu; Li-Jie Liu; Jian Wang; Richard Salvi; Yu-Chen Chen; Gao-Jun Teng (Brain Imaging and Behavior, 2022)

Global regulatory factor VeA upregulates the production of antitumor substances in endophytic Fusarium solani - Lu Cai; Jiankang Wang; Yongjie Li; Min Qin; Xuemin Yin; Zhangjiang He; Jichuan Kang (Antonie van Leeuwenhoek, 2022)

Pharmacokinetics of benapenem for injection in subjects with mild to moderate renal impairment - Haijing Yang; Min Zhang; Yuancheng Chen; Hong Ren; Hong Zhang; Chen Yu; Jianda Lu; Li You; Jicheng Yu; Hong Liang; Cuilan Xiao; Zishuang He; et al. (European Journal of Clinical Pharmacology, 2022)

Microbial composition and nitrogen removal pathways in a novel sequencing batch reactor integrated with semi-fixed biofilm carrier: evidence from a pilot study for low- and high-strength sewage treatment - Peng-fei Chen; Rui-jian Zhang; Zhi-li Du; Guang-hua Wang; Hao-tao Dong; Bin Cui; Ru-pei Fan; Lu-xin Li; Qian-bin Wang; Ying-shi Liu; Zhi-min Sun (Environmental Science and Pollution Research, 2022)

Effects of Late Pleistocene Climatic Fluctuations on the Phylogeographic and Demographic History of Japanese Scad (Decapterus maruadsi) - Qing-Hua Wang; Ren-Xie Wu; Zhong-Lu Li; Su-Fang Niu; Yun Zhai; Min Huang; Biao Li (Frontiers in Marine Science, 2022)
The Late Pleistocene-Holocene climate fluctuations have greatly influenced the phylogeographic structure and historical dynamics of many marine organisms in the western Pacific marginal seas. Here, we investigated the impact of Pleistocene glacial-interglacial cycles on the phylogeographic structure and demographic dynamics of Decapterus maruadsi , an economically important fish along the coast of the East China Sea (ECS) and northern South China Sea (NSCS). We obtained 430 concatenated sequences (Cyt b + control region, 1548–1554 bp) of D. maruadsi , including 246 newly sampled from the ECS and 184 previously determined from the NSCS. Genetic structure and phylogenetic analysis demonstrated a lack of significant population structure among 16 populations. Moreover, there was no significant differentiation among populations from Chinese coastal waters and northern Vietnam. Neutrality tests, unimodal mismatch distributions, Bayesian skyline plots, and the star-like haplotype networks all indicated a recent demographic expansion for D. maruadsi population during the Late Pleistocene-Holocene, explaining the low genetic diversity in D. maruadsi along the southeast coast of China. Notably, phylogenetic analyses and net genetic distances based on Cyt b jointly confirmed that 57 Cyt b haplotypes identified as D. maruadsi from the previously defined Sundaland-Rosario-Ranong clade actually represented D. russelli . These results not only reveal the complex effects of Pleistocene-Holocene climate fluctuations on the phylogeographic structure and demographic history of D. maruadsi but also provide useful genetic information for the management of genetic resources.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Effect of Culture Period and Stocking Density on Input Demand and Scale Economies of Milkfish (Chanos chanos) Polycultures with White Shrimp (Penaeus indicus) - Wei-Tse Pai; Christian Schafferer; Jie-Min Lee; Li-Ming Ho; Yung-Hsiang Lu; Han-Chung Yang; Chun-Yuan Yeh (Fishes, 2022)
Milkfish, Chanos chanos, is one of the major inland cultured fish species in Taiwan. Variations in land resources and climate have led to the application of two distinct culture practices of milkfish polycultures with white shrimp, Penaeus indicus. This study applies a translog cost function model to analyze the production scale economy and input demand price elasticity of four milkfish polyculture systems with two different culture periods (OWC and NOWC) and two different white shrimp–milkfish fry stocking ratios (low SMR: 10–55 fry/ha; high SMR: 56–100 fry/ha). The findings show that the four milkfish polyculture systems require different operational adjustments to increase production while reducing the average culture cost. More specifically, overwinter cultures (OWC) have economies of scale. Farmers may reduce the average cost by expanding the production scale. Non-overwinter polycultures (NOWC) with high SMR are at the stage of decreasing return to scale, meaning that gains in output of milkfish cannot reduce the average cost. In terms of input factor use, farmers of OWC systems with high SMR are sensitive to fluctuations in the fry price since fry constitutes the input factor exhibiting the highest own-price elasticity. Moreover, fry and feed of OWC households with high SMR have high levels of substitutability, whereas fry and other input exhibit substitutability in OWC systems with low SMR. In NOWC farming households with high SMR, fry and capital have substitutability. It is thus recommended to modify the input factor use according to the culture mode and the white shrimp–milkfish stocking density ratio. Moreover, the study found that NOWCs have considerably higher SMR than OWCs, which may lead to a deterioration of the water quality in NOWC fishponds and lower survival rates. It is thus recommended to reduce the SMR to 31:1 to achieve economies of scale in production and increase the survival rate of milkfish and white shrimp.

Simultaneous determination of praziquantel and its main metabolites in the tissues of black goats and their residue depletion - Tong-Yan Ding; Xiao-Gui Shu; Ren-Ping Xiong; Jing-Li Qiu; Lu Li; Li-Min He (Food Additives & Contaminants: Part A, 2022)

Probabilistic risk analysis for coal mine gas overrun based on FAHP and BN: a case study - Shan He; Yi Lu; Min Li (Environmental Science and Pollution Research, 2022)

Complete genome analysis of a novel picorna-like virus from a ladybird beetle (Cheilomenes sexmaculata) - Yu-Juan He; Zhuang-Xin Ye; Jian-Ping Chen; Chuan-Xi Zhang; Gang Lu; Jun-Min Li (Archives of Virology, 2022)

Complete genome sequence of a novel arlivirus from a yellow spotted stink bug (Erthesina fullo (Thunberg, 1783)) - Zhuang-Xin Ye; Shao-Min Wang; Gang Lu; Jian-Ping Chen; Chuan-Xi Zhang; Liao-Yuan Xu; Jun-Min Li (Archives of Virology, 2022)

Cancer metabolism and tumor microenvironment: fostering each other? - Yiyuan Yuan; Huimin Li; Wang Pu; Leilei Chen; Dong Guo; Hongfei Jiang; Bo He; Siyuan Qin; Kui Wang; Na Li; Jingwei Feng; Jing Wen; et al. (Science China Life Sciences, 2022)

Comparative Transcriptome Analysis of Spleen Reveals Potential Regulation of Genes and Immune Pathways Following Administration of Aeromonas salmonicida subsp. masoucida Vaccine in Atlantic Salmon (Salmo salar) - Qiang Fu; Yuqing Li; Hao Zhang; Min Cao; Lu Zhang; Chengbin Gao; Xin Cai; Defeng Chen; Ziying Yang; Jie Li; Ning Yang; Chao Li (Marine Biotechnology, 2022)

Prediction and validation of cross-protective candidate antigen of Hyalomma asiaticum cathepsin L between H. asiaticum and H. anatolicum - Ruiqi Song; Xuejie Zhai; Xinli Fan; Yongchang Li; Huercha; Ting Ge; Caishan Li; Min Li; Wenwen He; Huizhen Zheng; Lu Gan; Yang Zhang; et al. (Experimental and Applied Acarology, 2022)

Dose-effect and structure-activity relationships of haloquinoline toxicity towards Vibrio fischeri - Min Li; Yayao Wang; Lu Ma; Xingfu Yan; Qian Lei (Environmental Science and Pollution Research, 2022)

Study on metal binding capacity of the freshwater crab Sinopotamon henanense’s recombinant copper specific binding metallothionein expressed in Escherichia coli - Lu Wang; Hui Zhen Yang; Wen Li Ma; Chien Min Chen; Lan Wang (Ecotoxicology, 2022)

The specialized mitotic behavior of human embryonic stem cells - Rui Lyu; Xuemei Wu; Nan Ma; Difei Wang; Shuang Sun; Youguang Luo; Jun Zhou; Xinyi Lu; Min Liu; Dengwen Li (Cell and Tissue Research, 2022)

Complete genome analysis of a nege-like virus in aphids (Astegopteryx formosana) - Xiao-Di Zhang; Gang Lu; Zhuang-Xin Ye; Jian-Ping Chen; Chuan-Xi Zhang; Jun-Min Li (Archives of Virology, 2022)

The chemical profile and biological activity of different extracts of Sapindus mukorossi Gaertn. against Cutibacterium acnes - Min-Ping Wei; Jin-Dan Qiu; Lu Li; Yun-Fei Xie; Ya-Hui Guo; Hang Yu; Yu-Liang Cheng; He Qian; Wei-Rong Yao (Natural Product Research, 2021)

Leaching alleviates phenol-mediated root rot in Panax notoginseng by modifying the soil microbiota - Yijie Zhang; Tianyao Li; Chen Ye; Renchuang Lu; Yixiang Liu; Huichuan Huang; Xiahong He; Min Yang; Shusheng Zhu (Plant and Soil, 2021)

Dynamic evolution of eukaryotic mitochondrial and nuclear genomes: a case study in the gourmet pine mushroom Tricholoma matsutake - Shu Zhang; Xue Bai; Li‐Yuan Ren; Hui‐Hui Sun; Hui‐Ping Tang; Lu‐Min Vaario; Jianping Xu; Yong‐Jie Zhang (Environmental Microbiology, 2021)
Summary Fungi, as eukaryotic organisms, contain two genomes, the mitochondrial genome and the nuclear genome, in their cells. How the two genomes evolve and correlate to each other is debated. Herein, taking the gourmet pine mushroom Tricholoma matsutake as an example, we performed comparative mitogenomic analysis using samples collected from diverse locations and compared the evolution of the two genomes. The T. matsutake mitogenome encodes 49 genes and is rich of repetitive and non‐coding DNAs. Six genes were invaded by up to 11 group I introns, with one cox1 intron cox1P372 showing presence/absence dynamics among different samples. Bioinformatic analyses suggested limited or no evidence of mitochondrial heteroplasmy. Interestingly, hundreds of mitochondrial DNA fragments were found in the nuclear genome, with several larger than 500 nt confirmed by PCR assays and read count comparisons, indicating clear evidence of transfer of mitochondrial DNA into the nuclear genome. Nuclear DNA of T. matsutake showed a higher mutation rate than mitochondrial DNA. Furthermore, we found evidence of incongruence between phylogenetic trees derived from mitogenome and nuclear DNA sequences. Together, our results reveal the dynamic genome evolution of the gourmet pine mushroom.

Induced production of a new polyketide in Penicillium sp. HS-11 by chemical epigenetic manipulation - You-Min Ying; Ling Li; Hang-Fei Yu; Yi-Lian Xu; Lu Huang; Wei Mao; Cui-Ping Tong; Zhi-Dong Zhang; Zha-Jun Zhan; Yun Zhang (Natural Product Research, 2021)

Retraction Note to: CiRS-126 inhibits proliferation of ovarian granulosa cells through targeting the miR-21-PDCD4-ROS axis in a polycystic ovarian syndrome model - Jiafeng Lu; Ying Xue; Yuhang Wang; Yang Ding; Qinyan Zou; Min Pan; Longwei Qiao; Chunhua Zhang; Qinyu Ge; Ting Wang; Hong Li (Cell and Tissue Research, 2021)

Interactive effects of nutrient availability, fluctuating supply, and plant parasitism on the post-invasion success of Bidens pilosa - Fang-Lei Gao; Qiao-Sheng He; Ru-Qian Xie; Jia-Hui Hou; Chen-Lu Shi; Jun-Min Li; Fei-Hai Yu (Biological Invasions, 2021)

Influence of elevation on bioregionalisation: A case study of the Sino‐Himalayan flora - Yun Liu; Jian‐Fei Ye; Hai‐Hua Hu; Dan‐Xiao Peng; Li‐Na Zhao; Li‐Min Lu; Wajid Zaman; Zhi‐Duan Chen (Journal of Biogeography, 2021)
Aim Elevation is an important factor that influences bioregionalisation in mountainous areas, but its effects are not well known. Taking the Sino‐Himalayan flora as a case, we aimed to test the effect of elevation on bioregionalisation and provide a regionalisation scheme of the Sino‐Himalayan flora. Location The Sino‐Himalaya (East Himalaya, the Hengduan Mountains and the Yunnan Plateau in China). Taxon Angiosperms. Methods We compiled distribution data and elevation ranges of angiosperms in the Sino‐Himalaya and adjacent areas and reconstructed a species‐level phylogenetic tree of 19,313 angiosperm species. The area was divided into 398 grid cells, each 1 × 1°. Nine datasets of different elevation ranges were then used to delineate the flora of the Sino‐Himalaya and adjacent areas using the phylogenetic dissimilarity approach. Results A comparison of nine regionalisation schemes of the Sino‐Himalayan flora based on different elevation range datasets revealed that more than half of grid cells were allocated to more than one subregion. Most of these grid cells were located in areas with a wide range of elevation and/or at the boundaries between subregions. After revising the subregion allocations of eight shifting grid cells, we generated a phylogeny‐ and elevation‐based regionalisation scheme of three regions, comprising eight subregions, for the Sino‐Himalayan flora. Main conclusions By integrating phylogenetic and elevational information, the Sino‐Himalaya can be divided into three floristic regions: the Yunnan Plateau region, the Hengduan Mountains region and the East Himalaya region. Our study provides novel insights into the regionalisation of the flora and highlights the importance of incorporating elevation data in the bioregionalisation of areas with a broad elevational range.

OsGSTU6 Contributes to Cadmium Stress Tolerance in Rice by Involving in Intracellular ROS Homeostasis - Xiu-Qing Jing; Meng-Ru Zhou; Xiu-Min Nie; Lu Zhang; Peng-Tao Shi; Abdullah Shalmani; Hai Miao; Wen-Qiang Li; Wen-Ting Liu; Kun-Ming Chen (Journal of Plant Growth Regulation, 2021)

First detection and complete genome analysis of the Lyon IARC polyomavirus in China from samples of diarrheic cats - Yuying Li; Haixin Huang; Tian Lan; Wei Wang; Jie Zhang; Min Zheng; Liang Cao; Wenchao Sun; Huijun Lu (Virus Genes, 2021)

Correction to: Exploring the Genetic Association of the ABAT Gene with Alzheimer’s Disease - Quanzhen Zheng; Rui Bi; Min Xu; Deng-Feng Zhang; Li-Wen Tan; Ya-Ping Lu; Yong-Gang Yao (Molecular Neurobiology, 2021)

Exploring the Genetic Association of the ABAT Gene with Alzheimer’s Disease - Quanzhen Zheng; Rui Bi; Min Xu; Deng-Feng Zhang; Li-Wen Tan; Ya-Ping Lu; Yong-Gang Yao (Molecular Neurobiology, 2021)

An NGO disaster relief network for small and medium-scale natural hazards in China - Yi Lu; Chengyan Zhan; Rui Li; Min Su (Natural Hazards, 2021)

Catalyst-free visible-light induced synthesis of nitrogen- and oxygen-containing heterocycles from 1,3-diketones - Lu Chen; Zhenyuan lin; Xuefang Zhang; Leshi Tan; Min Zhang; Yibiao Li (Environmental Chemistry Letters, 2021)

Treatment via the Living Machine system of blackwater collected from septic tanks: effect of different plant groups in the systems - Li Tian; Lu Jinzhong; Yang Shenglin; Ye Zhourong; Zhao Min; Kong Hainan; Zheng Xiangyong (Environment, Development and Sustainability, 2021)

Recent progress on bio-succinic acid production from lignocellulosic biomass - Jiasheng Lu; Jiawen Li; Hao Gao; Dawei Zhou; Huixin Xu; Yuexin Cong; Wenming Zhang; Fengxue Xin; Min Jiang (World Journal of Microbiology and Biotechnology, 2021)

JAB1 promotes palmitate-induced insulin resistance via ERK pathway in hepatocytes - Yun Zhao; Suxian Ma; Xingna Hu; Min Feng; Rong Xiang; Min Li; Chenxiao Liu; Ting Lu; Aijie Huang; Jiaqi Chen; Mian Wu; Honghong Lu (Journal of Physiology and Biochemistry, 2020)

A Comparative Study of Associated Microbiota Between Pig Farm and Pig Slaughterhouse in Guangdong, China - Jian-Yong Wu; Yan-Shan Zhu; Cheng Guo; Yao Xia; Zhong-Min Guo; Qian-Lin Li; Jia-Hai Lu (Current Microbiology, 2020)

Comparison of mRNA Expression of P2X Receptor Subtypes in Different Arterial Tissues of Rats - Ling-Zhi Li; Li-Hui Yue; Zhi-Min Zhang; Jing Zhao; Lei-Ming Ren; Hong-Jie Wang; Lu Li (Biochemical Genetics, 2020)

Noise does not equal bias in assessing the evolutionary history of the angiosperm flora of China: A response to Qian (2019) - Li‐Min Lu; Hai‐Hua Hu; Dan‐Xiao Peng; Bing Liu; Jian‐Fei Ye; Tuo Yang; Hong‐Lei Li; Miao Sun; Stephen A. Smith; Pamela S. Soltis; Douglas E. Soltis; Zhi‐Duan Chen (Journal of Biogeography, 2020)
In response to our paper on the evolutionary history of the Chinese flora, Qian suggests that certain features of the divergence time estimation employed might have led to biased conclusions in Lu et al (2018). Here, we consider Qian's specific criticisms, explore the extent of uncertainty in the data and demonstrate that (i) no systematic bias toward dates that are too young or too old is detected in Lu et al.; (ii) constraint of the crown age of angiosperms does not bias the generic ages estimated by Lu et al.; and (iii) ages derived from the Chinese regional phylogeny do not bias the conclusions reported by Lu et al. All these analyses confirm that the conclusions reported previously are robust. We argue that, like many large‐scale biodiversity analyses, sources of noise in divergence time estimation are to be expected, but these should not be confused with bias.

OP16 induces deadly autophagy and apoptosis of cells by inhibiting Akt in esophageal squamous cell carcinoma - Guiqin Hou; Ang Jia; Li Yang; Yu Zhao; Yi Hu; Wuduo Zhao; Wen Zhao; Hong-Min Liu; Zhaoming Lu (Molecular and Cellular Biochemistry, 2020)

An Overview of the Expert Consensus on the Prevention and Treatment of Gaming Disorder in China (2019 Edition) - Yu-Tao Xiang; Yu Jin; Ling Zhang; Lu Li; Gabor S. Ungvari; Chee H. Ng; Min Zhao; Wei Hao (Neuroscience Bulletin, 2020)

Effects of carbendazim on catalase activity and related mechanism - Guangqiu Lu; Wei Tan; Guizhen Li; Min Yang; Hongbin Wang (Environmental Science and Pollution Research, 2020)

RETRACTED ARTICLE: CiRS-126 inhibits proliferation of ovarian granulosa cells through targeting the miR-21-PDCD4-ROS axis in a polycystic ovarian syndrome model - Jiafeng Lu; Ying Xue; Yuhang Wang; Yang Ding; Qinyan Zou; Min Pan; Longwei Qiao; Chunhua Zhang; Qinyu Ge; Ting Wang; Hong Li (Cell and Tissue Research, 2020)

Rapid detection of Anguina agrostis by loop-mediated isothermal amplification - Lu-zhen Yu; Shao-yi Song; Cui Yu; Bin-bin Jiao; Yi-min Tian; You-jun Li (European Journal of Plant Pathology, 2020)

Identification of wheat (Triticum aestivum L.) genotypes for food safety on two different cadmium contaminated soils - Min Lu; Xuerui Cao; Jianqing Pan; Tingqiang Li; Muhammad Bilal Khan; Hanumanth Kumar Gurajala; Zhenli He; Xiaoe Yang (Environmental Science and Pollution Research, 2020)

Developing stripe rust resistant wheat (Triticum aestivum L.) lines with gene pyramiding strategy and marker-assisted selection - Rong Liu; Jing Lu; Min Zhou; Shigang Zheng; Zehou Liu; Chihong Zhang; Mei Du; Minxiu Wang; Yunfang Li; Yu Wu; Lei Zhang (Genetic Resources and Crop Evolution, 2020)

Characterization and diagnostic marker development for Yr28-rga1 conferring stripe rust resistance in wheat - Shigang Zheng; Yu Wu; Min Zhou; Lian Zeng; Rong Liu; Yunfang Li; Zehou Liu; Chihong Zhang; Lu Lu; Lei Zhang (European Journal of Plant Pathology, 2020)

PEG-conjugated triacontanol micelles as docetaxel delivery systems for enhanced anti-cancer efficacy - Xiaoyu Lu; Min Fang; Yue Yang; Yu Dai; Jiaqiu Xu; Di Zhao; Yang Lu; Xijing Chen; Shan Lu; Ning Li (Drug Delivery and Translational Research, 2020)

Evidence for the paternal mitochondrial DNA in the crucian carp-like fish lineage with hybrid origin - Shi Wang; Ni Jiao; Lu Zhao; Meiwen Zhang; Pei Zhou; Xuexue Huang; Fangzhou Hu; Conghui Yang; Yuqin Shu; Wuhui Li; Chun Zhang; Min Tao; et al. (Science China Life Sciences, 2020)

Arundo donax L. stem-derived biochar increases As and Sb toxicities from nonferrous metal mine tailings - Jihai Gu; Jun Yao; Gyozo Jordan; Beenish Roha; Ning Min; Hao Li; Chao Lu (Environmental Science and Pollution Research, 2020)

Differential expression of activin β A and β B genes in female allotriploid and diploid red crucian carp Carassius auratus red var - Min Tao; Hong Hu; Lu Huang; Shengnan Li; Liujiao Yuan; Tian Zhou; Can Song; Rurong Zhao; Shaojun Liu (Journal of Fish Biology, 2019)
activin β A and β B from diploid and allotriploid crucian carp were cloned.The differential expression of activin β A and β B genes in female allotriploid and diploid red crucian carp Carassius auratus red var. were studied and found to be expressed in all the tested tissues; particularly, the expression of activin β A and β B was elevated in the ovaries of allotriploids and differential expression in pituitaries during the non‐breeding season and the breeding season period. The immunohistochemistry indicated that the abnormal triploid ovaries were dominated by small oogonium‐like cells with dense signals and that the elevated expression of activin β A and β B in the ovaries of allotriploids may be related to allotriploid sterility.

Expression of AHI1 Rescues Amyloidogenic Pathology in Alzheimer’s Disease Model Cells - Lai-Lei Ting; Hsien-Tsung Lu; Shu-Fen Yen; Thi Huong Ngo; Fang-Yu Tu; I-Shih Tsai; Yi-Hua Tsai; Fu-Yen Chang; Xiao-Jiang Li; Shihua Li; Ching-Kuo Lee; Shu-Huei Kao; et al. (Molecular Neurobiology, 2019)

Microencapsulated β-carotene preparation using different drying treatments - Xiang-yu Li; Mian-bin Wu; Min Xiao; Shu-huan Lu; Zhi-ming Wang; Jian-ming Yao; Li-rong Yang (Journal of Zhejiang University-SCIENCE B, 2019)

The dislocation properties of B2-AlPr in {110} plane - ShaoRong Li; ShuGang Li; Min Yan; Hui Lu; HaiFei Lin; HaiQing Shuang (Physics and Chemistry of Minerals, 2019)

Endoscopic ultrasonography is useful in the diagnosis and treatment of rectal neuroendocrine neoplasms: a case series - Qing Gu; Yi-ming Lin; Li Cen; Min Xu; Hong-zhang Li; Xian-chu Lin; Chao Lu (Journal of Zhejiang University-SCIENCE B, 2019)

The clinical and prognostic significance of paraoxonase-2 in gastric cancer patients: immunohistochemical analysis - Xiaohua Wang; Guifang Xu; Jingyuan Zhang; Shuaiyu Wang; Min Ji; Lei Mo; Mengxia Zhu; Jun Li; Guoren Zhou; Jianwei Lu; Cheng Chen (Human Cell, 2019)

African Orphan Crops Consortium (AOCC): status of developing genomic resources for African orphan crops - Prasad S. Hendre; Samuel Muthemba; Robert Kariba; Alice Muchugi; Yuan Fu; Yue Chang; Bo Song; Huan Liu; Min Liu; Xuezhu Liao; Sunil Kumar Sahu; Sibo Wang; et al. (Planta, 2019)

Synthesis and fungicidal activity of 1,3,4-oxadiazol-2-yl thioether derivatives containing a phenazine-1-carboxylic acid scaffold - Lu Xingliang; Zhu Xiang; Zhang Min; Wu Qinglai; Zhou Xudong; Li Junkai (Natural Product Research, 2019)

CTHRC1 promotes M2-like macrophage recruitment and myometrial invasion in endometrial carcinoma by integrin-Akt signaling pathway - Lu-Ying Li; Ke-Min Yin; Yi-Han Bai; Zhi-Gang Zhang; Wen Di; Shu Zhang (Clinical & Experimental Metastasis, 2019)

12-h abstinence-induced functional connectivity density changes and craving in young smokers: a resting-state study - Shuzhi Zhao; Yangding Li; Min Li; Ruonan Wang; Yanzhi Bi; Yajuan Zhang; Xiaoqi Lu; Dahua Yu; Likun Yang; Kai Yuan (Brain Imaging and Behavior, 2019)

Proteomics analysis of HSV-1-induced alterations in mouse brain microvascular endothelial cells - Hui Liu; Chu-Xin Huang; Qiang He; Dong Li; Min-Hua Luo; Fei Zhao; Wei Lu (Journal of NeuroVirology, 2019)

Shipborne gravimetry in the Baltic Sea: data processing strategies, crucial findings and preliminary geoid determination tests - Biao Lu; Franz Barthelmes; Min Li; Christoph Förste; Elmas Sinem Ince; Svetozar Petrovic; Frank Flechtner; Joachim Schwabe; Zhicai Luo; Bo Zhong; Kaifei He (Journal of Geodesy, 2019)

Correction to: Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Dual-Ligand Modification of PEGylated Liposomes Used for Targeted Doxorubicin Delivery to Enhance Anticancer Efficacy - Cong Li; Chaoyang Lai; Qiujun Qiu; Xiang Luo; Ling Hu; Huangliang Zheng; Yi Lu; Min Liu; Hongxia Zhang; Xinrong Liu; Yihui Deng; Yanzhi Song (AAPS PharmSciTech, 2019)

Characterization of the complete mitochondrial genome of an endangered fish Semilabeo obscurus (Cyprinidae; Labeoninae; Semilabeo) - Wei Wang; Shikai Li; Ting Liu; Xue Wang; Sheng Zeng; Wenwu Min; Lu Zhou (Conservation Genetics Resources, 2019)

Distribution of Black Carbon in Topsoils of the Northeastern Qinghai-Tibet Plateau Under Natural and Anthropogenic Influences - Xiuyun Min; Jun Wu; Jian Lu; Xiaohu Wen; Chunliang Gao; Leiming Li (Archives of Environmental Contamination and Toxicology, 2019)

In Vitro Susceptibility of Berberine Combined with Antifungal Agents Against the Yeast Form of Talaromyces marneffei - Hong Luo; Kai-su Pan; Xiao-lu Luo; Dong-yan Zheng; Alex Andrianopoulos; Le-min Wen; Yan-qing Zheng; Jing Guo; Chun-yang Huang; Xiu-ying Li; Rong Hu; Yu-jiao Li; et al. (Mycopathologia, 2019)

Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Multi-GNSS precise orbit positioning for airborne gravimetry over Antarctica - Min Li; Tianhe Xu; Biao Lu; Kaifei He (GPS Solutions, 2019)

A review of the ethnopharmacology, phytochemistry, and pharmacology of Changium smyrnioides Wolff - Lu-Jing Lei; Wen-Le Wang; Jie Wang; Li-juan Lv; Min-Hui Li (Journal of Natural Medicines, 2019)

Evaluation of matrix-assisted laser desorption/ionization time-of-flight mass spectrometry for identifying Burkholderia pseudomallei and Burkholderia thailandensis isolates - Jin Li; Weiwei Hu; Fengling Zhang; Min Li; Chenglong Rao; Weiping Lu (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Dynamics of nitrogen, phosphorus, and organic pollutant losses from a small watershed in the drinking-water source protection area in Guiyang City of Southern China - Zhen Hong Wang; Xiao Lu Yin; Li Wan; Chan Min Xu; Meng Jiao Zhang (Environmental Science and Pollution Research, 2019)

Insights into the role of extracellular polymeric substances in Zn2+ adsorption in different biological sludge systems - Yu-Xia Song; Cheng-Hai Lu; Peng Liu; Xi-Lin Chai; Xi Chen; Xiao-Bo Min; Chong-Jian Tang; Li-Yuan Chai (Environmental Science and Pollution Research, 2018)

Novel Self-Assembled Ibrutinib-Phospholipid Complex for Potently Peroral Delivery of Poorly Soluble Drugs with pH-Dependent Solubility - Qiujun Qiu; Mei Lu; Cong Li; Xiang Luo; Xinrong Liu; Ling Hu; Mingqi Liu; Huangliang Zheng; Hongxia Zhang; Min Liu; Chaoyang Lai; Yanzhi Song; et al. (AAPS PharmSciTech, 2018)

MLKL mediates apoptosis via a mutual regulation with PERK/eIF2α pathway in response to reactive oxygen species generation - Wen-Xiang Cao; Ting Li; Zheng-Hai Tang; Le-Le Zhang; Zhao-Yu Wang; Xia Guo; Min-Xia Su; Xiuping Chen; Jin-Jian Lu (Apoptosis, 2018)

Synthesis of NSAIDs–Se derivatives as potent anticancer agents - lei Liu; Shaolei Li; Xiaolong Li; Min Zhong; Yin Lu; Yang Jiajie; Zhang Yongmin; Xianran He (Medicinal Chemistry Research, 2018)

Identification of Neoscytalidium dimidiatum causing canker disease of pitaya in Hainan, China - Min Xu; Yun Peng; Zhao Qi; Zhen Yan; Lu Yang; Meng-Die He; Qing-Xiu Li; Cheng-Li Liu; Yun-Ze Ruan; Shuang-Shuang Wei; Jun Xie; You-Quan Xia; et al. (Australasian Plant Pathology, 2018)

Intra‐specific relatedness, spatial clustering and reduced demographic performance in tropical rainforest trees - Xiaona Shao; Calum Brown; Samantha J. Worthy; Lu Liu; Min Cao; Qiaoming Li; Luxiang Lin; Nathan G. Swenson (Ecology Letters, 2018)
Intra‐specific negative density dependence promotes species coexistence by regulating population sizes. Patterns consistent with such density dependence are frequently reported in diverse tropical tree communities. Empirical evidence demonstrating whether intra‐specific variation is related to these patterns, however, is lacking. The present study addresses this important knowledge gap by genotyping all individuals of a tropical tree in a long‐term forest dynamics plot in tropical China. We show that related individuals are often spatially clustered, but having closely related neighbours reduces the growth performance of focal trees. We infer from the evidence that dispersal limitation and negative density dependence are operating simultaneously to impact the spatial distributions of genotypes in a natural population. Furthermore, dispersal limitation decreases local intra‐specific genetic diversity and increases negative density dependence thereby promoting niche differences and species coexistence as predicted by theory.

Population pharmacokinetics of vancomycin and AUC-guided dosing in Chinese neonates and young infants - Yewei Chen; Dan Wu; Min Dong; Yiqing Zhu; Jinmiao Lu; Xiaoxia Li; Chao Chen; Zhiping Li (European Journal of Clinical Pharmacology, 2018)

Robust adaptive filter for shipborne kinematic positioning and velocity determination during the Baltic Sea experiment - Min Li; Kaifei He; Tianhe Xu; Biao Lu (GPS Solutions, 2018)

Isolation and identification of bovine nasopharyngeal mucosal epithelial cells and establishment of cell models of acute infection by foot-and-mouth disease virus - Wan-fu Bai; Lu Li; Ting Zhang; Xiao-hu Su; Yong-wei Wang; Bing-wu Zhao; Tao Zhang; Huan-min Zhou (In Vitro Cellular & Developmental Biology - Animal, 2018)

Improved plane layout of stabilizing piles based on the piecewise function expression of the irregular driving force - Wen-qiang Liu; Qun Li; Jian Lu; Chang-dong Li; Wen-min Yao; Jiang-bo Zeng (Journal of Mountain Science, 2018)

Antibacterial constituents from Antarctic fungus, Aspergillus sydowii SP-1 - Wen-ting Li; Dan Luo; Jia-ning Huang; Lin-lin Wang; Feng-guo Zhang; Tao Xi; Jian-min Liao; Yuan-yuan Lu (Natural Product Research, 2018)

The identification of IsiA proteins binding chlorophyll d in the cyanobacterium Acaryochloris marina - Zheng-Ke Li; Yan-Chao Yin; Lu-Dan Zhang; Zhong-Chun Zhang; Guo-Zheng Dai; Min Chen; Bao-Sheng Qiu (Photosynthesis Research, 2018)

Cryobiotechnology of forest trees: recent advances and future prospects - Jing-Wei Li; Elif Aylin Ozudogru; Jiao Li; Min-Rui Wang; Wen-Lu Bi; Maurizio Lambardi; Qiao-Chun Wang (Biodiversity and Conservation, 2018)

Anti-Apoptotic Effect of IGF1 on Schwann Exposed to Hyperglycemia is Mediated by Neuritin, a Novel Neurotrophic Factor - Lingfei Yan; Min Xie; He Lu; Hongman Zhang; Min Shi; Yingduan Zhang; Chunhong Xi; Jianbo Li; Tao Yang (Molecular Neurobiology, 2018)

Physical interactions and mutational analysis of MoYpt7 in Magnaporthe oryzae - Lu-yao Huang; Min Wu; Xiao-yun Yu; Lin Li; Fu-cheng Lin; Xiao-hong Liu (Journal of Zhejiang University-SCIENCE B, 2018)

Establishing a Forecast Mathematical Model of Sugarcane Yield and Brix Reduction Based on the Extent of Pokkah Boeng Disease - Ze-ping Wang; Lu Liu; Yu-chi Deng; Yi-jie Li; Ge-min Zhang; Shan-hai Lin; Tie-guang He (Sugar Tech, 2017)

The persistent prevalence and evolution of cross-family recombinant coronavirus GCCDC1 among a bat population: a two-year follow-up - Joseph O. Obameso; Hong Li; Hao Jia; Min Han; Shiyan Zhu; Canping Huang; Yuhui Zhao; Min Zhao; Yu Bai; Fei Yuan; Honglan Zhao; Xia Peng; et al. (Science China Life Sciences, 2017)

Combined effects of soil heterogeneity, herbivory and detritivory on growth of the clonal plant Hydrocotyle vulgaris - Lu Liu; Peter Alpert; Bi-Cheng Dong; Jun-Min Li; Fei-Hai Yu (Plant and Soil, 2017)

Lacustrine shale oil resource potential of Es 3 L Sub-Member of Bonan Sag, Bohai Bay Basin, Eastern China - Shuangfang Lu; Wei Liu; Min Wang; Linye Zhang; Zhentao Wang; Guohui Chen; Dianshi Xiao; Zhandong Li; Huiting Hu (Journal of Earth Science, 2017)

Saikosaponin D relieves unpredictable chronic mild stress induced depressive-like behavior in rats: involvement of HPA axis and hippocampal neurogenesis - Hong-Yan Li; Ying-Hua Zhao; Min-Jie Zeng; Fang Fang; Min Li; Ting-Ting Qin; Lu-Yu Ye; Hong-Wei Li; Rong Qu; Shi-Ping Ma (Psychopharmacology, 2017)

Olivibacter flavus sp. nov., a novel endophytic bacterium isolated from the root of Camellia sinensis - Lei Tian; Tong-Wei Guan; Ling-Ling Yang; Kai-Yang Lu; Bing-Bing Liu; Wei-Xun ChunYu; Min Yin; En-Yuan Li; Yang Ji; Xiao-Ping Zhang; Shu-Kun Tang (Archives of Microbiology, 2017)

Comparison of two matrix-assisted laser desorption ionization-time of flight mass spectrometry systems for the identification of clinical filamentous fungi - Yanfei Huang; Mingxin Zhang; Min Zhu; Mei Wang; Yufeng Sun; Haitong Gu; Jingjing Cao; Xue Li; Shaoya Zhang; Jinglin Wang; Xinxin Lu (World Journal of Microbiology and Biotechnology, 2017)

Spatial and temporal changes in desertification in the southern region of the Tengger Desert from 1973 to 2009 - Qingyu Guan; Wenqian Guan; Jing Yang; Shilei Zhao; Baotian Pan; Lei Wang; Na Song; Min Lu; Fuchun Li (Theoretical and Applied Climatology, 2017)

TGF-β1-miR-200a-PTEN induces epithelial–mesenchymal transition and fibrosis of pancreatic stellate cells - Min Xu; Guoying Wang; Hailang Zhou; Jing Cai; Ping Li; Meng Zhou; Ying Lu; Xiaomeng Jiang; Hongmei Huang; Youli Zhang; Aihua Gong (Molecular and Cellular Biochemistry, 2017)

Enhancement of simultaneous algicidal and denitrification of immobilized Acinetobacter sp. J25 with magnetic Fe3O4 nanoparticles - Jun feng Su; Dong hui Liang; Ting lin Huang; Li Wei; Min Ma; Jinsuo Lu (Environmental Science and Pollution Research, 2017)

Characterization and Complete Genome Sequence of a Novel Siphoviridae Bacteriophage BS5 - Xue Meng; Min Wang; Siyuan You; Duobing Wang; Yan Li; Zhaoyang Liu; Yu Gao; Lu Liu; Yaoyuan Zhang; Zhenghao Yan; Chunyan Liu; Yong Jiang; et al. (Current Microbiology, 2017)

The Research on the Relationship of RAGE, LRP-1, and Aβ Accumulation in the Hippocampus, Prefrontal Lobe, and Amygdala of STZ-Induced Diabetic Rats - Lou-Yan Ma; Yu-Lang Fei; Xiao-Ye Wang; Song-Di Wu; Jun-Hui Du; Mei Zhu; Long Jin; Ming Li; Hai-Long Li; Jia-Jia Zhai; Lu-Peng Ji; Ran-Ran Ma; et al. (Journal of Molecular Neuroscience, 2017)

A novel lectin from Artocarpus lingnanensis induces proliferation and Th1/Th2 cytokine secretion through CD45 signaling pathway in human T lymphocytes - Bo Cui; Lu Li; Qiyan Zeng; Faquan Lin; Lijun Yin; Liejun Liao; Min Huang; Jingping Wang (Journal of Natural Medicines, 2017)

Population pharmacokinetic models of lamotrigine in different age groups of Chinese children with epilepsy - Zhong-bin Zhang; Shuang-min Ji; Ying Han; Li-li Zang; Ying-hui Wang; Wei Lu; Li Wang; Ye Wu (European Journal of Clinical Pharmacology, 2017)

High genetic diversity and absence of phylogeographic structure in breeding populations of vulnerable Saundersilarus saundersi (Charadriiformes: Laridae) in Bohai Bay, China - Ya-Nan Zhang; Bo-Ye Liu; Lu Dong; Hong-Xing Jiang; Xuan Wang; Xue-Min Wang; Chang-Zhan Song; Xiu-Ming Li; Shu-Hong Li (Conservation Genetics, 2017)

Relationship between lightning activity and tropospheric nitrogen dioxide and the estimation of lightning-produced nitrogen oxides over China - Fengxia Guo; Xiaoyu Ju; Min Bao; Ganyi Lu; Zupei Liu; Yawen Li; Yijun Mu (Advances in Atmospheric Sciences, 2017)

Expression profiles of the genes involved in l-ascorbic acid biosynthesis and recycling in Rosa roxburghii leaves of various ages - LiangLiang Li; Min Lu; Huaming An (Acta Physiologiae Plantarum, 2017)

Taxonomy and pathogenicity of Leptographium species associated with Ips subelongatus infestations of Larix spp. in northern China, including two new species - Xue-Wei Liu; Hui-Min Wang; Quan Lu; Cony Decock; Yong-Xia Li; Xing-Yao Zhang (Mycological Progress, 2017)

Developing a rat model of dilated cardiomyopathy with improved survival - Li-juan Shen; Shu Lu; Yong-hua Zhou; Lan Li; Qing-min Xing; Yong-liang Xu (Journal of Zhejiang University-SCIENCE B, 2016)

Target attainment analysis and optimal sampling designs for population pharmacokinetic study on piperacillin/tazobactam in neonates and young infants - Yewei Chen; Jinmiao Lu; Min Dong; Dan Wu; Yiqing Zhu; Qin Li; Chao Chen; Zhiping Li (European Journal of Clinical Pharmacology, 2016)

Heavy metals in the riverbed surface sediment of the Yellow River, China - Qingyu Guan; Ao Cai; Feifei Wang; Lei Wang; Tao Wu; Baotian Pan; Na Song; Fuchun Li; Min Lu (Environmental Science and Pollution Research, 2016)

Antialgal and antilarval activities of bioactive compounds extracted from the marine dinoflagellate Amphidinium carterae - Xianyu Kong; Xiurong Han; Min Gao; Rongguo Su; Ke Wang; Xuzhao Li; Wei Lu (Journal of Ocean University of China, 2016)

Phospholipase C Beta 1: a Candidate Signature Gene for Proneural Subtype High-Grade Glioma - Guangrong Lu; Jeffrey T. Chang; Zheyu Liu; Yong Chen; Min Li; Jay-Jiguang Zhu (Molecular Neurobiology, 2016)

Ethanol Increases Mechanical Pain Sensitivity in Rats via Activation of GABAA Receptors in Medial Prefrontal Cortex - Kai-Wen Geng; Ting He; Rui-Rui Wang; Chun-Li Li; Wen-Jun Luo; Fang-Fang Wu; Yan Wang; Zhen Li; Yun-Fei Lu; Su-Min Guan; Jun Chen (Neuroscience Bulletin, 2016)

Multienzymatic cascade synthesis of fucosyloligosaccharide via a two-step fermentation strategy in Escherichia coli - Hui-Min Qin; Songtao Li; Yu-Fu Zhang; Jian-Wen Wang; Jixuan Li; Shiyi Song; Fuping Lu; Yu Li (Biotechnology Letters, 2016)

In Vivo Exposure of Kaempferol Is Driven by Phase II Metabolic Enzymes and Efflux Transporters - Liang Zheng; Lijun Zhu; Min Zhao; Jian Shi; Yuhuan Li; Jia Yu; Huangyu Jiang; Jinjun Wu; Yunli Tong; Yuting Liu; Ming Hu; Linlin Lu; et al. (The AAPS Journal, 2016)

Methotrexate affects HMGB1 expression in rheumatoid arthritis, and the downregulation of HMGB1 prevents rheumatoid arthritis progression - Yuan-bo Li; Peng Xu; Ke Xu; Yong-Song Cai; Meng-yao Sun; Le Yang; Jian Sun; She-min Lu (Molecular and Cellular Biochemistry, 2016)

Levels, congener profile and inventory of polychlorinated biphenyls in sediment from the Songhua River in the vicinity of cement plant, China: a case study - Song Cui; Qiang Fu; Yi-Fan Li; Wen-long Li; Tian-xiao Li; Min Wang; Zhen-xiang Xing; Lu-ji Zhang (Environmental Science and Pollution Research, 2016)

Occurrence conditions of positive cloud-to-ground flashes in severe thunderstorms - FengXia Guo; GanYi Lu; Xin Wu; HaoLiang Wang; ZuPei Liu; Min Bao; YaWen Li (Science China Earth Sciences, 2016)

Neurovascular Invasion and Histological Grade Serve as the Risk Factors of Cervical Lymph Node Metastases in Early Tongue Squamous Cell Carcinoma - Kailiu Wu; Xi Yang; Liwen Li; Min Ruan; Wei Liu; Wei Lu; Chenping Zhang; Siyi Li (Molecular Neurobiology, 2016)

Cognitive-enhancing effects of hydrolysate of polygalasaponin in SAMP8 mice - Pan Xu; Shu-ping Xu; Ke-zhu Wang; Cong Lu; Hong-xia Zhang; Rui-le Pan; Chang Qi; Yan-yan Yang; Ying-hui Li; Xin-min Liu (Journal of Zhejiang University-SCIENCE B, 2016)

Adenylate kinase: a novel antigen for immunodiagnosis and subunit vaccine against tuberculosis - Yangjiong Xiao; Wei Sha; Zhaofeng Tian; Yingying Chen; Ping Ji; Qin Sun; Huiyu Wang; Shujun Wang; Yong Fang; Han-Li Wen; Hui-min Zhao; Jie Lu; et al. (Journal of Molecular Medicine, 2016)

Cardiac-Specific Knockout of ETA Receptor Mitigates Paraquat-Induced Cardiac Contractile Dysfunction - Jiaxing Wang; Songhe Lu; Qijun Zheng; Nan Hu; Wenjun Yu; Na Li; Min Liu; Beilei Gao; Guoyong Zhang; Yingmei Zhang; Haichang Wang (Cardiovascular Toxicology, 2016)

Microbial communities of an arable soil treated for 8 years with organic and inorganic fertilizers - Chen Chen; Jianan Zhang; Min Lu; Chun Qin; Yahua Chen; Li Yang; Qiwei Huang; Jichen Wang; Zhenguo Shen; Qirong Shen (Biology and Fertility of Soils, 2016)

Interaction of TIM4 and TIM3 induces T helper 1 cell apoptosis - Rong-Ti Ge; Lu Zeng; Li-Hua Mo; Ling-Zhi Xu; Huan-Ping Zhang; Hai-Qiong Yu; Min Zhang; Zhi-Gang Liu; Zhan-Ju Liu; Ping-Chang Yang (Immunologic Research, 2016)

Sphingomonas qilianensis sp. nov., Isolated from Surface Soil in the Permafrost Region of Qilian Mountains, China - Ai-Lian Piao; Xiao-Min Feng; Yuichi Nogi; Lu Han; Yonghong Li; Jie Lv (Current Microbiology, 2016)

Rhodiola rosea extends lifespan and improves stress tolerance in silkworm, Bombyx mori - Cong Chen; Jiangbo Song; Min Chen; Zhiquan Li; Xiaoling Tong; Hai Hu; Zhonghuai Xiang; Cheng Lu; Fangyin Dai (Biogerontology, 2016)

Pubertal exposure to di-(2-ethylhexyl)-phthalate inhibits G9a-mediated histone methylation during spermatogenesis in mice - Chuan Liu; Peng Qian; Lingling Yang; Lei Zhang; Chunhai Chen; Mindi He; Yonghui Lu; Wei Feng; Min Li; Yanwen Zhang; Min Zhong; Zhengping Yu; et al. (Archives of Toxicology, 2016)

Transcriptome sequencing discovers genes related to fatty acid biosynthesis in the seeds of Eucommia ulmoides - Yan-zhi Feng; Lu Wang; Jian-min Fu; Ta-na Wuyun; Hong-yan Du; Xiao-feng Tan; Feng Zou; Fang-dong Li (Genes & Genomics, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Effects of freshwater leaching on potential bioavailability of heavy metals in tidal flat soils - Hui Li; Jun Lu; Qu-Sheng Li; Bao-Yan He; Xiu-Qin Mei; Dan-Ping Yu; Zhi-Min Xu; Shi-Hong Guo; Hui-Jun Chen (Environmental Geochemistry and Health, 2016)

Galactosylation of steroidal saponins by β-galactosidase from Lactobacillus bulgaricus L3 - Jie Zhang; Lili Lu; Li Lu; Yang Zhao; Liping Kang; Xu Pang; Jingyuan Liu; Tengchuan Jiang; Min Xiao; Baiping Ma (Glycoconjugate Journal, 2016)

Clinical validation of a novel real-time human papillomavirus assay for simultaneous detection of 14 high-risk HPV type and genotyping HPV type 16 and 18 in China - Hui Yang; Lie-Jun Li; Long-Xu Xie; Zhao-Yun Luo; Min Lu; Min Lin; Xiang-bin Zheng; Yue Huang; Li-Ye Yang (Archives of Virology, 2016)

Overexpression of miR-335 confers cell proliferation and tumour growth to colorectal carcinoma cells - Yanxia Lu; Hui Yang; Li Yuan; Guobing Liu; Chao Zhang; Min Hong; Yan Liu; Min Zhou; Fang Chen; Xuenong Li (Molecular and Cellular Biochemistry, 2016)

Notch2 signaling contributes to cell growth, invasion, and migration in salivary adenoid cystic carcinoma - Jing Qu; Min Song; Jian Xie; Xiao-Yu Huang; Xiao-Meng Hu; Rui-Huan Gan; Yong Zhao; Li-Song Lin; Jiang Chen; Xu Lin; Da-Li Zheng; You-Guang Lu (Molecular and Cellular Biochemistry, 2016)

Feasibility of diagnosing unstable plaque in patients with acute coronary syndrome using iMap-IVUS - Jian Liu; Zhao Wang; Wei-min Wang; Qi Li; Yu-liang Ma; Chuan-fen Liu; Ming-yu Lu; Hong Zhao (Journal of Zhejiang University-SCIENCE B, 2015)

Flavobacterium buctense sp. nov., isolated from freshwater - Xiao-Min Feng; Xu Tan; Li Jia; Ping-Ping Long; Lu Han; Jie Lv (Archives of Microbiology, 2015)

HPLC simultaneous determination of arbutin, chlorogenic acid and 6′- O -caffeoylarbutin in different parts of Vaccinium dunalianum Wight - Xu-Lu Luo; Na Li; Min Xu; Hong-Tao Zhu; Peng He; Yong Ding; Ping Zhao; Ying-Jun Zhang (Natural Product Research, 2015)

Influence of Sedimentation Rate on the Metal Contamination in Sediments of Bohai Bay, China - Yan Zhang; Xueqiang Lu; Xiaolong Shao; Honglei Liu; Meinan Xing; Feng Zhao; Xiaojuan Li; Min Yuan (Bulletin of Environmental Contamination and Toxicology, 2015)

Celastrol Ameliorates EAE Induction by Suppressing Pathogenic T Cell Responses in the Peripheral and Central Nervous Systems - Ying Wang; Lu Cao; Li-min Xu; Fan-fan Cao; Bin Peng; Xue Zhang; Yu-fan Shen; Georges Uzan; Deng-hai Zhang (Journal of Neuroimmune Pharmacology, 2015)

Genome-wide identification and characterization of Fox genes in the silkworm, Bombyx mori - JiangBo Song; ZhiQuan Li; XiaoLing Tong; Cong Chen; Min Chen; Gang Meng; Peng Chen; ChunLin Li; YaQun Xin; TingTing Gai; FangYin Dai; Cheng Lu (Functional & Integrative Genomics, 2015)

Union is strength: matrix elasticity and microenvironmental factors codetermine stem cell differentiation fate - Hongwei Lv; Lisha Li; Yin Zhang; Zhishen Chen; Meiyu Sun; Tiankai Xu; Licheng Tian; Man Lu; Min Ren; Yuanyuan Liu; Yulin Li (Cell and Tissue Research, 2015)

Identification and characterization of microRNA expression in Ginkgo biloba L. leaves - Li Wang; Jianguo Zhao; Min Zhang; Weixin Li; Kaige Luo; Zhaogeng Lu; Changquan Zhang; Biao Jin (Tree Genetics & Genomes, 2015)

Effects of glucose, insulin and triiodothyroxine on leptin and leptin receptor expression and the effects of leptin on activities of enzymes related to glucose metabolism in grass carp (Ctenopharyngodon idella) hepatocytes - Rong-Hua Lu; Yi Zhou; Xiao-Chen Yuan; Xu-Fang Liang; Liu Fang; Xiao-Li Bai; Min Wang; Yu-Hua Zhao (Fish Physiology and Biochemistry, 2015)

Altered microRNA Expression in Peripheral Blood Mononuclear Cells from Young Patients with Schizophrenia - Hui-min Fan; Xin-yang Sun; Wei Niu; Lin Zhao; Qiao-Li Zhang; Wan-shuai Li; Ai-fang Zhong; Li-yi Zhang; Jim Lu (Journal of Molecular Neuroscience, 2015)

Therapeutic potential of human umbilical cord blood mesenchymal stem cells on erectile function in rats with cavernous nerve injury - Jian-Qiang Zhu; Hong-Kai Lu; Zhi-Qiang Cui; Yong-Chuan Wang; Yong-Hui Li; Weixin Zhao; Qiang Fu; Yue-Min Xu; Yong Xu; Lu-Jie Song (Biotechnology Letters, 2015)

Effects of heat stress on serum insulin, adipokines, AMP-activated protein kinase, and heat shock signal molecules in dairy cows - Li Min; Jian-bo Cheng; Bao-lu Shi; Hong-jian Yang; Nan Zheng; Jia-qi Wang (Journal of Zhejiang University-SCIENCE B, 2015)

Establishment and maintenance of a standardized glioma tissue bank: Huashan experience - Abudumijiti Aibaidula; Jun-feng Lu; Jin-song Wu; He-jian Zou; Hong Chen; Yu-qian Wang; Zhi-yong Qin; Yu Yao; Ye Gong; Xiao-ming Che; Ping Zhong; Shi-qi Li; et al. (Cell and Tissue Banking, 2015)

Pitavastatin calcium improves endothelial function and delays the progress of atherosclerosis in patients with hypercholesterolemia - Jing Zhao; Hui-min Yan; Ya Li; Jia Wang; Lu Han; Zhi-hao Wang; Meng-xiong Tang; Wei Zhang; Yun Zhang; Ming Zhong (Journal of Zhejiang University-SCIENCE B, 2015)

Omega-3 Fatty Acids and Primary and Secondary Prevention of Cardiovascular Disease - Yong Cao; Lei Lu; Jun Liang; Min Liu; Xianchi Li; RongRong Sun; Yi Zheng; Peiying Zhang (Cell Biochemistry and Biophysics, 2015)

Cytokine production suppression by culture supernatant of B16F10 cells and amelioration by Ganoderma lucidum polysaccharides in activated lymphocytes - Li-Xin Sun; Wei-Dong Li; Zhi-Bin Lin; Xin-Suo Duan; En-Hong Xing; Miao-Miao Jiang; Ning Yang; Hai-Hua Qi; Yu Sun; Min Li; Yan-Dong Niu; Jie Lu (Cell and Tissue Research, 2015)

Silencing the Double-Stranded RNA Binding Protein DGCR8 Inhibits Ovarian Cancer Cell Proliferation, Migration, and Invasion - Yuqi Guo; Peng Tian; Chuanhe Yang; Zhibing Liang; Min Li; Michelle Sims; Lu Lu; Zhan Zhang; Hongwei Li; Lawrence M. Pfeffer; Junming Yue (Pharmaceutical Research, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Mapping of quantitative trait loci for cold tolerance at the early seedling stage in landrace rice Xiang 743 - Wenqiang Liu; Tingting Lu; Yongchao Li; Xiaowu Pan; Yonghong Duan; Jun Min; Xiqin Fu; Xinnian Sheng; Junzhi Xiao; Sanxiong Liu; Jiang Tan; Yi Yao; et al. (Euphytica, 2015)

Thermal effect of intrusive rock on hydrocarbon generation from organic matter - Min Wang; Shuangfang Lu; Shumin Chen; Jianzhong Li; Haitao Xue; Xiaozhi WU; Guohui Chen; Man Zheng; Shiguang Zhang; Wenbiao Huang (Arabian Journal of Geosciences, 2015)

PQ-69, a novel and selective adenosine A1 receptor antagonist with inverse agonist activity - Min Lu; Bo Wang; Cheng Zhang; Xiaomei Zhuang; Mei Yuan; Haoshan Wang; Weizhang Li; Ruibin Su; Jin Li (Purinergic Signalling, 2014)

Up-regulation of SKIP relates to retinal ganglion cells apoptosis after optic nerve crush in vivo - Yu Wu; Fan Xu; Hui Huang; Lifei Chen; Meidan Wen; Li Jiang; Lu Lu; Li Li; Di Song; Siming Zeng; Li Li; Min Li (Journal of Molecular Histology, 2014)

Antifouling potential of the marine microalga Dunaliella salina - Min Gao; Fengchao Li; Rongguo Su; Ke Wang; Xuzhao Li; Wei Lu (World Journal of Microbiology and Biotechnology, 2014)

Effects of Paraquat on Photosynthetic Pigments, Antioxidant Enzymes, and Gene Expression in Chlorella pyrenoidosa Under Mixotrophic Compared With Autotrophic Conditions - Weiguo Zhang; Min Liu; Peiliang Zhang; Fugen Yu; Shan Lu; Pengfu Li; Junying Zhou (Archives of Environmental Contamination and Toxicology, 2014)

Upregulation of Gem relates to retinal ganglion cells apoptosis after optic nerve crush in adult rats - Fan Xu; Hui Huang; Yu Wu; Lu Lu; Li Jiang; Lifei Chen; Siming Zeng; Li Li; Min Li (Journal of Molecular Histology, 2014)

Antifouling potential of bacteria isolated from a marine biofilm - Min Gao; Ke Wang; Rongguo Su; Xuzhao Li; Wei Lu (Journal of Ocean University of China, 2014)

The Melanogenesis-Inhibitory Effect and the Percutaneous Formulation of Ginsenoside Rb1 - Lin Wang; Ai-Ping Lu; Zhi-Ling Yu; Ricky N. S. Wong; Zhao-Xiang Bian; Hoi-Hin Kwok; Patrick Ying-Kit Yue; Li-Min Zhou; HuBiao Chen; Min Xu; Zhijun Yang (AAPS PharmSciTech, 2014)

Structure and function of the neck cell during fertilization in Ginkgo biloba L. - Di Wang; Yan Lu; Min Zhang; Zhaogeng Lu; Kaige Luo; Fangmei Cheng; Li Wang (Trees, 2014)

Bimodal voltage dependence of TRPA1: mutations of a key pore helix residue reveal strong intrinsic voltage-dependent inactivation - Xia Wan; Yungang Lu; Xueqin Chen; Jian Xiong; Yuanda Zhou; Ping Li; Bingqing Xia; Min Li; Michael X. Zhu; Zhaobing Gao (Pflügers Archiv - European Journal of Physiology, 2014)

6′- O -Caffeoylarbutin inhibits melanogenesis in zebrafish - Min Xu; Qiao-Cong Lao; Ping Zhao; Xiao-Yu Zhu; Hong-Tao Zhu; Xu-Lu Luo; Chong-Ren Yang; Jian-Hui He; Chun-Qi Li; Ying-Jun Zhang (Natural Product Research, 2014)

Corynoxine, a Natural Autophagy Enhancer, Promotes the Clearance of Alpha-Synuclein via Akt/mTOR Pathway - Lei-Lei Chen; Ju-Xian Song; Jia-Hong Lu; Zhen-Wei Yuan; Liang-Feng Liu; Siva Sundara Kumar Durairajan; Min Li (Journal of Neuroimmune Pharmacology, 2014)

Three homologous genes encoding functional ∆8-sphingolipid desaturase in Populus tomentosa - Shu-Fen Li; Guo-Jun Zhang; Ying-Chun Yuan; Cong-Hui Wang; Wu-Jun Gao; Chuan-Liang Deng; Long-Dou Lu; Zan-Min Hu (Genes & Genomics, 2014)

Synthesis, Spectroscopic Properties, and Biological Applications of Eight Novel Chlorinated Fluorescent Proteins-labeling Probes - Xianglong Wu; Min Tian; Wutu Fan; Yalei Pan; Yuankun Zhai; Yinbo Niu; Chenrui Li; Tingli Lu; Qibing Mei (Journal of Fluorescence, 2014)

Application of T-DNA activation tagging to identify glutamate receptor-like genes that enhance drought tolerance in plants - Guihua Lu; Xiping Wang; Junhua Liu; Kun Yu; Yang Gao; Haiyan Liu; Changgui Wang; Wei Wang; Guokui Wang; Min Liu; Guanfan Mao; Binfeng Li; et al. (Plant Cell Reports, 2014)

The metabolism of 8-heptadecene in Pyropia (Bangiaceae, Rhodophyta) - Min Zhang; Rui-Xia Li; Chuan-Ming Hu; Li-En Yang; Jun Tang; Qin-Qin Lu; Tao Zhang; Zong-Gen Shen; Song-Dong Shen; Pu Xu; Jian-Yi Zhu (Journal of Applied Phycology, 2014)

Photosynthetic responses of Oryza sativa L. seedlings to cadmium stress: physiological, biochemical and ultrastructural analyses - Yuwen Wang; Xiaohan Jiang; Kang Li; Min Wu; Rufeng Zhang; Lu Zhang; Guoxiang Chen (BioMetals, 2014)

AtMYB20 is negatively involved in plant adaptive response to drought stress - Shuai Gao; Yong Li Zhang; Lu Yang; Jian Bo Song; Zhi Min Yang (Plant and Soil, 2014)

Serum lipocalin-2, cathepsin S and chemerin levels and nonalcoholic fatty liver disease - Zi Ye; Suijun Wang; Zhen Yang; Min He; Shuo Zhang; Weiwei Zhang; Jie Wen; Qin Li; Ying Huang; Xuanchun Wang; Bin Lu; Zhaoyun Zhang; et al. (Molecular Biology Reports, 2014)

GbMPK3, a mitogen-activated protein kinase from cotton, enhances drought and oxidative stress tolerance in tobacco - Lu Long; Wei Gao; Li Xu; Min Liu; Xiangyin Luo; Xin He; Xiyan Yang; Xianlong Zhang; Longfu Zhu (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Is there a difference in cognitive development between preschool singletons and twins born after intracytoplasmic sperm injection or in vitro fertilization? - Lan-Feng Xing; Yu-Li Qian; Lu-Ting Chen; Fan-Hong Zhang; Xin-Fen Xu; Fan Qu; Yi-Min Zhu (Journal of Zhejiang University-SCIENCE B, 2014)

Charlson comorbidity index helps predict the risk of mortality for patients with type 2 diabetic nephropathy - You-Qun Huang; Rong Gou; Yong-Shu Diao; Qing-Hua Yin; Wen-Xing Fan; Ya-Ping Liang; Yi Chen; Min Wu; Li Zang; Ling Li; Jing Zang; Lu Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Green tea catechins: a fresh flavor to anticancer therapy - Yang Yu; Yuan Deng; Bang-min Lu; Yong-xi Liu; Jian Li; Jin-ku Bao (Apoptosis, 2014)

Expression of SbSNAC1, a NAC transcription factor from sorghum, confers drought tolerance to transgenic Arabidopsis - Min Lu; Deng-Feng Zhang; Yun-Su Shi; Yan-Chun Song; Tian-Yu Wang; Yu Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Molecular characterization of novel haplotypes of eIF4E family in Chinese cabbage (Brassica rapa L. ssp. pekinensis) - Shuan-Tao Liu; Zhi-Gang Zhang; Qiao-Yun Li; Shu-Fen Wang; Zhi-Zhong Zhao; Jin-Dong Lu; Wen-Ling Xu; Xian-Xian Liu; Wei-Min Fu (Genes & Genomics, 2013)

Seed morphological diversity of Pedicularis (Orobanchaceae) and its taxonomic significance - Min-Lu Liu; Wen-Bin Yu; De-Zhu Li; Robert R. Mill; Hong Wang (Plant Systematics and Evolution, 2013)

Diversity of Gene Cassette Promoter Variants of Class 1 Integrons in Uropathogenic Escherichia coli - Quhao Wei; Xiaofei Jiang; Min Li; Gang Li; Qingfeng Hu; Huoxiang Lu; Guoqiang Chen; Yonglie Zhou; Yuan Lu (Current Microbiology, 2013)

Erratum to: Genetic variants of fibroblast growth factor receptor 2 (FGFR2) are associated with breast cancer risk in Chinese women of the Han nationality - Fan Chen; Min Lu; Yun Xue; Jing Zhou; Feifei Hu; Xin Chen; Zhanqin Zhao; Yang Li; XingGuo Wang (Immunogenetics, 2013)

Climate change trend in China, with improved accuracy - Tian-Xiang Yue; Na Zhao; R. Douglas Ramsey; Chen-Liang Wang; Ze-Meng Fan; Chuan-Fa Chen; Yi-Min Lu; Bai-Lian Li (Climatic Change, 2013)

Genome-wide transcriptional analysis of apoptosis-related genes and pathways regulated by H2AX in lung cancer A549 cells - Chengrong Lu; Min Xiong; Yuan Luo; Jing Li; Yanjun Zhang; Yaqiong Dong; Yanjun Zhu; Tianhui Niu; Zhe Wang; Lianning Duan (Apoptosis, 2013)

Microlunatus cavernae sp. nov., a novel actinobacterium isolated from Alu ancient cave, Yunnan, south-west China - Juan Cheng; Wei Chen; Bing Huo-Zhang; Salam Nimaichand; En-Min Zhou; Xin-Hua Lu; Hans-Peter Klenk; Wen-Jun Li (Antonie van Leeuwenhoek, 2013)

Lack of association between SLCO1B1 polymorphism and the lipid-lowering effects of atorvastatin and simvastatin in Chinese individuals - Qiang Fu; Yan-Peng Li; Yuan Gao; Song-Hua Yang; Pei-Qi Lu; Min Jia; Li-Rong Zhang (European Journal of Clinical Pharmacology, 2013)

Study on reproductive barriers in 4x–2x crosses in Dianthus caryophyllus L - Xuhong Zhou; Min Gui; Dandan Zhao; Min Chen; Suping Ju; Shenchong Li; Zhenhong Lu; Xijun Mo; Jihua Wang (Euphytica, 2013)

Interactions of interleukin-12A and interleukin-12B polymorphisms on the risk of intracranial aneurysm - Li-Juan Li; Xin-Min Pan; Xiutian Sima; Zhao-Hui Li; Lu-Shun Zhang; Hong Sun; Yi Zhu; Wei-Bo Liang; Lin-Bo Gao; Lin Zhang (Molecular Biology Reports, 2012)

Overexpression of actin-depolymerizing factor blocks oxidized low-density lipoprotein-induced mouse brain microvascular endothelial cell barrier dysfunction - Jun Wang; Lu Sun; Yan-Fang Si; Bao-Min Li (Molecular and Cellular Biochemistry, 2012)

The role of leptin in lipid metabolism in fatty degenerated hepatocytes of the grass carp Ctenopharyngodon idellus - Rong-Hua Lu; Xu-Fang Liang; Min Wang; Yi Zhou; Xiao-Li Bai; Yan He (Fish Physiology and Biochemistry, 2012)

An Overview of Tubulin Inhibitors That Interact with the Colchicine Binding Site - Yan Lu; Jianjun Chen; Min Xiao; Wei Li; Duane D. Miller (Pharmaceutical Research, 2012)

Stat5a increases lactation of dairy cow mammary gland epithelial cells cultured in vitro - Xiao Fei Liu; Meng Li; Qing Zhang Li; Li Min Lu; Hui Li Tong; Xue Jun Gao (In Vitro Cellular & Developmental Biology - Animal, 2012)

A maize stress-responsive NAC transcription factor, ZmSNAC1, confers enhanced tolerance to dehydration in transgenic Arabidopsis - Min Lu; Sheng Ying; Deng-Feng Zhang; Yun-Su Shi; Yan-Chun Song; Tian-Yu Wang; Yu Li (Plant Cell Reports, 2012)

VEGF upregulates VEGF receptor-2 on human outer root sheath cells and stimulates proliferation through ERK pathway - Wei Li; Zhong-Fa Lu; Xiao-Yong Man; Chun-Ming Li; Jiong Zhou; Jia-Qi Chen; Xiao-Hong Yang; Xian-Jie Wu; Sui-Qing Cai; Min Zheng (Molecular Biology Reports, 2012)

Value of a new post-procedural intravascular ultrasound score in predicting target vessel revascularization after coronary drug-eluting stents implantation - Kai Xu; Ya-ling Han; Quan-min Jing; Shou-li Wang; Ying-yan Ma; Xiao-zeng Wang; Geng Wang; Zu-lu Wang (Journal of Zhejiang University-SCIENCE B, 2012)

Proteomic analysis of the nuclear phosphorylated proteins in dairy cow mammary epithelial cells treated with estrogen - Jian-guo Huang; Xue-jun Gao; Qing-zhang Li; Li-min Lu; Rong Liu; Chao-chao Luo; Jia-li Wang; Qiao Bin; Xin Jin (In Vitro Cellular & Developmental Biology - Animal, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Construction of an infectious clone of human adenovirus type 41 - Duo-Ling Chen; Liu-Xin Dong; Meng Li; Xiao-Juan Guo; Min Wang; Xin-Feng Liu; Zhuo-Zhuang Lu; Tao Hung (Archives of Virology, 2012)

ABA-mediated inhibition of seed germination is associated with ribosomal DNA chromatin condensation, decreased transcription, and ribosomal RNA gene hypoacetylation - Lu Zhang; Yong Hu; Shihan Yan; Hui Li; Shibin He; Min Huang; Lijia Li (Plant Molecular Biology, 2012)

Blockade of p53 by HIF-2α, but not HIF-1α, is involved in arsenite-induced malignant transformation of human bronchial epithelial cells - Yuan Xu; Yuan Li; Ying Pang; Min Ling; Lu Shen; Rongrong Jiang; Yue Zhao; Jianwei Zhou; Xinru Wang; Qizhan Liu (Archives of Toxicology, 2012)

Etiology and epidemiology of viral diarrhea in children under the age of five hospitalized in Tianjin, China - Yabo Ouyang; Hui Ma; Min Jin; Xinwei Wang; Jingfeng Wang; Lu Xu; Shuxiang Lin; Zhiqiang Shen; Zhaoli Chen; Zhigang Qiu; Zhixian Gao; Lin Peng; et al. (Archives of Virology, 2012)

Diversification of the Waxy Gene is Closely Related to Variations in Rice Eating and Cooking Quality - Zujian Zhang; Min Li; Yuwei Fang; Facai Liu; Yue Lu; Qingcai Meng; Juncheng Peng; Xiuhua Yi; Minghong Gu; Changjie Yan (Plant Molecular Biology Reporter, 2012)

Effects of a non-selective TRPC channel blocker, SKF-96365, on melittininduced spontaneous persistent nociception and inflammatory pain hypersensitivity - Jing Ding; Jia-Rui Zhang; Yan Wang; Chun-Li Li; Dan Lu; Su-Min Guan; Jun Chen (Neuroscience Bulletin, 2012)

High-level expression of bioactive recombinant human lysozyme in the milk of transgenic mice using a modified human lactoferrin BAC - Shen Liu; Xiangqing Li; Dan Lu; Shengzhe Shang; Meili Wang; Min Zheng; Ran Zhang; Bo Tang; Qiuyan Li; Yunping Dai; Ning Li (Transgenic Research, 2012)

Cathode Reactions and Applications in Microbial Fuel Cells: A Review - Min Lu; Sam Fong Yau Li (Critical Reviews in Environmental Science and Technology, 2012)

Characteristics and evolution of the PUF gene family in Bombyx mori and 27 other species - Chun-Dong Zhang; Min-Hui Pan; Juan Tan; Fang-Fang Li; Jun Zhang; Ting-Ting Wang; Cheng Lu (Molecular Biology Reports, 2012)

Single nucleotide polymorphism of CACNA2D1 gene and its association with milk somatic cell score in cattle - Zheng Rong Yuan; Jiao Li; Li Liu; Lu Pei Zhang; Li Min Zhang; Cui Chen; Xiao Jie Chen; Xue Gao; Jun Ya Li; Jin Bao Chen; Hui Jiang Gao; Shang Zhong Xu (Molecular Biology Reports, 2011)

Functional MRI mapping of category-specific sites associated with naming of famous faces, animals and man-made objects - Hong-Min Bai; Tao Jiang; Wei-Min Wang; Tian-Dong Li; Yan Liu; Yi-Cheng Lu (Neuroscience Bulletin, 2011)

Association of a LSP1 gene rs3817198T>C polymorphism with breast cancer risk: evidence from 33,920 cases and 35,671 controls - Min-Bin Chen; Chen Li; Wen-Xiang Shen; Yu-Jiang Guo; Wei Shen; Pei-Hua Lu (Molecular Biology Reports, 2011)

Human amniotic fluid-derived stem cells can differentiate into hepatocyte-like cells in vitro and in vivo - Hui Liu; Da-qing Liu; Bao-wei Li; Li-dong Guan; Zhi-feng Yan; Ya-li Li; Xue-tao Pei; Wen Yue; Min Wang; Yan-ping Lu; Hong-mei Peng; Yang Lv (In Vitro Cellular & Developmental Biology - Animal, 2011)

Effect of diindolylmethane on Ca2+ movement and viability in HA59T human hepatoma cells - Jin-Shiung Cheng; Su-Shung Shu; Chun-Chi Kuo; Chiang-Ting Chou; Wei-Lun Tsai; Yi-Chien Fang; Li-Ni Kuo; Jeng-Hsien Yeh; Wei-Chuan Chen; Jau-Min Chien; Ti Lu; Chih-Chuan Pan; et al. (Archives of Toxicology, 2011)

Biofilm-electrode process with high efficiency for degradation of 2,4-dichlorophenol - Xue-Na Zhang; Wei-Min Huang; Xuan Wang; Huiting Li; Hai-Yan Lu; Hai-Bo Lin (Environmental Chemistry Letters, 2011)

Increased urinary 8-hydroxy-2′-deoxyguanosine levels in workers exposed to di-(2-ethylhexyl) phthalate in a waste plastic recycling site in China - Qian Wang; Li Wang; Xi Chen; Kai Min Rao; Shao You Lu; Sheng Tao Ma; Pu Jiang; Dan Zheng; Shun Qing Xu; Hong Yan Zheng; Jian Shu Wang; Zhi Qiang Yu; et al. (Environmental Science and Pollution Research, 2011)

Single amino acid residue changes in subsite −1 of levansucrase from Zymomonas mobilis 10232 strongly influence the enzyme activities and products - Shuying Li; Yongliang Yan; Zhengfu Zhou; Haiying Yu; Yuhua Zhan; Wei Zhang; Ming Chen; Wei Lu; Shuzhen Ping; Min Lin (Molecular Biology Reports, 2011)

Minimally-invasive treatment of communicating hydrocephalus using a percutaneous lumboperitoneal shunt - Lu Jia; Zhong-xin Zhao; Chao You; Jia-gang Liu; Si-qing Huang; Min He; Pei-gang Ji; Jie Duan; Yi-jun Zeng; Guo-ping Li (Journal of Zhejiang University-SCIENCE B, 2011)

Molecular epidemiology of Echovirus 30 in Taiwan, 1988–2008 - Guan-Ming Ke; Kuei-Hsiang Lin; Po-Liang Lu; Yi-Chin Tung; Chu-Feng Wang; Liang-Yin Ke; Min-Sheng Lee; Pei-Chin Lin; Hui-Ju Su; Yi-Ying Lin; Tzu-Ping Huang; Jen-Ren Wang; et al. (Virus Genes, 2011)

Genetic Diversity and Identity of Chinese Loquat Cultivars/Accessions (Eriobotrya japonica) Using Apple SSR Markers - Qiao He; Xiong Wei Li; Guo Lu Liang; Kun Ji; Qi Gao Guo; Wei Min Yuan; Gen Zhi Zhou; Kun Song Chen; W. Eric van de Weg; Zhong Shan Gao (Plant Molecular Biology Reporter, 2011)

Molecular characterization of a thioredoxin h gene (HbTRX1) from Hevea brasiliensis showing differential expression in latex between self-rooting juvenile clones and donor clones - Hui-Liang Li; Hui-Zhong Lu; Dong Guo; Wei-Min Tian; Shi-Qing Peng (Molecular Biology Reports, 2011)

Analysis of correlation between blood biochemical indicators and bone mineral density of post-menopausal women - Shun-zhi Liu; Li-fang Tian; Peng Xu; Gui-hua Zhuang; Fang Zheng; Juan Tian; Qi-Lan Ning; Bo-Feng Zhu; She-Min Lu; Hong Yan (Molecular Biology Reports, 2011)

Constituents with α-glucosidase and advanced glycation end-product formation inhibitory activities from Salvia miltiorrhiza Bge. - Hai-Ying Ma; Hui-Yuan Gao; Lu Sun; Jian Huang; Xiao-Min Xu; Li-Jun Wu (Journal of Natural Medicines, 2011)

Multicomponent Amorphous Nanofibers Electrospun from Hot Aqueous Solutions of a Poorly Soluble Drug - Deng-Guang Yu; Li-Dong Gao; Kenneth White; Christopher Branford-White; Wei-Yue Lu; Li-Min Zhu (Pharmaceutical Research, 2010)

Delisheng, a Chinese medicinal compound, exerts anti-proliferative and pro-apoptotic effects on HepG2 cells through extrinsic and intrinsic pathways - Chuang-xin Lu; Ke-jun Nan; Yan-li Nie; Ya-nan Hai; Min Jiao (Molecular Biology Reports, 2010)

The Arabidopsis chloroplast ribosome recycling factor is essential for embryogenesis and chloroplast biogenesis - Liyuan Wang; Min Ouyang; Qiannan Li; Meijuan Zou; Jinkui Guo; Jinfang Ma; Congming Lu; Lixin Zhang (Plant Molecular Biology, 2010)

Effects of Manganese Deficiency on Spectral Characteristics and Oxygen Evolution in Maize Chloroplasts - Xiaolan Gong; Ying Wang; Chao Liu; Sisi Wang; Xiaoyang Zhao; Min Zhou; Na Li; Yun Lu; Fashui Hong (Biological Trace Element Research, 2010)

Co-culture with cardiomyocytes enhanced the myogenic conversion of mesenchymal stromal cells in a dose-dependent manner - Xiao-qing He; Min-sheng Chen; Shu-Hong Li; Shi-ming Liu; Yun Zhong; Heather Y. McDonald Kinkaid; Wei-Yang Lu; Richard D. Weisel; Ren-Ke Li (Molecular and Cellular Biochemistry, 2010)

Effects of sevoflurane preconditioning and postconditioning on rat myocardial stunning in ischemic reperfusion injury - An-lu Dai; Li-hua Fan; Feng-jiang Zhang; Mei-juan Yang; Jing Yu; Jun-kuan Wang; Tao Fang; Gang Chen; Li-na Yu; Min Yan (Journal of Zhejiang University-SCIENCE B, 2010)

The pheV Phenylalanine tRNA Gene in Klebsiella pneumoniae Clinical Isolates Is an Integration Hotspot for Possible Niche-Adaptation Genomic Islands - Nan Chen; Hong-Yu Ou; Jon Jurriaan van Aartsen; XiaoFei Jiang; Min Li; ZeHua Yang; QuHao Wei; XiaoYun Chen; Xinyi He; Zixin Deng; Kumar Rajakumar; Yuan Lu (Current Microbiology, 2010)

Secular trend of genome types of respiratory adenovirus type 3 during 1983–2005: a study from Taiwan - Yung-Cheng Lin; Kuei-Hsiang Lin; Guan-Ming Ke; Min-Sheng Lee; Pei-Chin Lin; Hsin-Fu Liu; Li-Ching Hsu; Po-Liang Lu (Archives of Virology, 2010)

Analysis of two sequence variants in peroxisome proliferator activated receptor gamma gene in Tajik population at high altitudes and Han population at low altitudes in China - Xiao-Ling Liu; Feng-Lin Zhang; Zhi-Yong Zhou; Hua-Lu Zhao; Guo-Min Shen; Wu-Yun Baohan; Zi-Yuan Duan; Wei Li; Jun-Wu Zhang (Molecular Biology Reports, 2010)

Correlation Analysis Between Bone Mineral Density and Serum Element Contents of Postmenopausal Women in Xi’an Urban Area - Shun-Zhi Liu; Hong Yan; Peng Xu; Jian-Ping Li; Gui-Hua Zhuang; Bo-Feng Zhu; She-Min Lu (Biological Trace Element Research, 2009)

Profiling Gene Expression During Gland Morphogenesis of a Glanded and a Glandless Upland Cotton - Ying-Fan Cai; Min Chen; Quan Sun; Yong-Fang Xie; Sheng-Wei Li; Ming-Feng Jiang; Jian-Chuan Mo; You-Lu Yuan; Yu-Zhen Shi; Huai-Zhong Jiang; Zheng Pan; Yun-Ling Gao; et al. (Journal of Plant Biology, 2009)

Molecular Cloning and Expression of cDNA Encoding the Cysteine Proteinase Inhibitor from Upland Cotton - Ming-feng Jiang; Sheng-wei Li; Min Chen; Ying-fan Cai; Yong-fang Xie; Biao Li; Quan Sun; Huai-zhong Jiang; Zheng Pan; Yun-ling Gao; You-Lu Yuan; Yu-zheng Shi (Journal of Plant Biology, 2009)

Relationships between endothelial nitric oxide synthase gene polymorphisms and osteoporosis in postmenopausal women - Shun-zhi Liu; Hong Yan; Wei-kun Hou; Peng Xu; Juan Tian; Li-fang Tian; Bo-feng Zhu; Jie Ma; She-min Lu (Journal of Zhejiang University-SCIENCE B, 2009)

Environmental estrogenic effects and gonadal development in wild goldfish (Carassius auratus) - Chun-Ri Li; Sang-Hoon Lee; So-Sun Kim; Andre Kim; Keun Woo Lee; Ming Lu; Hee-Eun Kim; Im-Jung Kwak; Yun-Ju Lee; Dong-Kyoo Kim; Jung-Sick Lee; Shin-Won Kang; et al. (Environmental Monitoring and Assessment, 2009)

Influence of HBV gene heterogeneity on the failure of immunization with HBV vaccines in eastern China - She-Lan Liu; Ying Dong; Li Zhang; Min-Wei Li; Jian-er Wo; Li-Wei Lu; Zhen-Juan Chen; Yong-Zhong Wang; Bing Ruan (Archives of Virology, 2009)

Genes Involved in the Benzoate Catabolic Pathway in Acinetobacter calcoaceticus PHEA-2 - Yuhua Zhan; Haiying Yu; Yongliang Yan; Ming Chen; Wei Lu; Shuying Li; Zixin Peng; Wei Zhang; Shuzhen Ping; Jin Wang; Min Lin (Current Microbiology, 2008)

A single residue mutation of 5-enoylpyruvylshikimate-3-phosphate synthase in Pseudomonas stutzeri enhances resistance to the herbicide glyphosate - Aimin Liang; Jiying Sha; Wei Lu; Ming Chen; Liang Li; Dan Jin; Yongliang Yan; Jin Wang; Shuzhen Ping; Wei Zhang; Yiding Wang; Min Lin (Biotechnology Letters, 2008)

Magnaporthe oryzae MTP1 gene encodes a type III transmembrane protein involved in conidiation and conidial germination - Qin Lu; Jian-ping Lu; Xiao-dong Li; Xiao-hong Liu; Hang Min; Fu-cheng Lin (Journal of Zhejiang University-SCIENCE B, 2008)

An ethanol-tolerant recombinant Escherichia coli expressing Zymomonas mobilis pdc and adhB genes for enhanced ethanol production from xylose - Zhanchao Wang; Ming Chen; Yuquan Xu; Shuying Li; Wei Lu; Shuzhen Ping; Wei Zhang; Min Lin (Biotechnology Letters, 2008)

Differential generation of hydrogen peroxide upon exposure to zinc and cadmium in the hyperaccumulating plant specie (Sedum alfredii Hance) - Yue-En Chao; Min Zhang; Sheng-ke Tian; Ling-li Lu; Xiao-e Yang (Journal of Zhejiang University-SCIENCE B, 2008)

Identification of a New Gene Encoding EPSPS with High Glyphosate Resistance from the Metagenomic Library - Dan Jin; Wei Lu; Shuzhen Ping; Wei Zhang; Jian Chen; Baoqing Dun; Ruiqiang Ma; Zhonglin Zhao; Jiying Sha; Liang Li; Zhirong Yang; Ming Chen; et al. (Current Microbiology, 2007)

China Subregional Avian Endemism and Biodiversity Conservation - Fu-Min Lei; Guo-An Wei; Hong-Feng Zhao; Zuo-Hua Yin; Jian-Li Lu (Biodiversity and Conservation, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Opposing Action of Estrogen Receptors α and β on Tumor Necrosis Factor-α Gene Expression and Caspase-8-mediated Apoptotic Effects in HA22T Cells - Erh-Jung Huang; Cheng-Chung Wu; Shin-Da Lee; Juen-Hau Chen; Jer-Yuh Liu; Jiunn-Liang Ko; James A. Lin; Min-Chi Lu; Li-Mien Chen; Chih-Yang Huang; Wei-Wen Kuo (Molecular and Cellular Biochemistry, 2006)

Cardiomyoblast apoptosis induced by insulin-like growth factor (IGF)-I resistance is IGF-II dependent and synergistically enhanced by angiotensin II - Wei-Wen Kuo; Chung-Jung Liu; Li-Ming Chen; Chieh-Hsi Wu; Chun-Hsien Chu; Jer-Yuh Liu; Min-Chi Lu; James A. Lin; Shin-Da Lee; Chih-Yang Huang (Apoptosis, 2006)

In situ and in vitro colonization of Cathaya argyrophylla (Pinaceae) by ectomycorrhizal fungi - Lu-Min Vaario; Shu-Tang Xing; Zong-Qiang Xie; Zhi-Ming Lun; Xue Sun; Yu Hua Li (Mycorrhiza, 2006)

A mesoscale analysis of heavy rain caused by frontal and topographical heterogeneities on Taiwan Island - Jing Li; Lu Hancheng; Wang Hanjie; Zhu Min; Kou Zheng (Advances in Atmospheric Sciences, 2004)

Floral development of Kingdonia (Ranunculaceae s. l., Ranunculales) - Yi Ren; Zhi-jun Li; Hong-li Chang; Yong-ji Lei; An-min Lu (Plant Systematics and Evolution, 2004)

A common IL-13 Arg130Gln single nucleotide polymorphism among Chinese atopy patients with allergic rhinitis - Min Wang; Zhi-Min Xing; Chao Lu; You-Xiang Ma; De-Lin Yu; Zheng Yan; Shen-Wu Wang; Li-Sheng Yu (Human Genetics, 2003)

Annual Reproductive Behavior of Rhinopithecus roxellana - Ren Bao-Ping; Zhang Shu-Yi; Xia Shu-Zhong; Li Qing-Fen; Liang Bing; Lu Min-Qiang (International Journal of Primatology, 2003)

Conservation on diversity and distribution patterns of endemic birds in China - Fu-Min Lei; Yan-Hua Qu; Jian-Li Lu; Yao Liu; Zuo-Hua Yin (Biodiversity and Conservation, 2003)

Mapping of leaf and neck blast resistance genes with resistance gene analog, RAPD and RFLP in rice - Jie-Yun Zhuang; Wen-Bin Ma; Jian-Li Wu; Rong-Yao Chai; Jun Lu; Ye-Yang Fan; Min-Zhong Jin; Hei Leung; Kang-Le Zheng (Euphytica, 2002)

The types of lake in Songnen Plain and their regional character - Jin-fu Lu; Dong-mei Jie; Zhi-min Li; Xue-tian Leng (Chinese Geographical Science, 2000)